Active Personal Eye Lens Dosimetry with the Hybrid Pixelated Dosepix Detector - Beiser, Florian; Haag, Dennis; Ballabriga, Rafael; Behrens, Rolf; Campbell, Michael; Fuhg, Christian; Hufschmidt, Patrick; Hupe, Oliver; Kupillas, Carolin; Llopart, Xavier; Roth, Jurgen; Schmidt, Sebastian; et al. (IEEE Transactions on Radiation and Plasma Medical Sciences, 2023)
Eye lens dosimetry has been an important field of research in the last decade. Dose measurements with a prototype of an active personal eye lens dosemeter based on the Dosepix detector are presented. The personal dose equivalent at 3 mm depth of soft tissue, Hp(3), was measured in the center front of a water-filled cylinder phantom with a height and diameter of 20 cm. The energy dependence of the normalized response is investigated for mean photon energies between 12.4 keV and 248 keV for continuous reference radiation fields (N-series) according to ISO 4037. The response normalized to N-60 (E=47.9 keV) at 0∘ angle of irradiation stays within the approval limits of IEC 61526 for angles of incidence between -75∘ and +75∘. Performance in pulsed photon fields was tested for varying dose rates from 0.1 Svh up to 1000 Svh and pulse durations from 1 ms up to 10 s. The dose measurement works well within the approval limits (acc. to IEC 61526) up to 1 Svh. No significant influence of the pulse duration on the measured dose is found. Reproducibility measurements yield a coefficient of variation which does not exceed 1 % for two tested eye lens dosemeter prototypes.
CRIS-Team Scopus Importer:2023-08-25
Keywords: Active personal dosemeter; Detectors; Dosepix; Dosimetry; dosimetry for interventional procedures; dosimetry for radiation based medical applications; eye lens dosimetry; Histograms; Lenses; Phantoms; Photonics; Prototypes; pulsed x-ray fields; radiation detectors for medical applications: semiconductors

A deep spectromorphological study of the γ -ray emission surrounding the young massive stellar cluster Westerlund 1 - Aharonian, F.; Ashkar, H.; Backes, M.; Martins, V. Barbosa; Becherini, Y.; Berge, D.; Bi, B.; Böttcher, Markus; De Lavergne, M. De Bony; Bradascio, F.; Brose, R.; Brun, F.; et al. (Astronomy & Astrophysics, 2022)
Context. Young massive stellar clusters are extreme environments and potentially provide the means for efficient particle acceleration. Indeed, they are increasingly considered as being responsible for a significant fraction of cosmic rays (CRs) that are accelerated within the Milky Way. Westerlund 1, the most massive known young stellar cluster in our Galaxy, is a prime candidate for studying this hypothesis. While the very-high-energy γ-ray source HESS J1646-458 has been detected in the vicinity of Westerlund 1 in the past, its association could not be firmly identified. Aims. We aim to identify the physical processes responsible for the γ-ray emission around Westerlund 1 and thus to understand the role of massive stellar clusters in the acceleration of Galactic CRs better. Methods. Using 164 h of data recorded with the High Energy Stereoscopic System (H.E.S.S.), we carried out a deep spectromorphological study of the γ-ray emission of HESS J1646-458. We furthermore employed H I and CO observations of the region to infer the presence of gas that could serve as target material for interactions of accelerated CRs. Results. We detected large-scale ( 2 diameter) γ-ray emission with a complex morphology, exhibiting a shell-like structure and showing no significant variation with γ-ray energy. The combined energy spectrum of the emission extends to several tens of TeV, and it is uniform across the entire source region. We did not find a clear correlation of the γ-ray emission with gas clouds as identified through H I and CO observations. Conclusions. We conclude that, of the known objects within the region, only Westerlund 1 can explain the majority of the γ-ray emission. Several CR acceleration sites and mechanisms are conceivable and discussed in detail. While it seems clear that Westerlund 1 acts as a powerful particle accelerator, no firm conclusions on the contribution of massive stellar clusters to the flux of Galactic CRs in general can be drawn at this point.
CRIS-Team Scopus Importer:2022-11-11
Keywords: Acceleration of particles; Galaxies: star clusters: individual: Westerlund 1; Gamma rays: general; Radiation mechanisms: non-thermal; Shock waves; Stars: massive

A first search for coincident gravitational waves and high energy neutrinos using LIGO, Virgo and ANTARES data from 2007 - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J.; Baret, B.; Basa, S.; et al. (Journal of Cosmology and Astroparticle Physics, 2013)
We present the results of the first search for gravitational wave bursts associated with high energy neutrinos. Together, these messengers could reveal new, hidden sources that are not observed by conventional photon astronomy, particularly at high energy. Our search uses neutrinos detected by the underwater neutrino telescope ANTARES in its 5 line configuration during the period January - September 2007, which coincided with the fifth and first science runs of LIGO and Virgo, respectively. The LIGO-Virgo data were analysed for candidate gravitational-wave signals coincident in time and direction with the neutrino events. No significant coincident events were observed. We place limits on the density of joint high energy neutrino - gravitational wave emission events in the local universe, and compare them with densities of merger and core-collapse events.
Keywords: gravitational waves / experiments; neutrino astronomy

All-flavor Search for a Diffuse Flux of Cosmic Neutrinos with Nine Years of ANTARES Data - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; et al. (Astrophysical Journal Letters, 2018)
The ANTARES detector is at present the most sensitive neutrino telescope in the northern hemisphere. The highly significant cosmic neutrino excess observed by the Antarctic IceCube detector can be studied with ANTARES, exploiting its complementing field of view, exposure, and lower energy threshold. Searches for an all-flavor diffuse neutrino signal, covering nine years of ANTARES data taking, are presented in this Letter. Upward-going events are used to reduce the atmospheric muon background. This work includes for the first time in ANTARES both track-like (mainly nu mu) and shower-like (mainly nu(e)) events in this kind of analysis. Track-like events allow for an increase of the effective volume of the detector thanks to the long path traveled by muons in rock and/ or sea water. Shower-like events are well reconstructed only when the neutrino interaction vertex is close to, or inside, the instrumented volume. A mild excess of high-energy events over the expected background is observed in nine years of ANTARES data in both samples. The best fit for a single power-law cosmic neutrino spectrum, in terms of perflavor flux at 100 TeV, is Phi(1f)(0) (100 TeV) = (1.7 +/- 1.0) x 10(-18) GeV-1 cm(-2) s(-1) sr(-1) with spectral index Gamma = 2.4(-0.4)(+0.5) .The null cosmic flux assumption is rejected with a significance of 1.6 sigma .
Keywords: astroparticle physics; neutrinos

All-sky Measurement of the Anisotropy of Cosmic Rays at 10 TeV and Mapping of the Local Interstellar Magnetic Field - Abeysekara, A. U.; Alfaro, R.; Alvarez, C.; Arceo, R.; Arteaga-Velazquez, J. C.; Avila Rojas, D.; Belmont-Moreno, E.; Benzvi, S. Y.; Brisbois, C.; Capistran, T.; Carramiana, A.; Casanova, S.; et al. (Astrophysical Journal, 2019)
We present the first full-sky analysis of the cosmic ray arrival direction distribution with data collected by the High-Altitude Water Cherenkov and IceCube observatories in the northern and southern hemispheres at the same median primary particle energy of 10 TeV. The combined sky map and angular power spectrum largely eliminate biases that result from partial sky coverage and present a key to probe into the propagation properties of TeV cosmic rays through our local interstellar medium and the interaction between the interstellar and heliospheric magnetic fields. From the map, we determine the horizontal dipole components of the anisotropy δ 0h = 9.16 ×10 -4 and δ 6h = 7.25 ×10 -4 (±0.04 × 10 -4 ). In addition, we infer the direction (229.°2 ± 3.°5 R.A., 11.°4 ± 3.°0 decl.) of the interstellar magnetic field from the boundary between large-scale excess and deficit regions from which we estimate the missing corresponding vertical dipole component of the large-scale anisotropy to be δN ∼ -3.97 +1.0 -2.0 × 10 -4 .
CRIS-Team Scopus Importer:2019-05-02
Keywords: astroparticle physics; cosmic rays; ISM: magnetic fields

All-sky search for high-energy neutrinos from gravitational wave event GW170104 with the Antares neutrino telescope: The ANTARES Collaboration - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin, V.; et al. (European Physical Journal C, 2017)
Advanced LIGO detected a significant gravitational wave signal (GW170104) originating from the coalescence of two black holes during the second observation run on January 4th, 2017. Anall-sky high-energy neutrino follow-up search has been made using data from the Antares neutrino telescope, including both upgoing and downgoing events in two separate analyses. No neutrino candidates were found within +/- 500 s around the GW event time nor any time clustering of events over an extended time window of +/- 3 months. The non-detection is used to constrain isotropic-equivalent high-energy neutrino emission from GW170104 to less than similar to 1.2 x 10(55) erg for a E-2 spectrum. This constraint is valid in the energy range corresponding to the 5-95% quantiles of the neutrino flux [3.2 TeV; 3.6 PeV], if the GW emitter was below the Antares horizon at the alert time.

A method for detection of muon induced electromagnetic showers with the ANTARES detector - Aguilar, J. A.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Auberth, J. J.; Baret, B.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2012)
The primary aim of ANTARES is neutrino astronomy with upward going muons created in charged current muon neutrino interactions in the detector and its surroundings. Downward going muons are background for neutrino searches. These muons are the decay products of cosmic-ray collisions in the Earth's atmosphere far above the detector. This paper presents a method to identify and count electromagnetic showers induced along atmospheric muon tracks with the ANTARES detector. The method is applied to both cosmic muon data and simulations and its applicability to the reconstruction of muon event energies is demonstrated. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Neutrino telescope; Electromagnetic shower identification; High energy muons; Energy reconstruction

A method to stabilise the performance of negatively fed KM3NeT photomultipliers - Adrián-Martínez, S.; Ageron, M.; Aiello, S.; Albert, A.; Ameli, F.; Anassontzis, E. G.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Avgitas, T.; et al. (Journal of Instrumentation, 2016)
The KM3NeT research infrastructure, currently under construction in the Mediterranean Sea, will host neutrino telescopes for the identification of neutrino sources in the Universe and for studies of the neutrino mass hierarchy. These telescopes will house hundreds of thousands of photomultiplier tubes that will have to be operated in a stable and reliable fashion. In this context, the stability of the dark counts has been investigated for photomultiplier tubes with negative high voltage on the photocathode and held in insulating support structures made of 3D printed nylon material. Small gaps between the rigid support structure and the photomultiplier tubes in the presence of electric fields can lead to discharges that produce dark count rates that are highly variable. A solution was found by applying the same insulating varnish as used for the high voltage bases directly to the outside of the photomultiplier tubes. This transparent conformal coating provides a convenient and inexpensive method of insulation.
Keywords: Instrument optimization; Large detector systems for particle and astroparticle physics; Neutrino detectors; Photon detectors for UV; visible and IR photons (gas) (gas-photocathodes; solid-photocathodes)

An algorithm for the reconstruction of high-energy neutrino-induced particle showers and its application to the ANTARES neutrino telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (European Physical Journal C, 2017)
A novel algorithm to reconstruct neutrino-induced particle showers within the ANTARES neutrino telescope is presented. The method achieves a median angular resolution of 6. for shower energies below 100TeV. Applying this algorithm to 6 years of data taken with theANTARES detector, 8 events with reconstructed shower energies above 10TeV are observed. This is consistent with the expectation of about 5 events from atmospheric backgrounds, but also compatible with diffuse astrophysical flux measurements by the IceCube collaboration, from which 2-4 additional events are expected. A 90% C.L. upper limit on the diffuse astrophysical neutrino flux with a value per neutrino flavour of E-2.Phi(90%) = 4.9 . 10(-8) GeV.cm(-2).s(-1).sr(-1) is set, applicable to the energy range from 23TeV to 7.8PeV, assuming an unbroken E-2 spectrum and neutrino flavour equipartition at Earth.

An Algorithm for the Reconstruction of Neutrino-induced Showers in the ANTARES Neutrino Telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin, V.; et al. (Astronomical Journal, 2017)
Muons created by nu(mu) charged current (CC) interactions in the water surrounding the ANTARES neutrino telescope have been almost exclusively used so far in searches for cosmic neutrino sources. Due to their long range, highly energetic muons inducing Cherenkov radiation in the water are reconstructed with dedicated algorithms that allow for the determination of the parent neutrino direction with a median angular resolution of about 0 degrees.4 for an E-2 neutrino spectrum. In this paper, an algorithm optimized for accurate reconstruction of energy and direction of shower events in the ANTARES detector is presented. Hadronic showers of electrically charged particles are produced by the disintegration of the nucleus both in CC and neutral current interactions of neutrinos in water. In addition, electromagnetic showers result from the CC interactions of electron neutrinos while the decay of a tau lepton produced in nu(tau) CC interactions will, in most cases, lead to either a hadronic or an electromagnetic shower. A shower can be approximated as a point source of photons. With the presented method, the shower position is reconstructed with a precision of about 1 m; the neutrino direction is reconstructed with a median angular resolution between 2 degrees and 3 degrees in the energy range of 1-1000 TeV. In this energy interval, the uncertainty on the reconstructed neutrino energy is about 5%-10%. The increase in the detector sensitivity due to the use of additional information from shower events in the searches for a cosmic neutrino flux is also presented.
Keywords: neutrinos; telescopes

A novel trigger based on neural networks for radio neutrino detectors - Anker, Astrid; Paul, Manuel P.; Baldi, Pierre; Barwick, Steven W.; Beise, Jakob; Bernhoff, Hans; Besson, Dave Z.; Bingefors, Nils; Cataldo, Maddalena; Chen, Pisin; Fernández, Daniel García; Gaswint, Geoffrey; et al. (Proceedings of Science, 2022)
The ARIANNA experiment is a proposed Askaryan detector designed to record radio signals induced by neutrino interactions in the Antarctic ice. Because of the low neutrino flux at high energies, the physics output is limited by statistics. Hence, an increase in sensitivity significantly improves the interpretation of data and offers the ability to probe new parameter spaces. The trigger thresholds are limited by the rate of triggering on unavoidable thermal noise fluctuations. The real-time thermal noise rejection algorithm enables the thresholds to be lowered substantially and increases the sensitivity by up to a factor of two compared to the current ARIANNA capabilities. A deep learning discriminator, based on a Convolutional Neural Network (CNN), is implemented to identify and remove a high percentage of thermal events in real time while retaining most of the neutrino signals. We describe a CNN that runs on the current ARIANNA microcomputer and retains 95% of the neutrino signals at a thermal rejection factor of 105. Finally, the experimental verification from lab measurements are conducted.
CRIS-Team Scopus Importer:2023-08-15

ANTARES constrains a blazar origin of two IceCube PeV neutrino events - Adrian-Martinez, S.; Albert, A.; Andre, M.; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Baret, B.; Barrios, J.; Basa, S.; Bertin, V.; Biagi, Simone; Bogazzi, C.; et al. (Astronomy & Astrophysics, 2015)
Results. Both blazars predicted to be the most neutrino-bright in the TANAMI sample (1653-329 and 1714-336) have a signal flux fitted by the likelihood analysis corresponding to approximately one event. This observation is consistent with the blazar-origin hypothesis of the IceCube event IC 14 for a broad range of blazar spectra, although an atmospheric origin cannot be excluded. No ANTARES events are observed from any of the other four blazars, including the three associated with IceCube event IC20. This excludes at a 90% confidence level the possibility that this event was produced by these blazars unless the neutrino spectrum is flatter than -2.4.
Keywords: neutrinos; galaxies: active; quasars: general

ANTARES Neutrino Search for Time and Space Correlations with IceCube High-energy Neutrino Events - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J; Aublin, J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin, V.; et al. (Astrophysical Journal, 2019)
In past years the IceCube Collaboration has reported the observation of astrophysical high-energy neutrino events in several analyses. Despite compelling evidence for the first identification of a neutrino source, TXS 0506+056, the origin of the majority of these events is still unknown. In this paper, we search for a possible transient origin of the IceCube astrophysical events using neutrino events detected by the ANTARES telescope. The arrival time and direction of 6894 track-like and 160 shower-like events detected over 2346 days of livetime are examined to search for coincidences with 54 IceCube high-energy track-like neutrino events, by means of a maximum likelihood method. No significant correlation is observed and upper limits on the one-flavor neutrino fluence from the direction of the IceCube candidates are derived. The nonobservation of time and space correlation within the time window of 0.1 days with the two most energetic IceCube events constrains the spectral index of a possible point-like transient neutrino source to be harder than -2.3 and -2.4 for each event, respectively.
CRIS-Team WoS Importer:2019-07-26

ANTARES Search for Point Sources of Neutrinos Using Astrophysical Catalogs: A Likelihood Analysis - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin, V.; Biagi, Simone; et al. (Astrophysical Journal, 2021)
A search for astrophysical pointlike neutrino sources using the data collected by the ANTARES detector between 2007 January 29 and 2017 December 31 is presented. A likelihood method is used to assess the significance of an excess of muon neutrinos inducing track-like events in correlation with the location of a list of possible sources. Different sets of objects are tested in the analysis: (a) a subsample of the Fermi 3LAC catalog of blazars, (b) a jet-obscured population of active galactic nuclei, (c) a sample of hard X-ray selected radio galaxies, (d) a star-forming galaxy catalog, and (e) a public sample of 56 very-high-energy track events from the IceCube experiment. None of the tested sources shows a significant association with the sample of neutrinos detected by ANTARES. The smallest p-value is obtained for the catalog of radio galaxies with an equal-weights hypothesis, with a pre-trial p-value equivalent to a 2.8 sigma excess, which is equivalent to 1.6 sigma post-trial. In addition, the results of a dedicated analysis for the blazar MG3 J225517+2409 are also reported: this source is found to be the most significant within the Fermi 3LAC sample, with five ANTARES events located less than one degree from the source. This blazar showed evidence of flaring activity in Fermi data, in spacetime coincidence with a high-energy track detected by IceCube. An a posteriori significance of 2.6 sigma for the combination of ANTARES and IceCube data is reported.
CRIS-Team WoS Importer:2021-04-30

ANTARES upper limits on the multi-TeV neutrino emission from the GRBs detected by IACTs - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin, V.; Biagi, S.; et al. (Journal of Cosmology and Astroparticle Physics, 2021)
The first gamma-ray burst detections by Imaging Atmospheric Cherenkov Telescopes have been recently announced: GRB 190114C, detected by MAGIC, GRB 180720B and GRB 190829A, observed by H.E.S.S. A dedicated search for neutrinos in space and time coincidence with the gamma-ray emission observed by IACTs has been performed using ANTARES data. The search covers both the prompt and afterglow phases, yielding no neutrinos in coincidence with the three GRBs studied. Upper limits on the energetics of the neutrino emission are inferred. The resulting upper limits are several orders of magnitude above the observed gamma-ray emission, and they do not allow to constrain the available models.
CRIS-Team Scopus Importer:2021-04-16

A polarized fast radio burst at low Galactic latitude - Petroff, E.; Burke-Spolaor, S.; Keane, E. F.; Mclaughlin, M. A.; Miller, R.; Andreoni, I.; Bailes, Matthew; Barr, E. D.; Bernard, S. R.; Bhandari, S.; Bhat, N. D. R.; Burgay, M.; et al. (Monthly Notices of the Royal Astronomical Society, 2017)
We report on the discovery of a new fast radio burst (FRB), FRB 150215, with the Parkes radio telescope on 2015 February 15. The burst was detected in real time with a dispersion measure (DM) of 1105.6 +/- 0.8 pc cm(-3), a pulse duration of 2.8(-0.5)(+1.2) ms, and a measured peak flux density assuming that the burst was at beam centre of 0.7(-0.1)(+0.2) Jy. The FRB originated at a Galactic longitude and latitude of 24.66 degrees, 5.28 degrees and 25 degrees away from the Galactic Center. The burst was found to be 43 +/- 5 per cent linearly polarized with a rotation measure (RM) in the range -9 < RM < 12 rad m(-2) (95 per cent confidence level), consistent with zero. The burst was followed up with 11 telescopes to search for radio, optical, X-ray, gamma-ray and neutrino emission. Neither transient nor variable emission was found to be associated with the burst and no repeat pulses have been observed in 17.25 h of observing. The sightline to the burst is close to the Galactic plane and the observed physical properties of FRB 150215 demonstrate the existence of sight lines of anomalously low RM for a given electron column density. The Galactic RM foreground may approach a null value due to magnetic field reversals along the line of sight, a decreased total electron column density from the Milky Way, or some combination of these effects. A lower Galactic DM contribution might explain why this burst was detectable whereas previous searches at low latitude have had lower detection rates than those out of the plane.
Keywords: polarization; methods: data analysis; surveys; ISM: structure

Application of deep learning methods to analysis of imaging atmospheric Cherenkov telescopes data - Shilon, Idan; Kraus, Michael; Büchele, Matthias; Egberts, K.; Fischer, T.; Holch, T. L.; Lohse, T.; Schwanke, U.; Steppa, C.; Funk, Stefan (Astroparticle Physics, 2019)
Ground based gamma-ray observations with Imaging Atmospheric Cherenkov Telescopes (IACTs) play a significant role in the discovery of very high energy (E > 100 GeV) gamma-ray emitters. The analysis of IACT data demands a highly efficient background rejection technique, as well as methods to accurately determine the position of its source in the sky and the energy of the recorded gamma-ray. We present results for background rejection and signal direction reconstruction from first studies of a novel data analysis scheme for IACT measurements. The new analysis is based on a set of Convolutional Neural Networks (CNNs) applied to images from the four H.E.S.S. phase-I telescopes. As the H.E.S.S. cameras pixels are arranged in a hexagonal array, we demonstrate two ways to use such image data to train CNNs: by resampling the images to a square grid and by applying modified convolution kernels that conserve the hexagonal grid properties.The networks were trained on sets of Monte-Carlo simulated events and tested on both simulations and measured data from the H.E.S.S. array. A comparison between the CNN analysis to current state-of-the-art algorithms reveals a clear improvement in background rejection performance. When applied to H.E.S.S. observation data, the CNN direction reconstruction performs at a similar level as traditional methods. These results serve as a proof-of-concept for the application of CNNs to the analysis of events recorded by IACTs. (C) 2018 Published by Elsevier B.V.
Keywords: Gamma-ray astronomy; IACT; Analysis technique; Deep learning; Convolutional neural networks; Recurrent neural networks

Application of deep learning methods to analysis of imaging atmospheric Cherenkov telescopes data - Shilon, Idan; Kraus, Michael; Büchele, Matthias; Egberts, K.; Fischer, T.; Holch, T. L.; Lohse, T.; Schwanke, U.; Steppa, C.; Funk, Stefan (Astroparticle Physics, 2019)
Ground based gamma-ray observations with Imaging Atmospheric Cherenkov Telescopes (IACTs) play a significant role in the discovery of very high energy (E > 100 GeV) gamma-ray emitters. The analysis of IACT data demands a highly efficient background rejection technique, as well as methods to accurately determine the position of its source in the sky and the energy of the recorded gamma-ray. We present results for background rejection and signal direction reconstruction from first studies of a novel data analysis scheme for IACT measurements. The new analysis is based on a set of Convolutional Neural Networks (CNNs) applied to images from the four H.E.S.S. phase-I telescopes. As the H.E.S.S. cameras pixels are arranged in a hexagonal array, we demonstrate two ways to use such image data to train CNNs: by resampling the images to a square grid and by applying modified convolution kernels that conserve the hexagonal grid properties.
CRIS-Team WoS Importer:2019-02-21

Application of graph networks to γ/hadron separation in IACT image analyses - Glombitza, Jonas; Joshi, Vikas; Bruno, Benedetta; Funk, Stefan (Proceedings of Science, 2024)
Imaging Atmospheric Cherenkov Telescopes (IACTs) enable precise ground-based observations of the gamma-ray sky by imaging the distribution of Cherenkov light emitted during the development of air showers. Nowadays, many reconstruction algorithms rely on an elliptical high-level parameterization of these IACT images — the Hillas parameterization — and exploit their correlations. To overcome the limitations of the elliptical modeling, besides sophisticated analytical or template-based models, the advent of deep learning allows for reconstruction techniques that showed first promising results. By interpreting the detected images as a collection of triggered sensors that graphs can represent, we propose an algorithm based on graph networks for stereoscopic IACT image analyses. For images cleaned from background noise, this allows for an efficient algorithm design that bypasses the challenge of sparse images that occur in deep learning approaches based on convolutional neural networks. We investigate graph network architectures to two different stereoscopic data sets, simulated for the H.E.S.S. experiment. The algorithm enables an excellent γ/hadron separation with improvements to classical machine learning. Further, we find that the algorithm offers promising prospects for stereoscopic reconstructions also for telescopes featuring different camera geometries.
CRIS-Team Scopus Importer:2025-02-04

A Search for Cosmic Neutrino and Gamma-Ray Emitting Transients in 7.3 yr of ANTARES and Fermi LAT Data - Solares, H. A. Ayala; Cowen, D. F.; Delaunay, J. J.; Fox, D. B.; Keivani, A.; Mostafa, M.; Murase, K.; Turley, C. F.; Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; et al. (Astrophysical Journal, 2019)
We analyze 7.3 yr of ANTARES high-energy neutrino and Fermi Large Area Telescope (LAT) gamma-ray data in search of cosmic neutrino + gamma-ray (nu + gamma) transient sources or source populations. Our analysis has the potential to detect either individual nu + gamma transient sources (durations delta t less than or similar to 1000 s), if they exhibit sufficient gamma-ray or neutrino multiplicity, or a statistical excess of nu + gamma transients of individually lower multiplicities. Individual high gamma-ray multiplicity events could be produced, for example, by a single ANTARES neutrino in coincidence with a LAT-detected gamma-ray burst. Treating ANTARES track and cascade event types separately, we establish detection thresholds by Monte Carlo scrambling of the neutrino data, and determine our analysis sensitivity by signal injection against these scrambled data sets. We find our analysis is sensitive to nu + gamma transient populations responsible for >5% of the observed gamma-coincident neutrinos in the track data at 90% confidence. Applying our analysis to the unscrambled data reveals no individual nu + gamma events of high significance; two ANTARES track + Fermi gamma-ray events are identified that exceed a once per decade false alarm rate threshold (p = 17%). No evidence for subthreshold nu + gamma source populations is found among the track (p = 39%) or cascade (p = 60%) events. Exploring a possible correlation of high-energy neutrino directions with Fermi gamma-ray sky brightness identified in previous work yields no added support for this correlation. While TXS.0506+056, a blazar and variable (nontransient) Fermi gamma-ray source, has recently been identified as the first source of high-energy neutrinos, the challenges in reconciling observations of the Fermi gamma-ray sky, the IceCube high-energy cosmic neutrinos, and ultrahigh-energy cosmic rays using only blazars suggest a significant contribution by other source populations. Searches for transient sources of high-energy neutrinos thus remain interesting, with the potential for either neutrino clustering or multimessenger coincidence searches to lead to discovery of the first nu + gamma transients.
CRIS-Team WoS Importer:2020-01-03

A search for neutrino emission from the Fermi bubbles with the ANTARES telescope - Adrian-Martinez, S.; Albert, A.; Al Samarai, I.; Andre, Michel; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J; Baret, B.; Barrios-Marti, J.; Basa, S.; et al. (European Physical Journal C, 2014)
Analysis of the Fermi-LAT data has revealed two extended structures above and below the Galactic Centre emitting gamma rays with a hard spectrum, the so-called Fermi bubbles. Hadronic models attempting to explain the origin of the Fermi bubbles predict the emission of high-energy neutrinos and gamma rays with similar fluxes. The ANTARES detector, a neutrino telescope located in the Mediterranean Sea, has a good visibility to the Fermi bubble regions. Using data collected from 2008 to 2011 no statistically significant excess of events is observed and therefore upper limits on the neutrino flux in TeV range from the Fermi bubbles are derived for various assumed energy cutoffs of the source.

A search for new supernova remnant shells in the Galactic plane with HESS - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, Michael; Balzer, A.; et al. (Astronomy & Astrophysics, 2018)
A search for new supernova remnants (SNRs) has been conducted using TeV gamma-ray data from the H.E.S.S. Galactic plane survey. As an identification criterion, shell morphologies that are characteristic for known resolved TeV SNRs have been used. Three new SNR candidates were identified in the H.E.S.S. data set with this method. Extensive multiwavelength searches for counterparts were conducted. A radio SNR candidate has been identified to be a counterpart to HESS J1534-571. The TeV source is therefore classified as a SNR. For the other two sources, HESS J1614-518 and HESS J1912 + 101, no identifying counterparts have been found, thus they remain SNR candidates for the time being. TeV-emitting SNRs are key objects in the context of identifying the accelerators of Galactic cosmic rays. The TeV emission of the relativistic particles in the new sources is examined in view of possible leptonic and hadronic emission scenarios, taking the current multiwavelength knowledge into account.
CRIS-Team WoS Importer:2020-01-15

A search for Secluded Dark Matter in the Sun with the ANTARES neutrino telescope - Adrián-Martínez, S.; Albert, A.; André, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Avgitas, T.; Baret, B.; Barrios-Martí, J.; Basa, S.; Bertin, V.; Biagi, S.; et al. (Journal of Cosmology and Astroparticle Physics, 2016)
A search for Secluded Dark Matter annihilation in the Sun using 2007-2012 data of the ANTARES neutrino telescope is presented. Three different cases are considered: a) detection of dimuons that result from the decay of the mediator, or neutrino detection from: b) mediator that decays into a dimuon and, in turn, into neutrinos, and c) mediator that decays directly into neutrinos. As no significant excess over background is observed, constraints are derived on the dark matter mass and the lifetime of the mediator.
Keywords: dark matter detectors; dark matter experiments; neutrino astronomy; neutrino detectors

Assessment of the additional clinical potential of X-ray dark-field imaging for breast cancer in a preclinical setup - Emons, Julius; Fasching, Peter; Wunderle, Marius; Heindl, Felix; Rieger, Jens; Horn, Florian; Pelzer, Georg; Ritter, André; Weber, Thomas; Radicke, Marcus; Polifka, Iris; Wachter, David; et al. (Therapeutic Advances in Medical Oncology, 2020)
Background: Mammography can identify calcifications up to 50–100 μm in size as a surrogate parameter for breast cancer or ductal carcinoma in situ (DCIS). Microcalcifications measuring <50 µm are also associated with breast cancer or DCIS and are frequently not detected on mammography, although they can be detected with dark-field imaging. This study examined whether additional breast examination using X-ray dark-field imaging can increase the detection rate of calcifications. Advances in knowledge: (1) evaluation of additional modality of breast imaging; (2) specific evaluation of breast calcifications. Implications for patient care: the addition of X-ray dark-field imaging to conventional mammography could detect additional calcifications. Methods: Talbot–Lau X-ray phase–contrast imaging and X-ray dark-field imaging were used to acquire images of breast specimens. The radiation dosage with the technique is comparable with conventional mammography. Three X-ray gratings with periods of 5–10 µm between the X-ray tube and the flat-panel detector provide three different images in a single sequence: the conventional attenuation image, differential phase image, and dark-field image. The images were read by radiologists. Radiological findings were marked and examined pathologically. The results were described in a descriptive manner. Results: A total of 81 breast specimens were investigated with the two methods; 199 significant structures were processed pathologically, consisting of 123 benign and 76 malignant lesions (DCIS or invasive breast cancer). X-ray dark-field imaging identified 15 additional histologically confirmed carcinoma lesions that were visible but not declared suspicious on digital mammography alone. Another four malignant lesions that were not visible on mammography were exclusively detected with X-ray dark-field imaging. Conclusions: Adding X-ray dark-field imaging to digital mammography increases the detection rate for breast cancer and DCIS associated lesions with micrometer-sized calcifications. The use of X-ray dark-field imaging may be able to provide more accurate and detailed radiological classification of suspicious breast lesions. Adding X-ray dark-field imaging to mammography may be able to increase the detection rate and improve preoperative planning in deciding between mastectomy or breast-conserving therapy, particularly in patients with invasive lobular breast cancer.
CRIS-Team Scopus Importer:2020-09-25
Keywords: breast cancer; interferometry; mammography; microcalcifications

Capabilities of ARIANNA: Neutrino Pointing Resolution and Implications for Future Ultra-high Energy Neutrino Astronomy - Barwick, Steven W.; Gaswint, Geoffrey; Anker, Astrid; Baldi, Pierre; Beise, Jakob; Bernhoff, Hans; Besson, Dave Z.; Bingefors, Nils; Cataldo, Maddalena; Chen, Pisin; Fernández, Daniel García; Glaser, Christian; et al. (Proceedings of Science, 2022)
A radio-frequency polarization measurement by the ARIANNA surface station was performed using a residual hole from the South Pole Ice Core (SPICEcore) Project. Radio pulses were emitted from a transmitter located down to 1.7 km below the snow surface. After deconvolving the raw signals for the detector response and attenuation from propagation through the ice, the signal pulses show no significant distortion and agree with a reference measurement of the emitter made in an anechoic chamber. The direction to transmitted radio pulse was measured with an angular resolution of 0.37 degree [statistical error]. For polarization, the statistical error of the polarization vector is depth dependent and below 1 degree. In addition, a slowly-varying systematic variation is observed as a function of depth with an rms error of 2.7 degrees. Neither the direction or polarization measurement show a significant offset as a function of depth relative to expectation. We also report on the results of a simulation study of the ARIANNA neutrino direction and energy resolution. The software tool NuRadioMC was used to reconstruct the polarization and viewing angle to determine the neutrino direction. Multiple models of Askaryan radiation and detector sites along with a range of neutrino energies were evaluated. The neutrino space angle resolution was determined to be below 3 degrees, which is comparable to the systematic polarization uncertainty. Therefore it is expected that the polarization resolution, which is the dominant contribution to the neutrino space angle resolution, will be improved in future studies by determining and eliminating systematic effects.
CRIS-Team Scopus Importer:2023-08-15
Keywords: Angle resolution; Implications for futures; Neutrino astronomy; Pointing resolution; Polarization measurements; Radio pulse; Radiofrequencies; Statistical errors; Surface station; Ultrahigh energy neutrinos

Characterisation and testing of CHEC-M-A camera prototype for the small-sized telescopes of the Cherenkov telescope array - Zorn, J.; White, Richard; Watson, J. J.; Armstrong, T. P.; Balzer, A.; Barcelo, M.; Berge, D.; Bose, R.; Brown, A. M.; Bryan, M.; Chadwick, P. M.; Clark, Paul; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2018)
The Compact High Energy Camera (CHEC) is a camera design for the Small-Sized Telescopes (SSTs; 4 m diameter mirror) of the Cherenkov Telescope Array (CTA). The SSTs are focused on very-high-energy gamma-ray detection via atmospheric Cherenkov light detection over a very large area. This implies many individual units and hence cost-effective implementation, as well as shower detection at large impact distance, and hence large field of view (FoV), and efficient image capture in the presence of large time gradients in the shower image detected by the camera. CHEC relies on dual-mirror optics to reduce the plate-scale and make use of 6 x 6 mm(2) pixels, leading to a low-cost (similar to 150 k(sic)), compact (0.5 m x 0.5 m), and light (similar to 45 kg) camera with 2048 pixels providing a camera FoV of similar to 9 degrees. The CHEC electronics are based on custom TARGET (TeV array readout with GSa/s sampling and event trigger) application-specific integrated circuits (ASICs) and field programmable gate arrays (FPGAs) sampling incoming signals at a gigasample per second, with flexible camera-level triggering within a single backplane FPGA. CHEC is designed to observe in the gamma-ray energy range of 1-300 TeV, and at impact distances up to similar to 500 m. To accommodate this and provide full flexibility for later data analysis, full waveforms with 96 samples for all 2048 pixels can be read out at rates up to similar to 900 Hz. The first prototype, CHEC-M, based on mull-anode photomultipliers (MAPMs) as photosensors, was commissioned and characterised in the laboratory and during two measurement campaigns on a telescope structure at the Paris Observatory in Meudon. In this paper, the results and conclusions from the laboratory and on-site testing of CHEC-M are presented. They have provided essential input on the system design and on operational and data analysis procedures for a camera of this type. A second full-camera prototype based on Silicon photomultipliers (SiPMs), addressing the drawbacks of CHEC-M identified during the first prototype phase, has already been built and is currently being commissioned and tested in the laboratory.
CRIS-Team WoS Importer:2020-01-15
Keywords: Full-waveform readout; Cherenkov telescope array; Imaging atmospheric Cherenkov telescopes; Gamma-rays

Characterisation of PMTs for KM3NeT - Herold, Björn; Kalekin, Oleg (31st International Cosmic Ray Conference, ICRC 2009, 2009)
Keywords: Photomultiplier; KM3NeT; Quantum efficiency

Characterisation of the Hamamatsu photomultipliers for the KM3NeT Neutrino Telescope - Aiello, S.; Akrame, S. E.; Ameli, F.; Anassontzis, E. G.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aublin, J.; Avgitas, T.; Baars, M.; et al. (Journal of Instrumentation, 2018)
The Hamamatsu R12199-023-inch photomultiplier tube is the photodetector chosen for the first phase of the KM3NeT neutrino telescope. About 7000 photomultipliers have been characterised for dark count rate, timing spread and spurious pulses. The quantum efficiency, the gain and the peak-to-valley ratio have also been measured for a sub-sample in order to determine parameter values needed as input to numerical simulations of the detector.
Keywords: Cherenkov detectors; Large detector systems for particle and astroparticle physics; Neutrino detectors; Photon detectors for UV; visible and IR photons (vacuum)

Combined search for neutrinos from dark matter self-annihilation in the Galactic Center with ANTARES and IceCube - Albert, A.; Andre, M.; Domi, Alba; Anghinolfi, M.; Ardid, M.; Aubert, J-J; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin,; Biagi, Simone; et al. (Physical Review D, 2020)
We present the results of the first combined dark matter search targeting the Galactic Center using the ANTARES and IceCube neutrino telescopes. For dark matter particles with masses from 50 to 1000 GeV, the sensitivities on the self-annihilation cross section set by ANTARES and IceCube are comparable, making this mass range particularly interesting for a joint analysis. Dark matter self-annihilation through the tau(+)tau(-) , mu(+)mu(-) , b (b) over bar, and W+W- channels is considered for both the Navarro-Frenk-White and Burkert halo profiles. In the combination of 2101.6 days of ANTARES data and 1007 days of IceCube data, no excess over the expected background is observed. Limits on the thermally averaged dark matter annihilation cross section are set. These limits present an improvement of up to a factor of 2 in the studied dark matter mass range with respect to the individual limits published by both collaborations. When considering dark matter particles with a mass of 200 GeV annihilating through the tau(+)tau(-)channel, the value obtained for the limit is 7.44 x 10(-24) cm(3) s(-1 )for the Navarro-Frenk-White halo profile. For the purpose of this joint analysis, the model parameters and the likelihood are unified, providing a benchmark for forthcoming dark matter searches performed by neutrino telescopes.
CRIS-Team WoS Importer:2020-11-13

Constraining the contribution of Gamma-Ray Bursts to the high-energy diffuse neutrino flux with 10 yr of ANTARES data - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin,; Biagi, S.; et al. (Monthly Notices of the Royal Astronomical Society, 2021)
Addressing the origin of the astrophysical neutrino flux observed by IceCube is of paramount importance. Gamma-Ray Bursts (GRBs) are among the few astrophysical sources capable of achieving the required energy to contribute to such neutrino flux through p gamma interactions. In this work, ANTARFS data have been used to search for upward going muon neutrinos in spatial and temporal coincidence with 784 GRBs occurred from 2007 to 2017. For each GRB, the expected neutrino flux has been calculated in the framework of the internal shock model and the impact of the lack of knowledge on the majority of source redshifts and on other intrinsic parameters of the emission mechanism has been quantified. It is found that the model parameters that set the radial distance where shock collisions occur have the largest impact on neutrino flux expectations. In particular, the bulk Lorentz factor of the source ejecta and the minimum variability time-scale are found to contribute significantly to the GRB-neutrino flux uncertainty. For the selected sources, ANTARES data have been analysed by maximizing the discovery probability of the stacking sample through an extended maximum-likelihood strategy. Since no neutrino event passed the quality cuts set by the optimization procedure, 90 per cent confidence level upper limits (with their uncertainty) on the total expected diffuse neutrino flux have been derived, according to the model. The GRB contribution to the observed diffuse astrophysical neutrino flux around 100 TeV is constrained to be less than 10 percent.
CRIS-Team WoS Importer:2021-01-29

Constraining the neutrino emission of gravitationally lensed Flat-Spectrum Radio Quasars with ANTARES data - Adrian-Martinez, S.; Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagii, S.; Bogazzi, C.; et al. (Journal of Cosmology and Astroparticle Physics, 2014)
This paper proposes to exploit gravitational lensing effects to improve the sensitivity of neutrino telescopes to the intrinsic neutrino emission of distant blazar populations. This strategy is illustrated with a search for cosmic neutrinos in the direction of four distant and gravitationally lensed Flat-Spectrum Radio Quasars. The magnification factor is estimated for each system assuming a singular isothermal profile for the lens. Based on data collected from 2007 to 2012 by the ANTARES neutrino telescope, the strongest constraint is obtained from the lensed quasar B0218+357, providing a limit on the total neutrino luminosity of this source of 1.08 x 10(46) erg s(-1) This limit is about one order of magnitude lower than those previously obtained in the ANTARES standard point source searches with non-lensed Flat-Spectrum Radio Quasars.
Keywords: gravitational lensing; neutrino astronomy

Constraining the TeV Halo Population in M31 - Andrés, A.; Albert, A.; Alfaro, R.; Alvarez, C.; Arteaga-Velázquez, J. C.; Avila Rojas, D.; Ayala Solares, H. A.; Babu, R.; Belmont-Moreno, E.; Caballero-Mora, K. S.; Capistrán, T.; Yun-Cárcamo, S.; et al. (Proceedings of Science, 2024)
TeV halos are a new class of γ-ray sources recently observed around some middle-aged pulsars. They are extended γ-ray emission regions with a size bigger than the Pulsar Wind Nebulae but smaller than a Supernova Remnant. Several studies indicate that a TeV halo may be a general signature around a middle-aged pulsar, but this is still an open question. Some recent results suggest TeV halos are significantly contributing to the TeV emission of our Galaxy, and models have been proposed to reproduce the observed population of TeV halos in the Milky Way. In this work, we analyze the emission at TeV energies of the Andromeda galaxy (M31), the closest spiral galaxy to Earth. M31 has also been observed to have a GeV excess similar to the observed in the Galactic Center of our Galaxy. The aim of this work is to model the γ-ray emission at TeV energies in M31 assuming both the Milky Way and M31 share similar properties. Using 6 years of HAWC observations, we compute the flux upper limits in the region of M31 at TeV energies.
CRIS-Team Scopus Importer:2025-02-04

Constraints on Minute-Scale Transient Astrophysical Neutrino Sources - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Al Samarai, I.; Altmann, D.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; et al. (Physical Review Letters, 2019)
High-energy neutrino emission has been predicted for several short-lived astrophysical transients including gamma-ray bursts (GRBs), core-collapse supernovae with choked jets, and neutron star mergers. IceCube's optical and x-ray follow-up program searches for such transient sources by looking for two or more muon neutrino candidates in directional coincidence and arriving within 100 s. The measured rate of neutrino alerts is consistent with the expected rate of chance coincidences of atmospheric background events and no likely electromagnetic counterparts have been identified in Swift follow-up observations. Here, we calculate generic bounds on the neutrino flux of short-lived transient sources. Assuming an E-2.5 neutrino spectrum, we find that the neutrino flux of rare sources, like long gamma-ray bursts, is constrained to < 5% of the detected astrophysical flux and the energy released in neutrinos (100 GeV to 10 PeV) by a median bright GRB-like source is < 10(52.5) erg. For a harder E-2.13 neutrino spectrum up to 30% of the flux could be produced by GRBs and the allowed median source energy is < 10(52) erg. A hypothetical population of transient sources has to be more common than 10(-5) Mpc(-3) yr(-1) (5 x 10(-8) Mpc(-3) yr(-1) for the E-2.13 spectrum) to account for the complete astrophysical neutrino flux.
CRIS-Team WoS Importer:2019-02-21

Constraints on the neutrino emission from the Galactic Ridge with the ANTARES telescope - Adrian-Martinez, S.; Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; et al. (Physics Letters B, 2016)
A highly significant excess of high-energy astrophysical neutrinos has been reported by the IceCube Collaboration. Some features of the energy and declination distributions of IceCube events hint at a North/South asymmetry of the neutrino flux. This could be due to the presence of the bulk of our Galaxy in the Southern hemisphere. The ANTARES neutrino telescope, located in the Mediterranean Sea, has been taking data since 2007. It offers the best sensitivity to muon neutrinos produced by galactic cosmic ray interactions in this region of the sky. In this letter a search for an extended neutrino flux from the Galactic Ridge region is presented. Different models of neutrino production by cosmic ray propagation are tested. No excess of events is observed and upper limits for different neutrino flux spectral indices Γ are set. For Γ=2.4 the 90% confidence level flux upper limit at 100 TeV for one neutrino flavour corresponds to Φ (100 TeV)=2.0⋅10 GeVcmssr. Under this assumption, at most two events of the IceCube cosmic candidates can originate from the Galactic Ridge. A simple power-law extrapolation of the Fermi-LAT flux to account for IceCube High Energy Starting Events is excluded at 90% confidence level.
Keywords: ANTARES; Diffuse muon neutrino flux; Neutrino telescope

Cosmic-ray energy reconstruction using machine learning techniques - Alvarado, A.; Capistrán, T.; Torres, I.; Sacahuí, J. R.; Alfaro, R.; Albert, A.; Alvarez, C.; Andrés, A.; Arteaga-Velázquez, J. C.; Avila Rojas, D.; Ayala Solares, H. A.; Babu, R.; et al. (Proceedings of Science, 2024)
HAWC is a ground-based observatory consisting of 300 water Cherenkov detectors, which observes the extensive air showers induced by cosmic rays from some TeV to a few PeV and, in particular, gamma rays from 300 GeV to more than 100 TeV. One of the crucial features required for a detector of extensive air showers is the estimation of the primary energy of the events to study the spectra of cosmic and gamma rays. For HAWC there are currently two gamma-ray energy estimators: one relies on a ground density parameter, while the other utilizes an artificial neural network. For the cosmic ray energy estimation, there is only one estimator based on maximum likelihood procedures and measurements of the lateral charge distribution of the events. It is worthwhile to update the cosmic-ray energy estimator due to recent improvements of the extensive air shower offline-reconstruction techniques in HAWC. Therefore, we implemented an artificial neural network to reconstruct the primary energy of hadronic events trained with several observables that characterize the air showers. We trained several models and evaluated their performance against the existing cosmic ray energy estimator. In this work, we present the features and performance of these models.
CRIS-Team Scopus Importer:2025-02-04

Deeper HESS observations of Vela Junior (RX J0852.0-4622): Morphology studies and resolved spectroscopy - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, Michael; Balzer, A.; et al. (Astronomy & Astrophysics, 2018)
Aims. We study gamma-ray emission from the shell-type supernova remnant (SNR) RXJ0852.0-4622 to better characterize its spectral properties and its distribution over the SNR.Methods. The analysis of an extended High Energy Spectroscopic System (H.E.S.S.) data set at very high energies (E > 100 GeV) permits detailed studies, as well as spatially resolved spectroscopy, of the morphology and spectrum of the whole RXJ0852.0-4622 region. The H.E.S.S. data are combined with archival data from other wavebands and interpreted in the framework of leptonic and hadronic models. The joint Fermi-LAT-H.E.S.S. spectrum allows the direct determination of the spectral characteristics of the parent particle population in leptonic and hadronic scenarios using only GeV-TeV data.Results. An updated analysis of the H.E.S.S. data shows that the spectrum of the entire SNR connects smoothly to the high-energy spectrum measured by Fermi-LAT. The increased data set makes it possible to demonstrate that the H.E.S.S. spectrum deviates significantly from a power law and is well described by both a curved power law and a power law with an exponential cutoff at an energy of E-cut = (6.7 +/- 1.2(stat) +/- 1.2(syst)) TeV. The joint Fermi-LAT-H.E.S.S. spectrum allows the unambiguous identification of the spectral shape as a power law with an exponential cutoff. No significant evidence is found for a variation of the spectral parameters across the SNR, suggesting similar conditions of particle acceleration across the remnant. A simple modeling using one particle population to model the SNR emission demonstrates that both leptonic and hadronic emission scenarios remain plausible. It is also shown that at least a part of the shell emission is likely due to the presence of a pulsar wind nebula around PSR J0855-4644.
Keywords: astroparticle physics; gamma rays: general; acceleration of particles; cosmic rays; ISM: supernova remnants

Deep-Sea Bioluminescence Blooms after Dense Water Formation at the Ocean Surface - Tamburini, Christian; Canals, Miquel; Houpert, Loic; Lefevre, Dominique; Martini, Verine; D'Ortenzio, Fabrizio; Robert, Anne; Testor, Pierre; Aguilar, Juan Antonio; Al Samarai, Imen; Albert, Arnaud; Andre, Michel; et al. (PLoS ONE, 2013)
The deep ocean is the largest and least known ecosystem on Earth. It hosts numerous pelagic organisms, most of which are able to emit light. Here we present a unique data set consisting of a 2.5-year long record of light emission by deep-sea pelagic organisms, measured from December 2007 to June 2010 at the ANTARES underwater neutrino telescope in the deep NW Mediterranean Sea, jointly with synchronous hydrological records. This is the longest continuous time-series of deep-sea bioluminescence ever recorded. Our record reveals several weeks long, seasonal bioluminescence blooms with light intensity up to two orders of magnitude higher than background values, which correlate to changes in the properties of deep waters. Such changes are triggered by the winter cooling and evaporation experienced by the upper ocean layer in the Gulf of Lion that leads to the formation and subsequent sinking of dense water through a process known as "open-sea convection". It episodically renews the deep water of the study area and conveys fresh organic matter that fuels the deep ecosystems. Luminous bacteria most likely are the main contributors to the observed deep-sea bioluminescence blooms. Our observations demonstrate a consistent and rapid connection between deep open-sea convection and bathypelagic biological activity, as expressed by bioluminescence. In a setting where dense water formation events are likely to decline under global warming scenarios enhancing ocean stratification, in situ observatories become essential as environmental sentinels for the monitoring and understanding of deep-sea ecosystem shifts.

Deep-sea deployment of the KM3NeT neutrino telescope detection units by self-unrolling - Aiello, S.; Domi, Alba; Albert, A.; Garre, S. Alves; Aly, Z.; Ameli, F.; Anassontzis, E.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anguita, M.; Anton, Gisela; et al. (Journal of Instrumentation, 2020)
KM3NeT is a research infrastructure being installed in the deep Mediterranean Sea. It will house a neutrino telescope comprising hundreds of networked moorings - detection units or strings - equipped with optical instrumentation to detect the Cherenkov radiation generated by charged particles from neutrino-induced collisions in its vicinity. In comparison to moorings typically used for oceanography, several key features of the KM3NeT string are different: the instrumentation is contained in transparent and thus unprotected glass spheres; two thin Dyneema (R) ropes are used as strength members; and a thin delicate backbone tube with fibre-optics and copper wires for data and power transmission, respectively, runs along the full length of the mooring. Also, compared to other neutrino telescopes such as ANTARES in the Mediterranean Sea and GVD in Lake Baikal, the KM3NeT strings are more slender to minimise the amount of material used for support of the optical sensors. Moreover, the rate of deploying a large number of strings in a period of a few years is unprecedented. For all these reasons, for the installation of the KM3NeT strings, a custom-made, fast deployment method was designed. Despite the length of several hundreds of metres, the slim design of the string allows it to be compacted into a small, re-usable spherical launching vehicle instead of deploying the mooring weight down from a surface vessel. After being lowered to the seafloor, the string unfurls to its full length with the buoyant launching vehicle rolling along the two ropes. The design of the vehicle, the loading with a string, and its underwater self-unrolling are detailed in this paper.
CRIS-Team WoS Importer:2020-12-18

Deep sea tests of a prototype of the KM3NeT digital optical module - Adrian-Martinez, S.; Ageron, M.; Aharonian, F.; Aiello, S.; Albert, A.; Ameli, F.; Anassontzis, E. G.; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; De Asmundis, R.; et al. (European Physical Journal C, 2014)
The first prototype of a photo-detection unit of the future KM3NeT neutrino telescope has been deployed in the deepwaters of the Mediterranean Sea. This digital optical module has a novel design with a very large photocathode area segmented by the use of 31 three inch photomultiplier tubes. It has been integrated in the ANTARES detector for in-situ testing and validation. This paper reports on the first months of data taking and rate measurements. The analysis results highlight the capabilities of the new module design in terms of background suppression and signal recognition. The directionality of the optical module enables the recognition of multiple Cherenkov photons from the same (40)Kdecay and the localisation of bioluminescent activity in the neighbourhood. The single unit can cleanly identify atmospheric muons and provide sensitivity to the muon arrival directions.

Demonstrating grating-based phase-contrast imaging of laser-driven shock waves - Wegert, Leonard; Schreiner, Stephan; Rauch, Constantin; Albertazzi, Bruno; Bleuel, Paulina; Fröjdh, Eric; Koenig, Michel; Ludwig, Veronika; Martynenko, Artem S.; Meyer, Pascal; Mozzanica, Aldo; Müller, Michael; et al. (Matter and Radiation at Extremes, 2024)
Single-shot X-ray phase-contrast imaging is used to take high-resolution images of laser-driven strong shock waves. Employing a two-grating Talbot interferometer, we successfully acquire standard absorption, differential phase-contrast, and dark-field images of the shocked target. Good agreement is demonstrated between experimental data and the results of two-dimensional radiation hydrodynamics simulations of the laser-plasma interaction. The main sources of image noise are identified through a thorough assessment of the interferometer’s performance. The acquired images demonstrate that grating-based phase-contrast imaging is a powerful diagnostic tool for high-energy-density science. In addition, we make a novel attempt at using the dark-field image as a signal modality of Talbot interferometry to identify the microstructure of a foam target.
CRIS-Team Scopus Importer:2024-07-19
Keywords: Electromagnetic pulse; Gratings; Interferometry; Phase contrast microscopy; X-ray imaging; X-ray phase contrast imaging; Lasers; Shock waves; Hydrodynamics simulations

Dependence of atmospheric muon flux on seawater depth measured with the first KM3NeT detection units: The KM3NeT Collaboration - Ageron, M.; Aiello, S.; Ameli, F.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aublin, J.; Bagatelas, C.; Barbarino, G.; Baret, B.; et al. (European Physical Journal C: Particles and Fields, 2020)
KM3NeT is a research infrastructure located in the Mediterranean Sea, that will consist of two deep-sea Cherenkov neutrino detectors. With one detector (ARCA), the KM3NeT Collaboration aims at identifying and studying TeV–PeV astrophysical neutrino sources. With the other detector (ORCA), the neutrino mass ordering will be determined by studying GeV-scale atmospheric neutrino oscillations. The first KM3NeT detection units were deployed at the Italian and French sites between 2015 and 2017. In this paper, a description of the detector is presented, together with a summary of the procedures used to calibrate the detector in-situ. Finally, the measurement of the atmospheric muon flux between 2232–3386 m seawater depth is obtained.
CRIS-Team Scopus Importer:2020-02-18

Design and performance of the first IceAct demonstrator at the South Pole - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; Argüelles, C.; et al. (Journal of Instrumentation, 2020)
In this paper we describe the first results of IceAct, a compact imaging air-Cherenkov telescope operating in coincidence with the IceCube Neutrino Observatory (IceCube) at the geographic South Pole. An array of IceAct telescopes (referred to as the IceAct project) is under consideration as part of the IceCube-Gen2 extension to IceCube. Surface detectors in general will be a powerful tool in IceCube-Gen2 for distinguishing astrophysical neutrinos from the dominant backgrounds of cosmic-ray induced atmospheric muons and neutrinos: the IceTop array is already in place as part of IceCube, but has a high energy threshold. Although the duty cycle will be lower for the IceAct telescopes than the present IceTop tanks, the IceAct telescopes may prove to be more effective at lowering the detection threshold for air showers. Additionally, small imaging air-Cherenkov telescopes in combination with IceTop, the deep IceCube detector or other future detector systems might improve measurements of the composition of the cosmic ray energy spectrum. In this paper we present measurements of a first 7-pixel imaging air Cherenkov telescope demonstrator, proving the capability of this technology to measure air showers at the South Pole in coincidence with IceTop and the deep IceCube detector.
CRIS-Team Scopus Importer:2020-03-20
Keywords: Cherenkov detectors; Gamma telescopes; Large detector systems for particle and astroparticle physics; Neutrino detectors

Design and sensitivity of the Radio Neutrino Observatory in Greenland (RNO-G) - Aguilar, J. A.; Allison, P.; Beatty, J. J.; Bernhoff, H.; Besson, D.; Bingefors, N.; Botner, O.; Buitink, S.; Carter, K.; Clark, B. A.; Connolly, A.; Dasgupta, P.; et al. (Journal of Instrumentation, 2021)
This article presents the design of the Radio Neutrino Observatory Greenland (RNO-G) and discusses its scientific prospects. Using an array of radio sensors, RNO-G seeks to measure neutrinos above 10 PeV by exploiting the Askaryan effect in neutrino-induced cascades in ice. We discuss the experimental considerations that drive the design of RNO-G, present first measurements of the hardware that is to be deployed and discuss the projected sensitivity of the instrument. RNO-G will be the first production-scale radio detector for in-ice neutrino signals.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Large detector systems for particle and astroparticle physics; Neutrino detectors

Design of a Talbot phase-contrast microscopy imaging system with a digital detector for laser-driven X-ray backlighter sources - Schreiner, Stephan; Rauch, Constantin; Akstaller, Bernhard; Bleuel, Paulina; Fröjdh, Erik; Ludwig, Veronika; Martynenko, Artem S.; Meyer, Pascal; Mozzanica, Aldo; Müller, Maximilian; Neumayer, Paul; Schuster, Max; et al. (Journal of Instrumentation, 2024)
Laser-driven shock waves in matter propagate with multiple kilometers per second and therefore require sources like a laser-driven backlighter, which emit the X-rays within picoseconds, to be able to capture sharp images. The small spatial extent of shocks in low-density materials pose challenges on the imaging setup. In this work, we present a design process for a single-shot X-ray phase-contrast imaging system geared towards these objects, consisting of a two-grating Talbot interferometer and a digital X-ray detector. This imaging system is optimized with respect to the detectable refraction angle of the X-rays induced by an object, which implies a high phase sensitivity. Therefore, an optimization parameter is defined that considers experimental constraints such as the limited number of photons, the required magnification, the size and spectrum of the X-ray source, and the visibility of the moiré fringes. In this way, a large parameter space is sampled and a suitable imaging system is chosen. During a campaign at the PHELIX high-power laser facility a static test sample was imaged which is used to benchmark the optimization process and the imaging system under real conditions. The results show good agreement with the predicted performance, which demonstrates the reliability of the presented design process. Likewise, the process can be adapted to other types of laser experiments or X-ray sources and is not limited to the application presented here.
CRIS-Team Scopus Importer:2024-05-24
Keywords: Inspection with x-rays; Models and simulations; Plasma diagnostics - interferometry; spectroscopy and imaging; X-ray radiography and digital radiography (DR)

Detection of the Temporal Variation of the Sun's Cosmic Ray Shadow with the IceCube Detector - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Altmann, D.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; Arguelles, C.; et al. (Astrophysical Journal, 2019)
We report on the observation of a deficit in the cosmic ray flux from the directions of the Moon and Sun with five years of data taken by the IceCube Neutrino Observatory. Between 2010 May and 2011 May the IceCube detector operated with 79 strings deployed in the glacial ice at the South Pole, and with 86 strings between 2011 May and 2015 May. A binned analysis is used to measure the relative deficit and significance of the cosmic ray shadows. Both the cosmic ray Moon and Sun shadows are detected with high statistical significance (> 10 sigma) for each year. The results for the Moon shadow are consistent with previous analyses and verify the stability of the IceCube detector over time. This work represents the first observation of the Sun shadow with the IceCube detector. We show that the cosmic ray shadow of the Sun varies with time. These results make it possible to study cosmic ray transport near the Sun with future data from IceCube.
CRIS-Team WoS Importer:2019-03-06

Detection of variable VHE gamma-ray emission from the extra-galactic gamma-ray binary LMC P3 - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Armand, C.; Arrieta, M.; Backes, Michael; Balzer, A.; Barnard, M.; Becherini, Y.; et al. (Astronomy & Astrophysics, 2018)
Context. Recently, the high-energy (HE, 0.1-100 GeV) gamma-ray emission from the object LMC P3 in the Large Magellanic Cloud (LMC) has been discovered to be modulated with a 10.3-day period, making it the first extra-galactic gamma-ray binary.
CRIS-Team WoS Importer:2020-01-15
Keywords: Gamma rays: stars; Binaries: general; Stars: massive

Detection of very-high-energy γ -ray emission from the colliding wind binary η Car with H.E.S.S. - Abdalla, H.; Adam, R.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Martins, V. Barbosa; et al. (Astronomy & Astrophysics, 2020)
Aims. Colliding wind binary systems have long been suspected to be high-energy (HE; 100 MeV < E < 100 GeV) γ-ray emitters. η Car is the most prominent member of this object class and is confirmed to emit phase-locked HE γ rays from hundreds of MeV to 100 GeV energies. This work aims to search for and characterise the very-high-energy (VHE; E >100 GeV) γ-ray emission from η Car around the last periastron passage in 2014 with the ground-based High Energy Stereoscopic System (H.E.S.S.). Methods. The region around η Car was observed with H.E.S.S. between orbital phase p = 0.78-1.10, with a closer sampling at p ≈ 0.95 and p ≈ 1.10 (assuming a period of 2023 days). Optimised hardware settings as well as adjustments to the data reduction, reconstruction, and signal selection were needed to suppress and take into account the strong, extended, and inhomogeneous night sky background (NSB) in the η Car field of view. Tailored run-wise Monte-Carlo simulations (RWS) were required to accurately treat the additional noise from NSB photons in the instrument response functions. Results. H.E.S.S. detected VHE γ-ray emission from the direction of η Car shortly before and after the minimum in the X-ray light-curve close to periastron. Using the point spread function provided by RWS, the reconstructed signal is point-like and the spectrum is best described by a power law. The overall flux and spectral index in VHE γ rays agree within statistical and systematic errors before and after periastron. The γ-ray spectrum extends up to at least 400 GeV. This implies a maximum magnetic field in a leptonic scenario in the emission region of 0.5 Gauss. No indication for phase-locked flux variations is detected in the H.E.S.S. data.
CRIS-Team Scopus Importer:2020-04-17
Keywords: Astroparticle physics; Binaries: general; Cosmic rays; Radiation mechanisms: non-thermal; Stars: individual: η Car; Stars: Wolf-Rayet

Detection potential of the KM3NeT detector for high-energy neutrinos from the Fermi bubbles - Adrian-Martinez, S.; Ageron, M.; Aguilar, J. A.; Aharonian, F.; Aiello, S.; Albert, A.; Alexandri, M.; Ameli, F.; Anassontzis, E. G.; Anghinolfi, M.; Anton, Gisela; Anvar, S.; et al. (Astroparticle Physics, 2013)
A recent analysis of the Fermi Large Area Telescope data provided evidence for a high-intensity emission of high-energy gamma rays with a E-2 spectrum from two large areas, spanning 50 above and below the Galactic centre (the "Fermi bubbles"). A hadronic mechanism was proposed for this gamma-ray emission making the Fermi bubbles promising source candidates of high-energy neutrino emission. In this work Monte Carlo simulations regarding the detectability of high-energy neutrinos from the Fermi bubbles with the future multi-km(3) neutrino telescope KM3NeT in the Mediterranean Sea are presented. Under the hypothesis that the gamma-ray emission is completely due to hadronic processes, the results indicate that neutrinos from the bubbles could be discovered in about one year of operation, for a neutrino spectrum with a cutoff at 100 TeV and a detector with about 6 km(3) of instrumented volume. The effect of a possible lower cutoff is also considered. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Neutrino telescope; Fermi Bubbles; KM3NeT

Development of an in-situ calibration device of firn properties for Askaryan neutrino detectors - Anker, Astrid; Baldi, Pierre; Barwick, Steven W.; Beise, Jakob; Bernhoff, Hans; Besson, Dave Z.; Bingefors, Nils; Cataldo, Maddalena; Chen, Pisin; Fernández, Daniel García; Gaswint, Geoffrey; Glaser, Christian; et al. (Proceedings of Science, 2022)
High energy neutrinos (E >1017 eV) are detected cost-efficiently via the Askaryan effect in ice, where a particle cascade induced by the neutrino interaction produces coherent radio emission that can be picked up by antennas installed below the surface. A good knowledge of the near surface ice (aka firn) properties is required to reconstruct the neutrino properties. In particular, a continuous monitoring of the snow accumulation (which changes the depth of the antennas) and the index-of-refraction profile are crucial for an accurate determination of the neutrino’s direction and energy. We present an in-situ calibration system that extends the radio detector station with a radio emitter to continuously monitor the firn properties by measuring time differences of direct and reflected (off the surface) signals (D’n’R). We optimized the station layout in a simulation study and quantified the achievable precision. We present 14 months of data of the ARIANNA detector on the Ross Ice Shelf, Antarctica, where a prototype of this calibration system was successfully used to monitor the snow accumulation with unprecedented precision of 1 mm. We explore and test several algorithms to extract the D’n’R time difference from noisy data (including deep learning). This constitutes an in-situ test of the neutrino vertex distance reconstruction using the D’n’R technique which is needed to determine the neutrino energy.
CRIS-Team Scopus Importer:2023-08-15

Electromagnetic pulse protective shielding for digital x-ray detectors - Schreiner, Stephan; Rauch, Constantin; Akstaller, Bernhard; Bleuel, Paulina; Fröjdh, Eric; Martynenko, Artem S.; Mozzanica, Aldo; Neumayer, Paul; Wegert, Leonard; Zielbauer, Bernhard; Zink, Adrian; Anton, Gisela; et al. (Review of Scientific Instruments, 2023)
Laser-driven x-ray backlighting can be used to image fast dynamic processes like the propagation of laser-driven shock waves in matter. We demonstrate and evaluate the feasibility of operating the JUNGFRAU detector designed by PSI, a direct detecting x-ray detector, in environments with extreme electromagnetic pulses. The electromagnetic pulse-protective housing is specifically designed for this detector and optimized for pump-probe experiments at the Petawatt High-Energy Laser for Heavy Ion EXperiments (PHELIX) facility at the GSI Helmholtzzentrum für Schwerionenforschung GmbH. The beryllium x-ray entrance window of the protective housing has a high x-ray transmission of 94% at 8 keV. Measurements have shown that the housing simultaneously provides a relative damping of the electromagnetic field on average higher than 1000 in the frequency range of 100 MHz to 5 GHz. The results demonstrate the feasibility of operating digital detectors in experiments where strong electromagnetic pulses are present.
CRIS-Team Scopus Importer:2023-08-11

Erratum: Publisher's Note: "Electromagnetic pulse protective shielding for digital x-ray detectors" [Rev. Sci. Instrum. 94, 075106 (2023) (The Review of scientific instruments (2023) 94 7 PII: 089902) - Schreiner, Stephan; Rauch, Constantin; Akstaller, Bernhard; Bleuel, Paulina; Frojdh, Eric; Martynenko, Artem S.; Mozzanica, Aldo; Neumayer, Paul; Wegert, Leonard; Zielbauer, Bernhard; Zink, Adrian; Anton, Gisela; et al. (Review of Scientific Instruments, 2023)
CRIS-Team Scopus Importer:2023-12-22

Erratum to: Search for annihilating dark matter in the Sun with 3 years of IceCube data: IceCube Collaboration (The European Physical Journal C, (2017), 77, 3, (146), 10.1140/epjc/s10052-017-4689-9) - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Altmann, D.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; Archinger, M.; et al. (European Physical Journal C: Particles and Fields, 2019)
In the analysis published in 1, constraints on the number of signal events can be interpreted as constraints on the volumetric neutrino to muon conversion rate.
CRIS-Team Scopus Importer:2019-05-02

Erratum to: Search for non-relativistic magnetic monopoles with IceCube (The European Physical Journal C, (2014), 74, 7, (2938), 10.1140/epjc/s10052-014-2938-8) - Aartsen, M. G.; Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, Markus; Altmann, D.; Arguelles, C.; Arlen, T. C.; Auffenberg, J.; Bai, X.; Baker, M.; et al. (European Physical Journal C: Particles and Fields, 2019)
In the analyses, published in Ref. [1], the exclusion limits are calculated in dependence of the mean free path of the magnetic monopole - nucleon catalysis interaction.
CRIS-Team Scopus Importer:2019-05-02

Evaluation of the Weighted Mean X-ray Energy for an Imaging System Via Propagation-Based Phase-Contrast Imaging - Seifert, Maria; Weule, Mareike; Cipiccia, Silvia; Flenner, Silja; Hagemann, Johannes; Ludwig, Veronika; Michel, Thilo; Neumayer, Paul; Schuster, Max; Wolf, Andreas; Anton, Gisela; Funk, Stefan; et al. (Journal of Imaging, 2020)
For imaging events of extremely short duration, like shock waves or explosions, it is necessary to be able to image the object with a single-shot exposure. A suitable setup is given by a laser-induced X-ray source such as the one that can be found at GSI (Helmholtzzentrum fur Schwerionenforschung GmbH) in Darmstadt (Society for Heavy Ion Research), Germany. There, it is possible to direct a pulse from the high-energy laser Petawatt High Energy Laser for Heavy Ion eXperiments (PHELIX) on a tungsten wire to generate a picosecond polychromatic X-ray pulse, called backlighter. For grating-based single-shot phase-contrast imaging of shock waves or exploding wires, it is important to know the weighted mean energy of the X-ray spectrum for choosing a suitable setup. In propagation-based phase-contrast imaging the knowledge of the weighted mean energy is necessary to be able to reconstruct quantitative phase images of unknown objects. Hence, we developed a method to evaluate the weighted mean energy of the X-ray backlighter spectrum using propagation-based phase-contrast images. In a first step wave-field simulations are performed to verify the results. Furthermore, our evaluation is cross-checked with monochromatic synchrotron measurements with known energy at Diamond Light Source (DLS, Didcot, UK) for proof of concepts.
CRIS-Team WoS Importer:2020-08-28

Event reconstruction for KM3NeT/ORCA using convolutional neural networks - Aiello, S.; Albert, A.; Garre, S. Alves; Aly, Z.; Ameli, F.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anguita, M.; Anton, Gisela; Ardid, M.; Aublin, J.; et al. (Journal of Instrumentation, 2020)
The KM3NeT research infrastructure is currently under construction at two locations in the Mediterranean Sea. The KM3NeT/ORCA water-Cherenkov neutrino detector off the French coast will instrument several megatons of seawater with photosensors. Its main objective is the determination of the neutrino mass ordering. This work aims at demonstrating the general applicability of deep convolutional neural networks to neutrino telescopes, using simulated datasets for the KM3NeT/ORCA detector as an example. To this end, the networks are employed to achieve reconstruction and classification tasks that constitute an alternative to the analysis pipeline presented for KM3NeT/ORCA in the KM3NeT Letter of Intent. They are used to infer event reconstruction estimates for the energy, the direction, and the interaction point of incident neutrinos. The spatial distribution of Cherenkov light generated by charged particles induced in neutrino interactions is classified as shower- or track-like, and the main background processes associated with the detection of atmospheric neutrinos are recognized. Performance comparisons to machine-learning classification and maximum-likelihood reconstruction algorithms previously developed for KM3NeT/ORCA are provided. It is shown that this application of deep convolutional neural networks to simulated datasets for a large-volume neutrino telescope yields competitive reconstruction results and performance improvements with respect to classical approaches.
CRIS-Team WoS Importer:2020-10-30

Event reconstruction in a liquid xenon Time Projection Chamber with an optically-open field cage - Stiegler, T.; Sangiorgio, S.; Brodsky, J. P.; Heffner, M.; Kharusi, S. Al; Anton, Gisela; Arnquist, I. J.; Badhrees, I.; Barbeau, P. S.; Beck, D.; Belov, V.; Bhatta, T.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2021)
nEXO is a proposed tonne-scale neutrinoless double beta decay (0νββ) experiment using liquid 136Xe (LXe) in a Time Projection Chamber (TPC) to read out ionization and scintillation signals. Between the field cage and the LXe vessel, a layer of LXe (“skin” LXe) is present, where no ionization signal is collected. Only scintillation photons are detected, owing to the lack of optical barrier around the field cage. In this work, we show that the light originating in the skin LXe region can be used to improve background discrimination by 5% over previous published estimates. This improvement comes from two elements. First, a fraction of the γ-ray background is removed by identifying light from interactions with an energy deposition in the skin LXe. Second, background from 222Rn dissolved in the skin LXe can be efficiently rejected by tagging the α decay in the 214Bi-214Po chain in the skin LXe.
CRIS-Team Scopus Importer:2021-04-02
Keywords: Liquid xenon detectors; Monte Carlo methods; Neutrinoless double beta decay; Time-projection chambers

Evidence of 100 TeV gamma-ray emission from HESS J1702-420: A new PeVatron candidate - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, Michael; Baghmanyan,; Martins, V. Barbosa; Barnacka, A.; et al. (Astronomy & Astrophysics, 2021)
Aims. The identification of PeVatrons, hadronic particle accelerators reaching the knee of the cosmic ray spectrum (few x 10(15) eV), is crucial to understand the origin of cosmic rays in the Galaxy. We provide an update on the unidentified source HESS J1702-420, a promising PeVatron candidate.
CRIS-Team WoS Importer:2021-10-15
Keywords: Cosmic rays; Gamma rays: general; Methods: data analysis; Radiation mechanisms: non-thermal

Expansion cone for the 3-inch PMTs of the KM3NeT optical modules - Adrian-Martinez, S.; Ageron, M.; Aguilar, J. A.; Aharonian, F.; Aiello, S.; Albert, A.; Alexandri, M.; Ameli, F.; Anassontzis, E. G.; Anghinolfi, M.; Anton, Gisela; Anvar, S.; et al. (Journal of Instrumentation, 2013)
Detection of high-energy neutrinos from distant astrophysical sources will open a new window on the Universe. The detection principle exploits the measurement of Cherenkov light emitted by charged particles resulting from neutrino interactions in the matter containing the telescope. A novel multi-PMT digital optical module (DOM) was developed to contain 31 3-inch photomultiplier tubes (PMTs). In order to maximize the detector sensitivity, each PMT will be surrounded by an expansion cone which collects photons that would otherwise miss the photocathode. Results for various angles of incidence with respect to the PMT surface indicate an increase in collection efficiency by 30% on average for angles up to 45 degrees with respect to the perpendicular. Ray-tracing calculations could reproduce the measurements, allowing to estimate an increase in the overall photocathode sensitivity, integrated over all angles of incidence, by 27% (for a single PMT). Prototype DOMs, being built by the KM3NeT consortium, will be equipped with these expansion cones.
Keywords: Optical detector readout concepts; Instrument optimisation; Cherenkov detectors; Large detector systems for particle and astroparticle physics

Final characterisation and design of the Gamma-ray Cherenkov Telescope (GCT) for the Cherenkov Telescope Array - Le Blanc, O.; Fasola, G.; Huet, J. M.; White, Richard; Dmytriiev, A.; Sol, H.; Zech, A.; Abchiche, A.; Amans, J. P.; Armstrong, T. P.; Barcelo, M.; Berge, D.; et al. (GROUND-BASED AND AIRBORNE TELESCOPES VII, 2018)
CRIS-Team WoS Importer:2020-01-15

First all-flavor neutrino pointlike source search with the ANTARES neutrino telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin, V.; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2017)
A search for cosmic neutrino sources using the data collected with the ANTARES neutrino telescope between early 2007 and the end of 2015 is performed. For the first time, all neutrino interactions-charged and neutral-current interactions of all flavors-are considered in a search for point-like sources with the ANTARES detector. In previous analyses, only muon neutrino charged-current interactions were used. This is achieved by using a novel reconstruction algorithm for shower-like events in addition to the standard muon track reconstruction. The shower channel contributes about 23% of all signal events for an E-2 energy spectrum. No significant excess over background is found. The most signal-like cluster of events is located at (alpha, delta) = (343.8 degrees, 23.5 degrees) with a significance of 1.9 sigma. The neutrino flux sensitivity of the search is about E(2)d Phi/dE = 6 x 10(-9) GeV cm(-2) s(-1) for declinations from -90 degrees up to -42 degrees, and below 10(-8) GeV cm(-2) s(-1) for declinations up to 5 degrees. The directions of 106 source candidates and 13 muon track events from the IceCube high-energy sample events are investigated for a possible neutrino signal and upper limits on the signal flux are determined.

First results on dark matter annihilation in the Sun using the ANTARES neutrino telescope - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anton, L.; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J.; Baret, B.; et al. (Journal of Cosmology and Astroparticle Physics, 2013)
A search for high-energy neutrinos coming from the direction of the Sun has been performed using the data recorded by the ANTARES neutrino telescope during 2007 and 2008. The neutrino selection criteria have been chosen to maximize the selection of possible signals produced by the self-annihilation of weakly interacting massive particles accumulated in the centre of the Sun with respect to the atmospheric background. After data unblinding, the number of neutrinos observed towards the Sun was found to be compatible with background expectations. The 90% CL upper limits in terms of spin-dependent and spin-independent WIMP-proton cross-sections are derived and compared to predictions of two supersymmetric models, CMSSM and MSSM-7. The ANTARES limits are comparable with those obtained by other neutrino observatories and are more stringent than those obtained by direct search experiments for the spin-dependent WIMP-proton cross-section in the case of hard self-annihilation channels (W+W-, tau(+)tau(-)).
Keywords: neutrino experiments; dark matter detectors; supersymmetry and cosmology; particle physics - cosmology connection

First search for neutrinos in correlation with gamma-ray bursts with the ANTARES neutrino telescope - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Aubert, J-J.; Baret, B.; et al. (Journal of Cosmology and Astroparticle Physics, 2013)
A search for neutrino-induced muons in correlation with a selection of 40 gamma-ray bursts that occurred in 2007 has been performed with the ANTARES neutrino telescope. During that period, the detector consisted of 5 detection lines. The ANTARES neutrino telescope is sensitive to TeV-PeV neutrinos that are predicted from gamma-ray bursts. No events were found in correlation with the prompt photon emission of the gamma-ray bursts and upper limits have been placed on the flux and fluence of neutrinos for different models.
Keywords: neutrino experiments; neutrino astronomy; gamma ray bursts theory

FIRST SEARCH FOR POINT SOURCES OF HIGH-ENERGY COSMIC NEUTRINOS WITH THE ANTARES NEUTRINO TELESCOPE - Adrian-Martinez, S.; Aguilar, J. A.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Aubert, J. -J.; et al. (Astrophysical Journal Letters, 2011)
Results are presented of a search for cosmic sources of high-energy neutrinos with the ANTARES neutrino telescope. The data were collected during 2007 and 2008 using detector configurations containing between 5 and 12 detection lines. The integrated live time of the analyzed data is 304 days. Muon tracks are reconstructed using a likelihood-based algorithm. Studies of the detector timing indicate a median angular resolution of 0.5 +/- 0.1 deg. The neutrino flux sensitivity is 7.5 x 10(-8)(E(v)/GeV)(-2) GeV(-1) s(-1) cm(-2) for the part of the sky that is always visible (delta < -48 deg), which is better than limits obtained by previous experiments. No cosmic neutrino sources have been observed.
Keywords: astroparticle physics; cosmic rays; neutrinos

FlashCam: A fully digital camera for the Cherenkov telescope array medium-sized telescopes - Pühlhofer, G.; Barcelo, M.; Bauer, C.; Bi, B.; Catalano, Jacqueline; Diebold, S.; Eschbach, Stefan; Florin, D.; Foehr, C.; Funk, Stefan; Gadola, A.; Garrecht, F.; et al. (Proceedings of SPIE - The International Society for Optical Engineering, 2019)
FlashCam is an innovative camera designed for the focal plane instrumentation of Cherenkov telescopes. The concept of the FlashCam trigger and readout system is based on the continuous digitization and digital processing of the photo detector signals on FPGAs, and on a high performance, Ethernet-based front-end readout. Because of the modular design, the electronics that have been developed can serve either photomultiplier tubes or silicon-based photon detectors. In the framework of the CTA (Cherenkov telescope array) project, the FlashCam team has developed a PMT-based camera that is suitable for the medium-sized telescopes. With over 100 Cherenkov telescopes, the CTA observatory will run the most sensitive ground-based telescope systems for TeV gamma-ray astronomy when the two arrays in the Northern and Southern Hemisphere (with three different telescope sizes) will go into operation in the upcoming years.
CRIS-Team Scopus Importer:2019-12-31
Keywords: Cherenkov Telescope Array; electronics; gamma-rays; Imaging Atmospheric Cherenkov Telescopes

Gamma-ray observations of MAXI J1820+070 during the 2018 outburst - Abe, H.; Abe, S.; Acciari, V. A.; Aniello, T.; Ansoldi, S.; Antonelli, L. A.; Engels, A. Arbet; Arcaro, C.; Artero, M.; Asano, K.; Baack, D.; Babic, A.; et al. (Monthly Notices of the Royal Astronomical Society, 2022)
MAXIJ1820+070 is a low-mass X-ray binary with a black hole (BH) as a compact object. This binary underwent an exceptionally bright X-ray outburst from 2018 March to October, showing evidence of a non-thermal particle population through its radio emission during this whole period. The combined results of 59.5 h of observations of the MAXI J1820+070 outburst with the H.E.S.S., MAGIC and VERITAS experiments at energies above 200 GeV are presented, together with Fermi-LAT data between 0.1 and 500 GeV, and multiwavelength observations from radio to X-rays. Gamma-ray emission is not detected from MAXI J1820+070, but the obtained upper limits and the multiwavelength data allow us to put meaningful constraints on the source properties under reasonable assumptions regarding the non-thermal particle population and the jet synchrotron spectrum. In particular, it is possible to show that, if a high-energy (HE) gamma-ray emitting region is present during the hard state of the source, its predicted flux should be at most a factor of 20 below the obtained Fermi-LAT upper limits, and closer to them for magnetic fields significantly below equipartition. During the state transitions, under the plausible assumption that electrons are accelerated up to similar to 500 GeV, the multiwavelength data and the gamma-ray upper limits lead consistently to the conclusion that a potential HE and very-HE gamma-ray emitting region should be located at a distance from the BH ranging between 10(11) and 10(13) cm. Similar outbursts from low-mass X-ray binaries might be detectable in the near future with upcoming instruments such as CTA.
CRIS-Team WoS Importer:2023-01-27

gSeaGen: The KM3NeT GENIE-based code for neutrino telescopes - Aiello, S.; Kalekin, Oleg; Domi, Alba; Albert, A.; Garre, S. Alves; Aly, Z.; Ameli, F.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anguita, M.; Anton, G.; et al. (Computer Physics Communications, 2020)
The gSeaGen code is a GENIE-based application developed to efficiently generate high statistics samples of events, induced by neutrino interactions, detectable in a neutrino telescope. The gSeaGen code is able to generate events induced by all neutrino flavours, considering topological differences between track-type and shower-like events. Neutrino interactions are simulated taking into account the density and the composition of the media surrounding the detector. The main features of gSeaGen are presented together with some examples of its application within the KM3NeT project. Program summary: Program Title: gSeaGen CPC Library link to program files: http://dx.doi.org/10.17632/ymgxvy2br4.1 Licensing provisions: GPLv3 Programming language: C++ External routines/libraries: GENIE [1] and its external dependencies. Linkable to MUSIC [2] and PROPOSAL [3]. Nature of problem: Development of a code to generate detectable events in neutrino telescopes, using modern and maintained neutrino interaction simulation libraries which include the state-of-the-art physics models. The default application is the simulation of neutrino interactions within KM3NeT [4]. Solution method: Neutrino interactions are simulated using GENIE, a modern framework for Monte Carlo event generators. The GENIE framework, used by nearly all modern neutrino experiments, is considered as a reference code within the neutrino community. Additional comments including restrictions and unusual features: The code was tested with GENIE version 2.12.10 and it is linkable with release series 3. Presently valid up to 5 TeV. This limitation is not intrinsic to the code but due to the present GENIE valid energy range. References: [1] C. Andreopoulos at al., Nucl. Instrum. Meth. A614 (2010) 87. [2] P. Antonioli et al., Astropart. Phys. 7 (1997) 357. [3] J. H. Koehne et al., Comput. Phys. Commun. 184 (2013) 2070. [4] S. Adrián-Martínez et al., J. Phys. G: Nucl. Part. Phys. 43 (2016) 084001.
CRIS-Team Scopus Importer:2020-07-17
Keywords: Astroparticle physics; GENIE; High energy neutrinos; KM3NeT; Monte Carlo event generator; Neutrino oscillations; Neutrino telescopes

HESS and Suzaku observations of the Vela X pulsar wind nebula - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Backes, M.; Barnard, M.; Becherini, Y.; Berge, D.; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2019)
Context. Pulsar wind nebulae (PWNe) represent the most prominent population of Galactic very-high-energy gamma-ray sources and are thought to be an efficient source of leptonic cosmic rays. Vela X is a nearby middle-aged PWN, which shows bright X-ray and TeV gamma-ray emission towards an elongated structure called the cocoon.
CRIS-Team WoS Importer:2019-07-23
Keywords: Gamma rays: stars; Pulsars: individual: PSR B0833-45; Radiation mechanisms: non-thermal; Stars: winds; outflows; Acceleration of particles

HESS detection of very high-energy gamma-ray emission from the quasar PKS 0736+017 - Abdalla, H.; Adam, R.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Ashkar, H.; Backes, M.; Martins, V. Barbosa; Barnard, M.; et al. (Astronomy & Astrophysics, 2020)
Context. Flat-spectrum radio-quasars (FSRQs) are rarely detected at very high energies (E& x2004;>=& x2004;100 GeV) due to their low-frequency-peaked spectral energy distributions. At present, only six FSRQs are known to emit very high-energy (VHE) photons, representing only 7% of the VHE extragalactic catalog, which is largely dominated by high-frequency-peaked BL Lacertae objects. Aims. Following the detection of MeV-GeV gamma-ray flaring activity from the FSRQ PKS 0736+017 (z& x2004;=& x2004;0.189) with Fermi-LAT, the H.E.S.S. array of Cherenkov telescopes triggered target-of-opportunity (ToO) observations on February 18, 2015, with the goal of studying the gamma-ray emission in the VHE band. Methods. H.E.S.S. ToO observations were carried out during the nights of February 18, 19, 21, and 24, 2015. Together with Fermi-LAT, the multi-wavelength coverage of the flare includes Swift observations in soft X-ray and optical-UV bands, and optical monitoring (photometry and spectro-polarimetry) by the Steward Observatory, and the ATOM, the KAIT, and the ASAS-SN telescopes. Results. VHE emission from PKS 0736+017 was detected with H.E.S.S. only during the night of February 19, 2015. Fermi-LAT data indicate the presence of a gamma-ray flare, peaking at the time of the H.E.S.S. detection, with a flux doubling timescale of around six hours. The gamma-ray flare was accompanied by at least a 1 mag brightening of the non-thermal optical continuum. No simultaneous observations at longer wavelengths are available for the night of the H.E.S.S. detection. The gamma-ray observations with H.E.S.S. and Fermi-LAT are used to put constraints on the location of the gamma-ray emitting region during the flare: it is constrained to be just outside the radius of the broad-line region r(BLR) with a bulk Lorentz factor Gamma& x2004;similar or equal to& x2004;20, or at the level of the radius of the dusty torus r(torus) with Gamma& x2004;similar or equal to& x2004;60. Conclusions. PKS 0736+017 is the seventh FSRQ known to emit VHE photons, and at z& x2004;=& x2004;0.189 is the nearest so far. The location of the gamma-ray emitting region during the flare can be tightly constrained thanks to opacity, variability, and collimation arguments.
CRIS-Team WoS Importer:2020-02-18
Keywords: Astroparticle physics; Gamma rays: general; Quasars: individual: PKS 0736+017; Relativistic processes

HESS discovery of very high energy gamma-ray emission from PKS 0625-354 - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguner, E. O.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; et al. (Monthly Notices of the Royal Astronomical Society, 2018)
PKS 0625-354 (z = 0.055) was observed with the four High Energy Stereoscopic System (H.E.S.S.) telescopes in 2012 during 5.5 h. The source was detected above an energy threshold of 200 GeV at a significance level of 6.1 sigma. No significant variability is found in these observations. The source is well described with a power-law spectrum with photon index Gamma = 2.84 +/- 0.50(stat) +/- 0.10(syst) and normalization (at E-0 = 1.0 TeV) N-0(E-0)=(0.58 +/- 0.22(stat) +/- 0.12(syst)) x 10(-12) TeV-1 cm(-2) s(-1). Multiwavelength data collected with Fermi-LAT, Swift-XRT, Swift-UVOT, ATOM and WISE are also analysed. Significant variability is observed only in the Fermi-LAT gamma-ray and Swift-XRT X-ray energy bands. Having a good multiwavelength coverage from radio to very high energy, we performed a broad-band modelling from two types of emission scenarios. The results from a one zone lepto-hadronic and a multizone leptonic models are compared and discussed. On the grounds of energetics, our analysis favours a leptonic multizone model. Models associated to the X-ray variability constraint support previous results, suggesting a BL Lac nature of PKS 0625-354 with, however, a large-scale jet structure typical of a radio galaxy.
Keywords: radiation mechanisms: non-thermal; galaxies: active; galaxies: individual: PKS 0625-354; galaxies: jets; gamma-rays: galaxies

HESS Follow-up Observations of Binary Black Hole Coalescence Events during the Second and Third Gravitational-wave Observing Runs of Advanced LIGO and Advanced Virgo - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Ashkar, H.; Backes, M.; Baghmanyan,; Martins, V. Barbosa; Batzofin, R.; Becherini, Y.; Berge, D.; Bernlohr, K.; et al. (Astrophysical Journal, 2021)
We report on the observations of four well-localized binary black hole (BBH) mergers by the High Energy Stereoscopic System (H.E.S.S.) during the second and third observing runs of Advanced LIGO and Advanced Virgo, O2 and O3. H.E.S.S. can observe 20 deg(2) of the sky at a time and follows up gravitational-wave (GW) events by "tiling" localization regions to maximize the covered localization probability. During O2 and O3, H.E.S.S. observed large portions of the localization regions, between 35% and 75%, for four BBH mergers (GW170814, GW190512_180714, GW190728_064510, and S200224ca). For these four GW events, we find no significant signal from a pointlike source in any of the observations, and we set upper limits on the very high energy (>100 GeV) gamma-ray emission. The 1-10 TeV isotropic luminosity of these GW events is below 10(45) erg s(-1) at the times of the H.E.S.S. observations, around the level of the low-luminosity GRB 190829A. Assuming no changes are made to how follow-up observations are conducted, H.E.S.S. can expect to observe over 60 GW events per year in the fourth GW observing run, O4, of which eight would be observable with minimal latency.
CRIS-Team WoS Importer:2021-12-24

HESS J1809-193: A halo of escaped electrons around a pulsar wind nebula? - Aharonian, F.; Ait Benkhali, F.; Aschersleben, J.; Ashkar, H.; Backes, M.; Barbosa Martins, V.; Batzofin, R.; Becherini, Y.; Berge, D.; Boettcher, M.; Boisson, C.; Bolmont, J.; et al. (Astronomy & Astrophysics, 2023)
Context. HESS J1809-193 is an unassociated very-high-energy gamma-ray source located on the Galactic plane. While it has been connected to the nebula of the energetic pulsar PSR J1809-1917, supernova remnants and molecular clouds present in the vicinity also constitute possible associations. Recently, the detection of gamma-ray emission up to energies of similar to 100 TeV with the HAWC observatory has led to renewed interest in HESS J1809-193.Aims. We aim to understand the origin of the gamma-ray emission of HESS J1809-193.Methods. We analysed 93.2 h of data taken on HESS J1809-193 above 0.27 TeV with the High Energy Stereoscopic System (H.E.S.S.), using a multi-component, three-dimensional likelihood analysis. In addition, we provide a new analysis of 12.5 yr of Fermi-LAT data above 1 GeV within the region of HESS J1809-193. The obtained results are interpreted in a time-dependent modelling framework.Results. For the first time, we were able to resolve the emission detected with H.E.S.S. into two components: an extended component (modelled as an elongated Gaussian with a 1-sigma semi-major and semi-minor axis of similar to 0.62 degrees and similar to 0.35 degrees, respectively) that exhibits a spectral cutoff at similar to 13 TeV, and a compact component (modelled as a symmetric Gaussian with a 1-sigma radius of similar to 0.1 degrees) that is located close to PSR J1809-1917 and shows no clear spectral cutoff. The Fermi-LAT analysis also revealed extended gamma-ray emission, on scales similar to that of the extended H.E.S.S. component.Conclusions. Our modelling indicates that based on its spectrum and spatial extent, the extended H.E.S.S. component is likely caused by inverse Compton emission from old electrons that form a halo around the pulsar wind nebula. The compact component could be connected to either the pulsar wind nebula or the supernova remnant and molecular clouds. Due to its comparatively steep spectrum, modelling the Fermi-LAT emission together with the H.E.S.S. components is not straightforward.
CRIS-Team WoS Importer:2023-05-05

HESS observations of RX J1713.7-3946 with improved angular and spectral resolution: Evidence for gamma-ray emission extending beyond the X-ray emitting shell - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, E. O.; Arrieta, M.; Aubert, P.; Backes, Michael; Balzer, A.; Barnard, Monica; et al. (Astronomy & Astrophysics, 2018)
Supernova remnants exhibit shock fronts (shells) that can accelerate charged particles up to very high energies. In the past decade, measurements of a handful of shell-type supernova remnants in very high-energy gamma rays have provided unique insights into the acceleration process. Among those objects, RX J1713.7-3946 (also known as G347.3-0.5) has the largest surface brightness, allowing us in the past to perform the most comprehensive study of morphology and spatially resolved spectra of any such very high-energy gamma-ray source. Here we present extensive new H.E.S.S. measurements of RX J1713.7-3946, almost doubling the observation time compared to our previous publication. Combined with new improved analysis tools, the previous sensitivity is more than doubled. The H.E.S.S. angular resolution of 0.048 degrees (0.036 degrees above 2 TeV) is unprecedented in gamma-ray astronomy and probes physical scales of 0.8 (0.6) parsec at the remnant's location. The new H. E. S. S. image of RX J1713.7-3946 allows us to reveal clear morphological di ff erences between X-rays and gamma rays. In particular, for the outer edge of the brightest shell region, we find the first ever indication for particles in the process of leaving the acceleration shock region. By studying the broadband energy spectrum, we furthermore extract properties of the parent particle populations, providing new input to the discussion of the leptonic or hadronic nature of the gamma-ray emission mechanism.
CRIS-Team WoS Importer:2020-01-15
Keywords: ISM: Supernova remnants; cosmic rays; gamma rays: General; Acceleration of particles; astroparticle physic

HESS observations of the flaring gravitationally lensed galaxy PKS 1830-211 - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, M.; Barnard, M.; Becherini, Y.; Tjus, J. Becker; et al. (Monthly Notices of the Royal Astronomical Society, 2019)
PKS 1830-211 is a known macrolensed quasar located at a redshift of z = 2.5. Its highenergy gamma-ray emission has been detected with the Fermi-Large Area Telescope (LAT) instrument and evidence for lensing was obtained by several authors from its high-energy data. Observations of PKS 1830-211 were taken with the High Energy Stereoscopic System (H.E.S.S.) array of Imaging Atmospheric Cherenkov Telescopes in 2014 August, following a flare alert by the Fermi-LAT Collaboration. The H.E.S.S observations were aimed at detecting a gamma-ray flare delayed by 20-27 d from the alert flare, as expected from observations at other wavelengths. More than 12 h of good-quality data were taken with an analysis threshold of similar to 67 GeV. The significance of a potential signal is computed as a function of the date and the average significance over the whole period. Data are compared to simultaneous observations by Fermi-LAT. No photon excess or significant signal is detected. An upper limit on PKS 1830-211 flux above 67 GeV is computed and compared to the extrapolation of the Fermi-LAT flare spectrum.
CRIS-Team WoS Importer:2019-07-26
Keywords: gamma-rays: galaxies; gravitational lensing: strong; diffuse radiation

High-energy neutrino follow-up search of gravitational wave event GW150914 with ANTARES and IceCube - Adrian-Martinez, S.; Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2016)
We present the high-energy-neutrino follow-up observations of the first gravitational wave transient GW150914 observed by the Advanced LIGO detectors on September 14, 2015. We search for coincident neutrino candidates within the data recorded by the IceCube and Antares neutrino detectors. A possible joint detection could be used in targeted electromagnetic follow-up observations, given the significantly better angular resolution of neutrino events compared to gravitational waves. We find no neutrino candidates in both temporal and spatial coincidence with the gravitational wave event. Within ±500 s of the gravitational wave event, the number of neutrino candidates detected by IceCube and Antares were three and zero, respectively. This is consistent with the expected atmospheric background, and none of the neutrino candidates were directionally coincident with GW150914. We use this nondetection to constrain neutrino emission from the gravitational-wave event.

High-performance end-user analysis in pure Julia programming language - Ling, Jerry; Gál, Tamás (EPJ Web of Conferences, 2024)
We present tools for high-performance analysis written in pure Julia, a just-in-time (JIT) compiled dynamic programming language with a high-level syntax and performance. The packages we present center around UnROOT.jl, a pure Julia ROOT file I/O package that is optimized for speed, lazy reading, flexibility and thread safety. We discuss what affects performance in Julia, the challenges, and their solutions during the development of UnROOT.jl. We highlight type stability as a challenge and discuss its implication whenever any “compilation” happens (incl. Numba, Jax, C++) as well as Julia's specific ones. We demonstrate the performance and “easy to use” claim by comparing UnROOT.jl against popular alternatives (RDataFrame, Uproot, etc.) in medium-size realistic benchmarks, comparing both performance and code complexity. Finally, we also showcase real ATLAS analysis workflows both locally and on an HPC system, highlighting the composability of UnROOT.jl with multithread/process and out-of-core distributed computing libraries.
CRIS-Team Scopus Importer:2025-02-04

Imaging individual barium atoms in solid xenon for barium tagging in nEXO - Chambers, C.; Walton, T.; Fairbank, D.; Craycraft, A.; Yahne, D. R.; Todd, J.; Iverson, A.; Fairbank, W.; Alamre, A.; Albert, J. B.; Anton, Gisela; Arnquist, I. J.; et al. (Nature, 2019)
Double-β-decay involves the simultaneous conversion of two neutrons into two protons, and the emission of two electrons and two neutrinos; the neutrinoless process, although not yet observed, is thought to involve the emission of the two electrons but no neutrinos. The search for neutrinoless-double-β-decay probes fundamental properties of neutrinos, including whether or not the neutrino and antineutrino are distinct particles. Double-β-decay detectors are large and expensive, so it is essential to achieve the highest possible sensitivity with each study, and removing spurious contributions (‘background’) from detected signals is crucial. In the nEXO neutrinoless-double-β-decay experiment, the identification, or ‘tagging’, of the 136 Ba daughter atom resulting from the double-β decay of 136 Xe provides a technique for discriminating background. The tagging scheme studied here uses a cryogenic probe to trap the barium atom in a solid xenon matrix, where the barium atom is tagged through fluorescence imaging. Here we demonstrate the imaging and counting of individual barium atoms in solid xenon by scanning a focused laser across a solid xenon matrix deposited on a sapphire window. When the laser irradiates an individual atom, the fluorescence persists for about 30 seconds before dropping abruptly to the background level—a clear confirmation of one-atom imaging. Following evaporation of a barium deposit, the residual barium fluorescence is 0.16 per cent or less. Our technique achieves the imaging of single atoms in a solid noble element, establishing the basic principle of barium tagging for nEXO.
CRIS-Team Scopus Importer:2019-05-17

Impact of satellite trails on H.E.S.S. astronomical observations - Lang, Thomas; Spencer, Samuel; Mitchell, Alison (Astronomy & Astrophysics, 2023)
Context. The number of satellites launched into Earth’s orbit has almost tripled in the last three years (to over 4000) due to the increasing commercialisation of space. Multiple satellite constellations, consisting of over 400,000 individual satellites, have either been partially launched or are proposed for launch in the near future. Many of these satellites are highly reflective, resulting in a high optical brightness that affects ground-based astronomical observations. Despite this caveat, the potential effect of these satellites on gamma-ray-observing Imaging Atmospheric Cherenkov Telescopes (IACTs) has largely been assumed to be negligible due to their nanosecond-scale integration times. However, this assumption has not been verified to date. Aims. As IACTs are sensitive to optical wavelength light, we aim to identify satellite trails in data taken by the High Energy Stereo-scopic System (H.E.S.S.) IACT array. In particular, this study is aimed at quantifying the potential effects on data quality and extensive air shower event classification and reconstruction. Methods. Using night sky background measurements from H.E.S.S., we determined which observation times and pointing directions are affected most by these satellite trails. We then evaluated their impact on the standard Hillas parameter variables used for event analysis. Results. Due to the brightest trails, false trigger events can occur, however, for most modern analyses, the effect on astronomical results will be minimal. We observe a mild increase in the rate of trail detections over time (approximately doubling in three years), which is partially correlated with the number of satellite launches. Overall, the fraction of H.E.S.S. data affected (∼ 0.2% of dark time observations) is currently minimal. We note that these trails could still have a non-negligible effect on future Cherenkov Telescope Array observations if advanced analysis techniques designed to lower the energy threshold of the instrument are applied.<br
Keywords: Astroparticle Physics; Light Pollution; Methods: Data Analysis; Instrumentation: Detectors; Gamma-Rays: General

Intrinsic limits on resolutions in muon- and electron-neutrino charged-current events in the KM3NeT/ORCA detector - Adrian-Martinez, S.; Ageron, M.; Aiello, S.; Albert, A.; Ameli, F.; Anassontzis, E. G.; Andre, Michel; Androulakis, G.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Avgitas, T.; et al. (Journal of High Energy Physics, 2017)
Studying atmospheric neutrino oscillations in the few-GeV range with a multimegaton detector promises to determine the neutrino mass hierarchy. This is the main science goal pursued by the future KM3NeT/ORCA water Cherenkov detector in the Mediterranean Sea. In this paper, the processes that limit the obtainable resolution in both energy and direction in charged-current neutrino events in the ORCA detector are investigated. These processes include the composition of the hadronic fragmentation products, the subsequent particle propagation and the photon-sampling fraction of the detector. GEANT simulations of neutrino interactions in seawater produced by GENIE are used to study the effects in the 1-20 GeV range. It is found that fluctuations in the hadronic cascade in conjunction with the variation of the inelasticity y are most detrimental to the resolutions. The effect of limited photon sampling in the detector is of significantly less importance. These results will therefore also be applicable to similar detectors/media, such as those in ic
Keywords: Neutrino Detectors and Telescopes (experiments)

Is Julia ready to be adopted by HEP? - Gál, Tamás; Gras, Philippe; Hegner, Benedikt; Acosta, Uwe Hernandez; Kluth, Stefan; Ling, Jerry; Mato, Pere; Moreno, Alexander; Pivarski, Jim; Schulz, Oliver; Stewart, Graeme; Strube, Jan; et al. (EPJ Web of Conferences, 2024)
The Julia programming language was created 10 years ago and is now a mature and stable language with a large ecosystem including more than 8,000 third-party packages. It was designed for scientific programming to be a high-level and dynamic language as Python is, while achieving runtime performances comparable to C/C++ or even faster. With this, we ask ourselves if the Julia language and its ecosystem is ready now for its adoption by the High Energy Physics community. We will report on a number of investigations and studies of the Julia language that have been done for various representative HEP applications, ranging from computing intensive initial data processing of experimental data and simulation, to final interactive data analysis and plotting. Aspects of collaborative code development of large software within a HEP experiment has also been investigated: scalability with large development teams, continuous integration and code test, code reuse, language interoperability to enable an adiabatic migration of packages and tools, software installation and distribution, training of the community, benefit from development from industry and academia from other fields.
CRIS-Team Scopus Importer:2025-02-04

Joint Constraints on Galactic Diffuse Neutrino Emission from the ANTARES and IceCube Neutrino Telescopes - Albert, A.; Grasso, D.; Andre, M.; Anghinolfi, M.; Ardid, M.; Aubert, J. -J.; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; et al. (Astrophysical Journal Letters, 2018)
The existence of diffuse Galactic neutrino production is expected from cosmic-ray interactions with Galactic gas and radiation fields. Thus, neutrinos are a unique messenger offering the opportunity to test the products of Galactic cosmic-ray interactions up to energies of hundreds of TeV. Here we present a search for this production using ten years of Astronomy with a Neutrino Telescope and Abyss environmental RESearch (ANTARES) track and shower data, as well as seven years of IceCube track data. The data are combined into a joint likelihood test for neutrino emission according to the KRA(gamma) model assuming a 5 PeV per nucleon Galactic cosmic-ray cutoff. No significant excess is found. As a consequence, the limits presented in this Letter start constraining the model parameter space for Galactic cosmic-ray production and transport.
Keywords: cosmic rays; diffusion; Galaxy: disk; gamma rays: diffuse background; neutrinos

KM3NeT front-end and readout electronics system: hardware, firmware, and software - Aiello, Sebastiano; Amllei, Fabrizio; Andre, Michel; Androulakis, Giorgos; Anghinolfi, Marco; Anton, Gisela; Ardid, Miquel; Aublin, Julien; Bagatelas, Christos; Barbarino, Giancarlo; Baret, Bruny; Du Pree, Suzan Basegmez; et al. (Journal of Astronomical Telescopes, Instruments, and Systems, 2019)
The KM3NeT research infrastructure being built at the bottom of the Mediterranean Sea will host water-Cherenkov telescopes for the detection of cosmic neutrinos. The neutrino telescopes will consist of large volume three-dimensional grids of optical modules to detect the Cherenkov light from charged particles produced by neutrino-induced interactions. Each optical module houses 31 3-in. photomultiplier tubes, instrumentation for calibration of the photomultiplier signal and positioning of the optical module, and all associated electronics boards. By design, the total electrical power consumption of an optical module has been capped at seven Watts. We present an overview of the front-end and readout electronics system inside the optical module, which has been designed for a 1-ns synchronization between the clocks of all optical modules in the grid during a life time of at least 20 years. (C) 2019 Society of Photo-Optical Instrumentation Engineers (SPIE)
CRIS-Team WoS Importer:2020-02-28

Large-scale simulations of antihelium production in cosmic-ray interactions - Shukla, Anirvan; Datta, Amaresh; Von Doetinchem, Philip; Gomez-Coral, Diego-Mauricio; Kanitz, Carina (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2020)
The possibility of antihelium production in interaction of cosmic rays with the interstellar gas is studied using large-scale Monte Carlo simulations. For this purpose, an energy-dependent coalescence mechanism developed previously is extended to estimate the production of light antinuclei ((3)(He) over bar and (4)(He) over bar). The uncertainty in the coalescence parameter and its effect on the expected antiparticle flux is also investigated. The simulated background antihelium fluxes are found to be lower than the fluxes predicted by simplified models using numerical scaling techniques.
CRIS-Team WoS Importer:2020-09-25

Letter of intent for KM3NeT 2.0 - Adrian-Martinez, S.; Ageron, M.; Aharonian, F.; Aiello, S.; Albert, A.; Ameli, F.; Anassontzis, E.; Andre, Michel; Androulakis, G.; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; et al. (Journal of Physics G: Nuclear and Particle Physics, 2016)
The main objectives of the KM3NeT Collaboration are (i) the discovery and subsequent observation of high-energy neutrino sources in the Universe and (ii) the determination of the mass hierarchy of neutrinos. These objectives are strongly motivated by two recent important discoveries, namely: (1) the high-energy astrophysical neutrino signal reported by IceCube and (2) the sizable contribution of electron neutrinos to the third neutrino mass eigenstate as reported by Daya Bay, Reno and others. To meet these objectives, the KM3NeT Collaboration plans to build a new Research Infrastructure consisting of a network of deep-sea neutrino telescopes in the Mediterranean Sea. A phased and distributed implementation is pursued which maximises the access to regional funds, the availability of human resources and the synergistic opportunities for the Earth and sea sciences community. Three suitable deep-sea sites are selected, namely off-shore Toulon (France), Capo Passero (Sicily, Italy) and Pylos (Peloponnese, Greece). The infrastructure will consist of three so-called building blocks. A building block comprises 115 strings, each string comprises 18 optical modules and each optical module comprises 31 photo-multiplier tubes. Each building block thus constitutes a three-dimensional array of photo sensors that can be used to detect the Cherenkov light produced by relativistic particles emerging from neutrino interactions. Two building blocks will be sparsely configured to fully explore the IceCube signal with similar instrumented volume, different methodology, improved resolution and complementary field of view, including the galactic plane. One building block will be densely configured to precisely measure atmospheric neutrino oscillations.
Keywords: deep sea neutrino telescope; neutrino astronomy; neutrino mass hierarchy; neutrino physics

Letter of interest for a neutrino beam from Protvino to KM3NeT/ORCA - Akindinov, V.; Anassontzis, E. G.; Anton, Gisela; Ardid, M.; Aublin, J.; Baret, B.; Bertin,; Bourret, S.; Bozza, C.; Bruchner, M.; Bruijn, R.; Brunner, J.; et al. (European Physical Journal C: Particles and Fields, 2019)
The Protvino accelerator facility located in the Moscow region, Russia, is in a good position to offer a rich experimental research program in the field of neutrino physics. Of particular interest is the possibility to direct a neutrino beam from Protvino towards the KM3NeT/ORCA detector, which is currently under construction in the Mediterranean Sea 40 km offshore Toulon, France. This proposal is known as P2O. Thanks to its baseline of 2595 km, this experiment would yield an unparalleled sensitivity to matter effects in the Earth, allowing for the determination of the neutrino mass ordering with a high level of certainty after only a few years of running at a modest beam intensity of sensitivity to the leptonic CP-violating Dirac phase can be achieved. A second stage of the experiment, comprising a further intensity upgrade of the accelerator complex and a densified version of the ORCA detector (Super-ORCA), would allow for up to a 6 sigma[12pt] resolution on the CP phase after 10 years of running with a 450 kW beam, competitive with other planned experiments. The initial composition and energy spectrum of the neutrino beam would need to be monitored by a near detector, to be constructed several hundred meters downstream from the proton beam target. The same neutrino beam and near detector set-up would also allow for neutrino-nucleus cross section measurements to be performed. A short-baseline sterile neutrino search experiment would also be possible.
CRIS-Team WoS Importer:2019-10-04

Limits on dark matter annihilation in the sun using the ANTARES neutrino telescope - Adrian-Martineza, S.; Albert, A.; Andre, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Physics Letters B, 2016)
A search for muon neutrinos originating from dark matter annihilations in the Sun is performed using the data recorded by the ANTARES neutrino telescope from 2007 to 2012. In order to obtain the best possible sensitivities to dark matter signals, an optimisation of the event selection criteria is performed taking into account the background of atmospheric muons, atmospheric neutrinos and the energy spectra of the expected neutrino signals. No significant excess over the background is observed and 90% C.L. upper limits on the neutrino flux, the spin-dependent and spin-independent WIMP-nucleon cross-sections are derived for WIMP masses ranging from 50 GeV to 5 TeV for the annihilation channels WIMP+WIMP→bb-,WW and ττ.
Keywords: Dark matter; Indirect detection; Neutralino; Neutrino telescope; Sun; WIMP

LMC N132D: A mature supernova remnant with a power-law gamma-ray spectrum extending beyond 8 TeV - Abdalla, H.; Aharonian, F.; Mitchell, Alison; Benkhali, F. Ait; Anguner, E. O.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, Michael; Baghmanyan,; Martins, V. Barbosa; et al. (Astronomy & Astrophysics, 2021)
Context. Supernova remnants (SNRs) are commonly thought to be the dominant sources of Galactic cosmic rays up to the knee of the cosmic-ray spectrum at a few PeV. Imaging Atmospheric Cherenkov Telescopes have revealed young SNRs as very-high-energy (VHE, >100 GeV) gamma-ray sources, but for only a few SNRs the hadronic cosmic-ray origin of their gamma-ray emission is indisputably established. In all these cases, the gamma-ray spectra exhibit a spectral cutoff at energies much below 100 TeV and thus do not reach the PeVatron regime. Aims. The aim of this work was to achieve a firm detection for the oxygen-rich SNR LMC N132D in the VHE gamma-ray domain with an extended set of data, and to clarify the spectral characteristics and the localization of the gamma-ray emission from this exceptionally powerful gamma-ray-emitting SNR. Methods. We analyzed 252 h of High Energy Stereoscopic System (H.E.S.S.) observations towards SNR N132D that were accumulated between December 2004 and March 2016 during a deep survey of the Large Magellanic Cloud, adding 104 h of observations to the previously published data set to ensure a > 5σ detection. To broaden the gamma-ray spectral coverage required for modeling the spectral energy distribution, an analysis of Fermi-LAT Pass 8 data was also included. Results. We unambiguously detect N132D at VHE with a significance of 5.7σ. We report the results of a detailed analysis of its spectrum and localization based on the extended H.E.S.S. data set. The joint analysis of the extended H.E.S.S and Fermi-LAT data results in a spectral energy distribution in the energy range from 1.7 GeV to 14.8 TeV, which suggests a high luminosity of N132D at GeV and TeV energies. We set a lower limit on a gamma-ray cutoff energy of 8 TeV with a confidence level of 95%. The new gamma-ray spectrum as well as multiwavelength observations of N132D when compared to physical models suggests a hadronic origin of the VHE gamma-ray emission. Conclusions. SNR N132D is a VHE gamma-ray source that shows a spectrum extending to the VHE domain without a spectral cutoff at a few TeV, unlike the younger oxygen-rich SNR Cassiopeia A. The gamma-ray emission is best explained by a dominant hadronic component formed by diffusive shock acceleration. The gamma-ray properties of N132D may be affected by an interaction with a nearby molecular cloud that partially lies inside the 95% confidence region of the source position.
CRIS-Team Scopus Importer:2021-11-19
Keywords: Cosmic rays; Gamma rays: General; ISM: Supernova remnants

Long-term monitoring of the ANTARES optical module efficiencies using K-40 decays in sea water - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; et al. (European Physical Journal C, 2018)
Cherenkov light induced by radioactive decay products is one of the major sources of background light for deep-sea neutrino telescopes such as ANTARES. These decays are at the same time a powerful calibration source. Using data collected by the ANTARES neutrino telescope from mid 2008 to 2017, the time evolution of the photon detection efficiency of optical modules is studied. A modest loss of only 20% in 9 years is observed. The relative time calibration between adjacent modules is derived as well.

Measurement of atmospheric neutrino oscillations with the ANTARES neutrino telescope ANTARES Collaboration - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J. -J.; Baret, B.; Basa, S.; et al. (Physics Letters B, 2012)
The data taken with the ANTARES neutrino telescope from 2007 to 2010, a total live time of 863 days, are used to measure the oscillation parameters of atmospheric neutrinos. Muon tracks are reconstructed with energies as low as 20 GeV. Neutrino oscillations will cause a suppression of vertical upgoing muon neutrinos of such energies crossing the Earth. The parameters determining the oscillation of atmospheric neutrinos are extracted by fitting the event rate as a function of the ratio of the estimated neutrino energy and reconstructed flight path through the Earth. Measurement contours of the oscillation parameters in a two-flavour approximation are derived. Assuming maximal mixing, a mass difference of Delta m(32)(2) = (3.1 +/- 0.9) . 10(-3) eV(2) is obtained, in good agreement with the world average value. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Neutrino oscillations; Neutrino telescope; ANTARES

Measurement of atmospheric tau neutrino appearance with IceCube DeepCore - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, Markus; Ahrens, M.; Altmann, D.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; Arguelles, C.; et al. (Physical Review D, 2019)
We present a measurement of atmospheric tau neutrino appearance from oscillations with three years of data from the DeepCore subarray of the IceCube Neutrino Observatory. This analysis uses atmospheric neutrinos from the full sky with reconstructed energies between 5.6 and 56 GeV to search for a statistical excess of cascadelike neutrino events which are the signature of nu(tau) interactions. For CC thorn NC (CC-only) interactions, we measure the tau neutrino normalization to be 0.73(-0.24)(+0.30) (0.57(-0.30)(+0.36)) and exclude the absence of tau neutrino oscillations at a significance of 3.2 sigma (2.0 sigma) These results are consistent with, and of similar precision to, a confirmatory IceCube analysis also presented, as well as measurements performed by other experiments.
CRIS-Team WoS Importer:2019-02-27

Measurement of the atmospheric nu (mu) energy spectrum from 100 GeV to 200 TeV with the ANTARES telescope - Adrian-Martinez, S.; Albert, A.; Al Samarai, I.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J. -J.; Baret, B.; Barrios-Marti, J.; et al. (European Physical Journal C, 2013)
Atmospheric neutrinos are produced during cascades initiated by the interaction of primary cosmic rays with air nuclei. In this paper, a measurement of the atmospheric energy spectrum in the energy range 0.1-200 TeV is presented, using data collected by the ANTARES underwater neutrino telescope from 2008 to 2011. Overall, the measured flux is similar to 25 % higher than predicted by the conventional neutrino flux, and compatible with the measurements reported in ice. The flux is compatible with a single power-law dependence with spectral index gamma (meas)=3.58 +/- 0.12. With the present statistics the contribution of prompt neutrinos cannot be established.

Measurement of the atmospheric νe and νμ energy spectra with the ANTARES neutrino telescope - Albert, A.; Alves, S.; André, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bendahman, M.; et al. (Physics Letters B, 2021)
This letter presents a combined measurement of the energy spectra of atmospheric νe and νμ in the energy range between ∼100 GeV and ∼50 TeV with the ANTARES neutrino telescope. The analysis uses 3012 days of detector livetime in the period 2007–2017, and selects 1016 neutrinos interacting in (or close to) the instrumented volume of the detector, yielding shower-like events (mainly from νe+ν‾e charged current plus all neutrino neutral current interactions) and starting track events (mainly from νμ+ν‾μ charged current interactions). The contamination by atmospheric muons in the final sample is suppressed at the level of a few per mill by different steps in the selection analysis, including a Boosted Decision Tree classifier. The distribution of reconstructed events is unfolded in terms of electron and muon neutrino fluxes. The derived energy spectra are compared with previous measurements that, above 100 GeV, are limited to experiments in polar ice and, for νμ, to Super-Kamiokande.
CRIS-Team Scopus Importer:2021-04-02
Keywords: ANTARES; Atmospheric neutrinos; Neutrino telescope

Measurement of the group velocity of light in sea water at the ANTARES site - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Aubert, J-J.; Baret, B.; et al. (Astroparticle Physics, 2012)
The group velocity of light has been measured at eight different wavelengths between 385 nm and 532 nm in the Mediterranean Sea at a depth of about 2.2 km with the ANTARES optical beacon systems. A parametrisation of the dependence of the refractive index on wavelength based on the salinity, pressure and temperature of the sea water at the ANTARES site is in good agreement with these measurements. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: ANTARES; Neutrino telescope; Optical beacon system; Velocity of light; Refractive index

Measurement of the scintillation and ionization response of liquid xenon at MeV energies in the EXO-200 experiment - Anton, Gisela; Badhrees, I.; Barbeau, P. S.; Beck, D.; Belov, V.; Bhatta, T.; Breidenbach, M.; Brunner, T.; Cao, G. F.; Cen, W. R.; Chambers, C.; Cleveland, B.; et al. (Physical Review C - Nuclear Physics, 2020)
Liquid xenon (LXe) is employed in a number of current and future detectors for rare event searches. We use the EXO-200 experimental data to measure the absolute scintillation and ionization yields generated by gamma interactions from Th-228 (2615 keV), Ra-226 (1764 keV), and Co-60 (1332 keV and 1173 keV) calibration sources, over a range of electric fields. The W value that defines the recombination-independent energy scale is measured to be 11.5 +/- 0.5 (syst.) +/- 0.1 (stat.) eV. These data are also used to measure the recombination fluctuations in the number of electrons and photons produced by the calibration sources at the MeV scale, which deviate from extrapolations of lower-energy data. Additionally, a semiempirical model for the energy resolution of the detector is developed, which is used to constrain the recombination efficiency, i.e., the fraction of recombined electrons that result in the emission of a detectable photon. Detailed measurements of the absolute charge and light yields for MeV-scale electron recoils are important for predicting the performance of future neutrinoless double beta-decay detectors.
CRIS-Team WoS Importer:2020-06-30

Measurement of the Spectral Shape of the beta-Decay of Xe-137 to the Ground State of Cs-137 in EXO-200 and Comparison with Theory - Al Kharusi, S.; Anton, Gisela; Badhrees, I.; Barbeau, P. S.; Beck, D.; Belov, V.; Bhatta, T.; Breidenbach, M.; Brunner, T.; Cao, G. F.; Cen, W. R.; Chambers, C.; et al. (Physical Review Letters, 2020)
We report on a comparison between the theoretically predicted and experimentally measured spectra of the first-forbidden nonunique beta-decay transition Xe-137(7/2(-)) -> Cs-137(7/2(+)). The experimental data were acquired by the EXO-200 experiment during a deployment of an AmBe neutron source. The ultralow background environment of EXO-200, together with dedicated source deployment and analysis procedures, allowed for collection of a pure sample of the decays, with an estimated signal to background ratio of more than 99 to 1 in the energy range from 1075 to 4175 keV. In addition to providing a rare and accurate measurement of the first-forbidden nonunique beta-decay shape, this work constitutes a novel test of the calculated electron spectral shapes in the context of the reactor antineutrino anomaly and spectral bump.
CRIS-Team WoS Importer:2020-06-26

Measurements of electron transport in liquid and gas Xenon using a laser-driven photocathode - Njoya, O.; Tsang, T.; Tarka, M.; Fairbank, W.; Kumar, K. S.; Rao, T.; Wager, T.; Kharusi, S. Al; Anton, Gisela; Arnquist, I. J.; Badhrees, I.; Barbeau, P. S.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2020)
Measurements of electron drift properties in liquid and gaseous xenon are reported. The electrons are generated by the photoelectric effect in a semi-transparent gold photocathode driven in transmission mode with a pulsed ultraviolet laser. The charges drift and diffuse in a small chamber at various electric fields and a fixed drift distance of 2.0 cm. At an electric field of 0.5 kV/cm, the measured drift velocities and corresponding temperature coefficients respectively are 1.97±0.04mm∕μs and (−0.69±0.05)%/K for liquid xenon, and 1.42±0.03mm∕μs and (+0.11±0.01)%/K for gaseous xenon at 1.5 bar. In addition, we measure longitudinal diffusion coefficients of 25.7±4.6 cm2/s and 149±23 cm2/s, for liquid and gas, respectively. The quantum efficiency of the gold photocathode is studied at the photon energy of 4.73 eV in liquid and gaseous xenon, and vacuum. These charge transport properties and the behavior of photocathodes in a xenon environment are important in designing and calibrating future large scale noble liquid detectors.
CRIS-Team Scopus Importer:2020-05-29

Measurements using the inelasticity distribution of multi-TeV neutrino interactions in IceCube - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, Markus; Ahrens, M.; Al Samarai, I.; Altmann, D.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; et al. (Physical Review D, 2019)
Inelasticity, the fraction of a neutrino's energy transferred to hadrons, is a quantity of interest in the study of astrophysical and atmospheric neutrino interactions at multi-TeV energies with IceCube. In this work, a sample of contained neutrino interactions in IceCube is obtained from five years of data and classified as 2650 tracks and 965 cascades. Tracks arise predominantly from charged-current nu(mu) interactions, and we demonstrate that we can reconstruct their energy and inelasticity. The inelasticity distribution is found to be consistent with the calculation of Cooper-Sarkar et al. across the energy range from similar to 1 to similar to 100 TeV. Along with cascades from neutrinos of all flavors, we also perform a fit over the energy, zenith angle, and inelasticity distribution to characterize the flux of astrophysical and atmospheric neutrinos. The energy spectrum of diffuse astrophysical neutrinos is described well by a power law in both track and cascade samples, and a best-fit index gamma = 2.62 +/- 0.07 is found in the energy range from 3.5 TeV to 2.6 PeV. Limits are set on the astrophysical flavor composition and are compatible with a ratio of (1/3 : 1/3 : 1/3)(circle plus). Exploiting the distinct inelasticity distribution of nu(mu) and (nu) over bar (mu) interactions, the atmospheric nu(mu) to (nu) over bar (mu) flux ratio in the energy range from 770 GeV to 21 TeV is found to be 0.77(-0.25)(+0.44) times the calculation by Honda et al. Lastly, the inelasticity distribution is also sensitive to neutrino charged-current charm production. The data are consistent with a leading-order calculation, with zero charm production excluded at 91% confidence level. Future analyses of inelasticity distributions may probe new physics that affects neutrino interactions both in and beyond the Standard Model.
CRIS-Team WoS Importer:2019-02-27

Measuring the atmospheric neutrino oscillation parameters and constraining the 3+1 neutrino model with ten years of ANTARES data - Albert, A.; André, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Martí, J.; Basa, S.; Belhorma, B.; et al. (Journal of High Energy Physics, 2019)
The ANTARES neutrino telescope has an energy threshold of a few tens of GeV. This allows to study the phenomenon of atmospheric muon neutrino disappearance due to neutrino oscillations. In a similar way, constraints on the 3+1 neutrino model, which foresees the existence of one sterile neutrino, can be inferred. Using data collected by the ANTARES neutrino telescope from 2007 to 2016, a new measurement of Δm322 and θ23 has been performed — which is consistent with world best-fit values — and constraints on the 3+1 neutrino model have been derived.[Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2019-07-02
Keywords: Neutrino Detectors and Telescopes (experiments); Oscillation

Model-independent search for neutrino sources with the ANTARES neutrino telescope - Albert, A.; André, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Avgitas, T.; Baret, B.; Barrios-Martí, J.; Basa, S.; Bertin, V.; Biagi, S.; et al. (Astroparticle Physics, 2020)
A novel method to analyse the spatial distribution of neutrino candidates recorded with the ANTARES neutrino telescope is introduced, searching for an excess of neutrinos in a region of arbitrary size and shape from any direction in the sky. Techniques originating from the domains of machine learning, pattern recognition and image processing are used to purify the sample of neutrino candidates and for the analysis of the obtained skymap. In contrast to a dedicated search for a specific neutrino emission model, this approach is sensitive to a wide range of possible morphologies of potential sources of high-energy neutrino emission. The application of these methods to ANTARES data yields a large-scale excess with a post-trial significance of 2.5σ. Applied to public data from IceCube in its IC40 configuration, an excess consistent with the results from ANTARES is observed with a post-trial significance of 2.1σ.
CRIS-Team Scopus Importer:2019-07-02
Keywords: Anisotropy; Astroparticle physics; Neutrino astronomy; Pattern recognition

Monte Carlo simulations for the ANTARES underwater neutrino telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin, V.; Biagi, S.; et al. (Journal of Cosmology and Astroparticle Physics, 2021)
Monte Carlo simulations are a unique tool to check the response of a detector and to monitor its performance. For a deep-sea neutrino telescope, the variability of the environmental conditions that can affect the behaviour of the data acquisition system must be considered, in addition to a reliable description of the active parts of the detector and of the features of physics events, in order to produce a realistic set of simulated events. In this paper, the software tools used to produce neutrino and cosmic ray signatures in the telescope and the strategy developed to represent the time evolution of the natural environment and of the detector efficiency are described.
CRIS-Team Scopus Importer:2021-02-12
Keywords: Cosmic ray experiments; Neutrino astronomy; Neutrino detectors; Neutrino experiments

Multi-messenger Observations of a Binary Neutron Star Merger - Abbott, B. P.; Abbott, R.; Abbott, T. D.; Acernese, F.; Ackley, K.; Adams, C.; Adams, T.; Addesso, Paolo; Adhikari, R. X.; Adya, V. B.; Affeldt, C.; Afrough, M.; et al. (Astrophysical Journal Letters, 2017)
On 2017 August 17 a binary neutron star coalescence candidate (later designated GW170817) with merger time 12:41:04 UTC was observed through gravitational waves by the Advanced LIGO and Advanced Virgo detectors. The Fermi Gamma-ray Burst Monitor independently detected a gamma-ray burst (GRB 170817A) with a time delay of similar to 1.7 s with respect to the merger time. From the gravitational-wave signal, the source was initially localized to a sky region of 31 deg(2) at a luminosity distance of 40(-8)(+8) Mpc and with component masses consistent with neutron stars. The component masses were later measured to be in the range 0.86 to 2.26 M-circle dot. An extensive observing campaign was launched across the electromagnetic spectrum leading to the discovery of a bright optical transient (SSS17a, now with the IAU identification of AT 2017gfo) in NGC 4993 (at similar to 40 Mpc) less than 11 hours after the merger by the One-Meter, Two Hemisphere (1M2H) team using the 1 m Swope Telescope. The optical transient was independently detected by multiple teams within an hour. Subsequent observations targeted the object and its environment. Early ultraviolet observations revealed a blue transient that faded within 48 hours. Optical and infrared observations showed a redward evolution over similar to 10 days. Following early non-detections, X-ray and radio emission were discovered at the transient's position similar to 9 and similar to 16 days, respectively, after the merger. Both the X-ray and radio emission likely arise from a physical process that is distinct from the one that generates the UV/optical/near-infrared emission. No ultra-high-energy gamma-rays and no neutrino candidates consistent with the source were found in follow-up searches. These observations support the hypothesis that GW170817 was produced by the merger of two neutron stars in NGC4993 followed by a short gamma-ray burst (GRB 170817A) and a kilonova/macronova powered by the radioactive decay of r-process nuclei synthesized in the ejecta.
Keywords: gravitational waves; stars: neutron

Multimessenger observations of a flaring blazar coincident with high-energy neutrino IceCube-170922A - Aartsen, M. G.; Ackermann, Markus; Mitchell, Alison; Adams, J.; Aguilar, J. A.; Ahlers, Markus; Ahrens, M.; Al Samarai, I.; Altmann, D.; Andeen, K.; Anderson, T.; Ansseau, I.; et al. (Science, 2018)
CRIS-Team WoS Importer:2020-01-15

MURCHISON WIDEFIELD ARRAY LIMITS on RADIO EMISSION from ANTARES NEUTRINO EVENTS - Croft, Steve; Kaplan, D. L.; Tingay, S. J.; Murphy, Tara; Bell, M. E.; Rowlinson, Antonia; Adrian-Martinez, S.; Ageron, M.; Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; et al. (Astrophysical Journal Letters, 2016)
We present a search, using the Murchison Widefield Array (MWA), for electromagnetic (EM) counterparts to two candidate high-energy neutrino events detected by the ANTARES neutrino telescope in 2013 November and 2014 March. These events were selected by ANTARES because they are consistent, within 0°.4, with the locations of galaxies within 20 Mpc of Earth. Using MWA archival data at frequencies between 118 and 182 MHz, taken ∼20 days prior to, at the same time as, and up to a year after the neutrino triggers, we look for transient or strongly variable radio sources that are consistent with the neutrino positions. No such counterparts are detected, and we set a 5σ upper limit for low-frequency radio emission of ∼10 erg s for progenitors at 20 Mpc. If the neutrino sources are instead not in nearby galaxies, but originate in binary neutron star coalescences, our limits place the progenitors at z 0.2. While it is possible, due to the high background from atmospheric neutrinos, that neither event is astrophysical, the MWA observations are nevertheless among the first to follow up neutrino candidates in the radio, and illustrate the promise of wide-field instruments like MWA for detecting EM counterparts to such events.
Keywords: neutrinos; radio continuum: general

New constraints on all flavor Galactic diffuse neutrino emission with the ANTARES telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin, V.; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2017)
The flux of very high-energy neutrinos produced in our Galaxy by the interaction of accelerated cosmic rays with the interstellar medium is not yet determined. The characterization of this flux will shed light on Galactic accelerator features, gas distribution morphology and Galactic cosmic ray transport. The central Galactic plane can be the site of an enhanced neutrino production, thus leading to anisotropies in the extraterrestrial neutrino signal as measured by the IceCube Collaboration. The ANTARES neutrino telescope, located in the Mediterranean Sea, offers a favorable view of this part of the sky, thereby allowing for a contribution to the determination of this flux. The expected diffuse Galactic neutrino emission can be obtained, linking a model of generation and propagation of cosmic rays with the morphology of the gas distribution in the Milky Way. In this paper, the so-called "gamma model" introduced recently to explain the high-energy gamma-ray diffuse Galactic emission is assumed as reference. The neutrino flux predicted by the "gamma model" depends on the assumed primary cosmic ray spectrum cutoff. Considering a radially dependent diffusion coefficient, this proposed scenario is able to account for the local cosmic ray measurements, as well as for the Galactic gamma-ray observations. Nine years of ANTARES data are used in this work to search for a possible Galactic contribution according to this scenario. All flavor neutrino interactions are considered. No excess of events is observed, and an upper limit is set on the neutrino flux of 1.1 (1.2) times the prediction of the "gamma model," assuming the primary cosmic ray spectrum cutoff at 5 (50) PeV. This limit excludes the diffuse Galactic neutrino emission as the major cause of the "spectral anomaly" between the two hemispheres measured by IceCube.

Nuradioreco: A new reconstruction framework for radio neutrino detectors - Glaser, Christian; Nelles, Anna; Plaisier, Ilse; Welling, Christoph; Barwick, Steven W.; García-Fernández, Daniel; Gaswint, Geoffrey; Lahmann, Robert; Persichilli, Christopher (Proceedings of Science, 2019)
The radio detection of high-energy neutrinos has huge potential as it allows for cost-efficient instrumentation of huge volumes leading to unprecedented sensitivity in the 1016 eV - 1020 eV energy regime. The required technological advances of the detector hardware have matured in the two pilot arrays ARA and ARIANNA and the focus shifts to analysis and reconstruction techniques. We present a new modular framework for the detector simulation and data reconstruction of radio detectors of neutrinos and cosmic rays. The software is written in Python and publicly available on github. We built on the long-standing experience of cosmic-ray detectors as many aspects of data processing, detector simulation and reconstruction are very similar for neutrinos. NuRadioReco is already being used by the ARIANNA experiment and for the detector simulation in the novel neutrino MC code NuRadioMC. It was designed to be flexible so that is can be adapted for different neutrino and cosmic-ray detectors and can serve as the software framework of a future large-scale Askaryan detector which is actively discussed in the community.
CRIS-Team Scopus Importer:2021-04-20

Observation of the cosmic ray shadow of the Sun with the ANTARES neutrino telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin,; Biagi, S.; et al. (Physical Review D, 2020)
The ANTARES detector is an undersea neutrino telescope in the Mediterranean Sea. The search for pointlike neutrino sources is one of the main goals of the ANTARES telescope, requiring a reliable method to evaluate the detector angular resolution and pointing accuracy. This work describes the study of the Sun "shadow" effect with the ANTARES detector. The shadow is the deficit in the atmospheric muon flux in the direction of the Sun caused by the absorption of the primary cosmic rays. This analysis is based on the data collected between 2008 and 2017 by the ANTARES telescope. The observed statistical significance of the Sun shadow detection is 3.7 sigma, with an estimated angular resolution of 0.59 degrees +/- 0.10 degrees for downward-going muons. The pointing accuracy is found to be consistent with the expectations and no evidence of systematic pointing shifts is observed.
CRIS-Team WoS Importer:2021-01-15

Observation of the Gamma-Ray Binary HESS J0632+057 with the HESS, MAGIC, and VERITAS Telescopes - Adams, C. B.; Benbow, W.; Brill, A.; Buckley, J. H.; Capasso, M.; Chromey, A. J.; Errando, M.; Falcone, A.; Farrell, K. A.; Feng, Q.; Finley, J. P.; Foote, G. M.; et al. (Astrophysical Journal, 2021)
The results of gamma-ray observations of the binary system HESS J0632 + 057 collected during 450 hr over 15 yr, between 2004 and 2019, are presented. Data taken with the atmospheric Cherenkov telescopes H.E.S.S., MAGIC, and VERITAS at energies above 350 GeV were used together with observations at X-ray energies obtained with Swift-XRT, Chandra, XMM-Newton, NuSTAR, and Suzaku. Some of these observations were accompanied by measurements of the H alpha emission line. A significant detection of the modulation of the very high-energy gamma-ray fluxes with a period of 316.7 +/- 4.4 days is reported, consistent with the period of 317.3 +/- 0.7 days obtained with a refined analysis of X-ray data. The analysis of data from four orbital cycles with dense observational coverage reveals short-timescale variability, with flux-decay timescales of less than 20 days at very high energies. Flux variations observed over a timescale of several years indicate orbit-to-orbit variability. The analysis confirms the previously reported correlation of X-ray and gamma-ray emission from the system at very high significance, but cannot find any correlation of optical H alpha parameters with fluxes at X-ray or gamma-ray energies in simultaneous observations. The key finding is that the emission of HESS J0632 + 057 in the X-ray and gamma-ray energy bands is highly variable on different timescales. The ratio of gamma-ray to X-ray flux shows the equality or even dominance of the gamma-ray energy range. This wealth of new data is interpreted taking into account the insufficient knowledge of the ephemeris of the system, and discussed in the context of results reported on other gamma-ray binary systems.
CRIS-Team WoS Importer:2022-01-14

Optical and X-ray early follow-up of ANTARES neutrino alerts - Adrian-Martinez, S.; Ageron, M.; Albert, A.; Al Samarai, I.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; et al. (Journal of Cosmology and Astroparticle Physics, 2016)
High-energy neutrinos could be produced in the interaction of charged cosmic rays with matter or radiation surrounding astrophysical sources. Even with the recent detection of extraterrestrial high-energy neutrinos by the IceCube experiment, no astrophysical neutrino source has yet been discovered. Transient sources, such as gamma-ray bursts, core-collapse supernovae, or active galactic nuclei are promising candidates. Multi-messenger programs offer a unique opportunity to detect these transient sources. By combining the information provided by the ANTARES neutrino telescope with information coming from other observatories, the probability of detecting a source is enhanced, allowing the possibility of identifying a neutrino progenitor from a single detected event. A method based on optical and X-ray follow-ups of high-energy neutrino alerts has been developed within the ANTARES collaboration. This method does not require any assumptions on the relation between neutrino and photon spectra other than time-correlation. This program, denoted as TAToO, triggers a network of robotic optical telescopes (TAROT and ROTSE) and the Swift-XRT with a delay of only a few seconds after a neutrino detection, and is therefore well-suited to search for fast transient sources. To identify an optical or X-ray counterpart to a neutrino signal, the images provided by the follow-up observations are analysed with dedicated pipelines. A total of 42 alerts with optical and 7 alerts with X-ray images taken with a maximum delay of 24 hours after the neutrino trigger have been analysed. No optical or X-ray counterparts associated to the neutrino triggers have been found, and upper limits on transient source magnitudes have been derived. The probability to reject the gamma-ray burst origin hypothesis has been computed for each alert.

Optical Modules and Readout Scheme for the KM3NeT Neutrino Telescope - Kalekin, Oleg (NUCL PHYS B-PROC SUP, 2012)
Keywords: High energy neutrino detection; Photomultiplier; KM3NeT

Optical modules for the neutrino telescope KM3NeT - Kalekin, Oleg (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2010)
Keywords: Cherenkov light detection; High energy neutrino; Deep-sea neutrino telescope

Orbital solutions of eight close sdB binaries and constraints on the nature of the unseen companions - Geier, S.; Ostensen, R. H.; Heber, Ulrich; Kupfer, Thomas; Maxted, P. F. L.; Barlow, B. N.; Vuckovic, Maja; Tillich, A.; Mueller, S.; Edelmann, Heinz; Classen, Lew; Mcleod, A. F. (Astronomy & Astrophysics, 2014)
The project Massive Unseen Companions to Hot Faint Underluminous Stars from SDSS (MUCHFUSS) aims at finding hot subdwarf stars (sdBs) with massive compact companions such as white dwarfs, neutron stars, or stellar-mass black holes. In a supplementary programme we obtained time-resolved spectroscopy of known hot subdwarf binary candidates. Here we present orbital solutions of eight close sdB binaries with orbital periods ranging from 0.1 d to, which allow us to derive lower limits on the masses of their companions. Additionally, a dedicated photometric follow-up campaign was conducted to obtain light curves of the reflection-effect binary HS 2043+0615. We are able to constrain the most likely nature of the companions in all cases but one, making use of information derived from photometry and spectroscopy. Four sdBs have white dwarf companions, while another three are orbited by low-mass main sequence stars of spectral type M. © 2014 ESO.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: spectroscopic; Subdwarfs

Panel Discussion V: Neutrino Physics - Obratzsov, Vladimir; Konaka, Akira; Ikeda, Motoyasu; Jediny, Filip; Shirokov, Evgeny; Kalekin, Oleg; Palomares-Ruiz, Sergio (PROCEEDINGS OF THE XXX-TH INTERNATIONAL WORKSHOP ON HIGH ENERGY PHYSICS, 2015)

Particle transport within the pulsar wind nebula HESS J1825-137 - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, M.; Barnard, Monica; Becherini, Y.; Tjus, J. Becker; et al. (Astronomy & Astrophysics, 2019)
Context. We present a detailed view of the pulsar wind nebula (PWN) HESS J1825-137. We aim to constrain the mechanisms dominating the particle transport within the nebula, accounting for its anomalously large size and spectral characteristics. Aims. The nebula was studied using a deep exposure from over 12 years of H.E.S.S. I operation, together with data from H.E.S.S. II that improve the low-energy sensitivity. Enhanced energy-dependent morphological and spatially resolved spectral analyses probe the very high energy (VHE, E > 0.1 TeV) γ-ray properties of the nebula. Methods. The nebula emission is revealed to extend out to 1.5° from the pulsar, ∼1.5 times farther than previously seen, making HESS J1825-137, with an intrinsic diameter of ∼100 pc, potentially the largest γ-ray PWN currently known. Characterising the strongly energy-dependent morphology of the nebula enables us to constrain the particle transport mechanisms. A dependence of the nebula extent with energy of RE α with α = -0.29 ± 0.04 stat ± 0.05 sys disfavours a pure diffusion scenario for particle transport within the nebula. The total γ-ray flux of the nebula above 1 TeV is found to be (1.12 ± 0.03 stat ± 0.25 sys ) × 10 -11 cm -2 s -1 , corresponding to ∼64% of the flux of the Crab nebula. Results. HESS J1825-137 is a PWN with clearly energy-dependent morphology at VHE γ-ray energies. This source is used as a laboratory to investigate particle transport within intermediate-age PWNe. Based on deep observations of this highly spatially extended PWN, we produce a spectral map of the region that provides insights into the spectral variation within the nebula.
CRIS-Team Scopus Importer:2019-05-02
Keywords: gamma rays: general; acceleration of particles; convection; diffusion; pulsars: general

Performances of JEM-EUSO: angular reconstruction (vol 30, pg 153, 2015) - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, A.; Arai, Y.; Asano, K.; Ave Pernas, M.; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)

Performance verification of the FlashCam prototype camera for the Cherenkov Telescope Array - Werner, F.; Bauer, C.; Bernhard, S.; Capasso, M.; Diebold, S.; Eisenkolb, F.; Eschbach, Stefan; Florin, D.; Foehr, C.; Funk, Stefan; Gadola, A.; Garrecht, F.; et al. (ELSEVIER SCIENCE BV, 2017)
The Cherenkov Telescope Array (CTA) is a future gamma-ray observatory that is planned to significantly improve upon the sensitivity and precision of the current generation of Cherenkov telescopes. The observatory will consist of several dozens of telescopes with different sizes and equipped with different types of cameras. Of these, the FlashCam camera system is the first to implement a fully digital signal processing chain which allows for a traceable, configurable trigger scheme and flexible signal reconstruction. As of autumn 2016, a prototype FlashCam camera for the medium-sized telescopes of CTA nears completion. First results of the ongoing system tests demonstrate that the signal chain and the readout system surpass CTA requirements. The stability of the system is shown using long-term temperature cycling.
Keywords: Gamma-ray astronomy; Cherenkov camera; Performance verification; Temperature stability; CTA; MST; FlashCam

Personal Dosimetry in Continuous Photon Radiation Fields with the Dosepix Detector - Haag, Dennis; Schmidt, Sebastian; Hufschmidt, Patrick; Eberle, Franziska; Michel, Thilo; Anton, Gisela; Hupe, Oliver; Roth, Jurgen; Fuhg, Christian; Zutz, Hayo; Behrens, Rolf; Campbell, Michael; et al. (IEEE Transactions on Nuclear Science, 2021)
First measurements characterizing dosimetric properties of a dosimetry system designed for the purpose of active personal dosimetry for photons with mean energies from 12.4 keV to 1250 keV according to PTB requirements are presented. The system consists of three Dosepix detectors, which is a hybrid, pixelated, photon-counting X-ray detector. The energy and angular dependence of the normalized response and the coefficients of variation of the personal dose equivalents Hp(10) and Hp(0.07) are determined on an ISO water slab phantom in continuous reference photon radiation fields according to ISO 4037-1 and ISO 4037-3. The energy response is presented for the narrow spectra N-15 to N-300 and the radiation qualities S-Cs and S-Co for angles of incidence of 0 °, 30 ° and ±60 °. The highest deviation of the response from the reference response is found at N-60, -60 ° with 1.179±0.007 (standard deviation) for Hp(10). The energy range of use for Hp(10) is expected to extend from 12.4 keV to 1250 keV. For the personal dose equivalent Hp(0.07) the normalized response at ±60 ° is below the lower limit for N-15, N-20 and N-25. It results in an energy range of use from 24.6 keV to 1250 keV. The coefficient of variation increases with increasing photon energy and stays below 1% for all measurements.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Active personal dosimetry; Aluminum; Detectors; Dosimetry; dosimetry with ionizing radiation; hybrid pixel detector; ISO Standards; Phantoms; Photonics; Uncertainty

Photomultipliers for the KM3NeT optical modules - Kalekin, Oleg; Steijger, J. J. M.; Peek, H. Z. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2012)
Keywords: Neutrino telescope; KM3NeT; PMT; Photomultiplier tube

PMT characterisation for the KM3NeT project - Herold, Björn; Kalekin, Oleg (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2011)
Keywords: High energy neutrino detection; Cherenkov light; Photomultiplier; KM3NeT

PMT characterisation for the KM3NeT project - Herold, Björn; Kalekin, Oleg; Reubelt, Jonas (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2011)
Keywords: Cherenkov light; KM3NeT; High energy neutrino detection; Photomultiplier

PMT measurements in Antares - Creusot, Alexandre; Kalekin, Oleg; Kulikovskiy, Vladimir; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2013)
Keywords: Neutrino telescope; Antares; Photomultiplier tube; Optical module; PMT

Polarization Reconstruction of Cosmic Rays with the ARIANNA Neutrino Radio Detector - Zhao, Leshan; Anker, Astrid; Baldi, Pierre; Barwick, Steven W.; Beise, Jakob; Bernhoff, Hans; Besson, Dave Z.; Bingefors, Nils; Cataldo, Maddalena; Chen, Pisin; Fernández, Daniel García; Gaswint, Geoffrey; et al. (Proceedings of Science, 2022)
The ARIANNA detector is designed to detect neutrinos of energies above 1016 eV. Due to the similarities in generated radio signals, cosmic rays are often used as test beams for neutrino detectors. Some ARIANNA detector stations are equipped with antennas capable of detecting air showers. The radio emission properties of air showers are well understood, and the polarization of the radio signal can be predicted from arrival direction with high precision. For this reason, cosmic rays can be used as a proxy to assess the reconstruction capabilities of the ARIANNA neutrino detector. We report on dedicated efforts of reconstructing the polarization of cosmic-ray radio pulses. A total of 148 cosmic rays are identified from over 90,000 triggered events collected between Nov 21, 2018 and Mar 15, 2019. A cut was put on these events requiring them to have a signal-to-noise (SNR) ratio of at least 4.5 in all upward-facing channels. This was to improve the performance of arrival direction and polarization reconstruction algorithms. Polarization of these cosmic rays were reconstructed with a resolution of 3.5 degrees (68% containment), which agrees with the expected value we obtained from simulation. Furthermore, if we subselect events with zenith angle greater than 70 deg, the contribution to polarization of Askaryan effect is reduced, which reduces the error in the predicted polarization. With limited statistics, we find the polarization uncertainty is reduced to 1.3 deg (68% containment).
CRIS-Team Scopus Importer:2023-08-15

Probing the Magnetic Field in the GW170817 Outflow Using HESS Observations - Abdalla, H.; Adam, R.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Baghmanyan,; et al. (Astrophysical Journal Letters, 2020)
The detection of the first electromagnetic counterpart to the binary neutron star (BNS) merger remnant GW170817 established the connection between short gamma-ray bursts and BNS mergers. It also confirmed the forging of heavy elements in the ejecta (a so-called kilonova) via the r-process nucleosynthesis. The appearance of nonthermal radio and X-ray emission, as well as the brightening, which lasted more than 100 days, were somewhat unexpected. Current theoretical models attempt to explain this temporal behavior as either originating from a relativistic off-axis jet or a kilonova-like outflow. In either scenario, there is some ambiguity regarding how much energy is transported in the nonthermal electrons versus the magnetic field of the emission region. Combining the Very Large Array (radio) and Chandra (X-ray) measurements with observations in the GeV-TeV domain can help break this ambiguity, almost independently of the assumed origin of the emission. Here we report for the first time on deep H.E.S.S. observations of GW170817/GRB 170817A between 124 and 272 days after the BNS merger with the full H.E.S.S. array of telescopes, as well as on an updated analysis of the prompt (<5 days) observations with the upgraded H.E.S.S. phase-I telescopes. We discuss implications of the H.E.S.S. measurement for the magnetic field in the context of different source scenarios.
CRIS-Team WoS Importer:2020-05-29

Radiation measurements and simulations at the PHELIX laser facility, GSI - Behrens, R.; Hufschmidt, Patrick; Roth, J.; Akstaller, Bernhard; Hupe, O.; Haag, D.; Schmidt, Sebastian; Schreiner, Stephan; Michel, Thilo (Journal of Instrumentation, 2022)
The absolute spectral electron and photon emission from a Tungsten target irradiated by the Petawatt High-Energy Laser for Heavy Ion EXperiments (PHELIX) facility was measured inside the PHELIX target chamber. For this, a thermo-lumi-nescence detector (TLD)-based few-channel spectrometer (FCS) was used in combination with a Bayesian data analysis. The results of the FCS measurement served as input for a Monte-Carlo particle transport simulation to determine the spectra and dose out of the PHELIX target chamber. Two different simulation methods proved to be consistent and, therefore, reliable. The simulation results were compared to the dose measured with a dosemeter that consists of three Dosepix detectors in combination with a neural network analysis. The two dose results show a satisfactory agreement.
CRIS-Team WoS Importer:2022-06-10

Readout electronics testing during mass production of FlashCam cameras for the Cherenkov Telescope Array - Diebold, S.; Barcelo, M.; Bauer, C.; Bernhard, S.; Biegger, M.; Capasso, M.; Eisenkolb, F.; Eschbach, Stefan; Florin, D.; Foehr, C.; Funk, Stefan; Gadola, A.; et al. (OPTICS FOR EUV, X-RAY, AND GAMMA-RAY ASTRONOMY VIII, 2017)
CRIS-Team WoS Importer:2020-01-15

Recent results from the High Altitude Water Cherenkov Observatory - Mostafá, Miguel; Albert, A.; Alfaro, R.; Alvarez, C.; Andrés, A.; Arteaga-Velázquez, J. C.; Avila Rojas, D.; Ayala Solares, H. A.; Babu, R.; Belmont-Moreno, E.; Caballero-Mora, K. S.; Capistrán, T.; et al. (Proceedings of Science, 2024)
High energy γ-ray observations are an essential probe of cosmic-ray acceleration mechanisms. The detection of the highest energy γ rays and the shortest timescales of variability are the key to improve our understanding of the acceleration processes and the environment of the cosmic accelerators. The High Altitude Water Cherenkov (HAWC) experiment is a large field-of-view, multi-TeV, γ-ray observatory continuously operating at 4100 m a.s.l. since March, 2015. The HAWC observatory has an order of magnitude better sensitivity, angular resolution, and background rejection than the previous generation of water-Cherenkov arrays. The improved performance allows us to discover new TeV sources, to detect transient events, to study the Galactic diffuse emission at TeV energies, to measure or constrain the TeV spectra of GeV γ-ray sources, to search for Galactic Pevatrons, and to improve the upper limits on indirect searches for dark matter and the constrains on Lorentz invariance violation. In this contribution I summarize the most recent results from the HAWC observatory using the latest reconstruction algorithm (Pass 5 production) and I discuss their implications for cosmic-ray acceleration and propagation.
CRIS-Team Scopus Importer:2025-02-04

Reflectance of Silicon Photomultipliers at Vacuum Ultraviolet Wavelengths - Lv, P.; Cao, G. F.; Wen, L. J.; Kharusi, S. Al; Anton, Gisela; Arnquist, I. J.; Badhrees, I.; Barbeau, P. S.; Beck, D.; Belov, V.; Bhatta, T.; Breur, P. A.; et al. (IEEE Transactions on Nuclear Science, 2020)
Characterization of the vacuum ultraviolet (VUV) reflectance of silicon photomultipliers (SiPMs) is important for large-scale SiPM-based photodetector systems. We report the angular dependence of the specular reflectance in vacuum of SiPMs manufactured by Fondazionc Bruno Kessler (FBK) and Hamamatsu Photonics K.K. (HPK) over wavelengths ranging from 120 to 280 nm. Refractive index and extinction coefficient of the thin silicon-dioxide film deposited on the surface of the FBK SiPMs are derived from reflectance data of an FBK silicon wafer with the same deposited oxide film as SiPMs. The diffuse reflectance of SiPMs is also measured at 193 nm. We use the VUV spectral dependence of the optical constants to predict the reflectance of the FBK silicon wafer and FBK SiPMs in liquid xenon.
CRIS-Team WoS Importer:2021-01-01

Reflectance of VUV-sensitive SiPM surfaces in liquid xenon - Wagenpfeil, Michael; Ziegler, Tobias; Fieguth, Alexander; Schneider, Judith; Michel, Thilo; Weinheimer, Christian (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2019)
The nEXO experiment will operate an ultra-low background time projection chamber filled with 5t of isotopically enriched liquid xenon (LXe) for the search for the neutrinoless double beta decay in Xe-136. The detector will use 4m2 of silicon photomultipliers (SiPMs) operated at about −104∘C to collect the scintillation light. There are strong requirements on the background levels, light collection efficiency and SiPM performance to set the most stringent limits on the half-life. Detecting the 0νββ-decay would have wide-spread implications for neutrino physics. The SiPMs need to be sensitive to the vacuum-ultraviolet scintillation light of LXe at 178nm which is not given for off-the-shelf SiPMs. The SiPM performance requirements adopted by nEXO are (among others) a photon detection efficiency of at least 15% at 178nm, a correlated avalanche probability of less than 20% and a low dark-rate. Additionally, the VUV-reflectance of the SiPM surface in LXe is an important parameter for optimal light collection and thus the energy resolution of nEXO. We present measurements with state-of-the-art VUV-sensitive SiPMs focusing on the surface VUV-reflectance in liquid xenon.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Liquid xenon; Reflectance; Silicon photomultipliers; VUV-sensitive

Reflectivity and PDE of VUV4 Hamamatsu SiPMs in liquid xenon - Nakarmi, P.; Ostrovskiy, I.; Soma, A. K.; Retière, F.; Kharusi, S. Al; Alfaris, M.; Anton, Gisela; Arnquist, I. J.; Badhrees, I.; Barbeau, P. S.; Beck, D.; Belov, V.; et al. (Journal of Instrumentation, 2020)
Understanding reflective properties of materials and photodetection efficiency (PDE) of photodetectors is important for optimizing energy resolution and sensitivity of the next generation neutrinoless double beta decay, direct detection dark matter, and neutrino oscillation experiments that will use noble liquid gases, such as nEXO, DARWIN, DarkSide-20k, and DUNE . Little information is currently available about reflectivity and PDE in liquid noble gases, because such measurements are difficult to conduct in a cryogenic environment and at short enough wavelengths. Here we report a measurement of specular reflectivity and relative PDE of Hamamatsu VUV4 silicon photomultipliers (SiPMs) with 50 μm micro-cells conducted with xenon scintillation light (∼175 nm) in liquid xenon. The specular reflectivity at 15ˆ incidence of three samples of VUV4 SiPMs is found to be 30.4±1.4%, 28.6±1.3%, and 28.0±1.3%, respectively. The PDE at normal incidence differs by ±8% (standard deviation) among the three devices. The angular dependence of the reflectivity and PDE was also measured for one of the SiPMs. Both the reflectivity and PDE decrease as the angle of incidence increases. This is the first measurement of an angular dependence of PDE and reflectivity of a SiPM in liquid xenon.
CRIS-Team Scopus Importer:2020-03-31
Keywords: Dark Matter detectors (WIMPs; axions; etc.); Double-beta decay detectors; Noble liquid detectors (scintillation; ionization; double-phase); Photon detectors for UV; visible and IR photons (solid-state) (PIN diodes; APDs; Si-PMTs; G-APDs; CCDs; EBCCDs; EMCCDs; CMOS imagers; etc)

Refraction in a Talbot-Lau setup allows High Energy, Visibility, and Sensitivity - Preusche, Oliver; Weber, Thomas; Anton, Gisela (International Symposium on BioMedical Applications of X-Ray Phase Contrast Imaging (IMXP 2014), 2015)
Photon energies above 50 keV are rarely used in Talbot-Lau interferometers, because the analyzer grating G2 becomes quite transparent at higher photon energies [1-4]. For medical imaging, this transparency causes an inacceptable increase in radiation dose. To allow higher energies, several proposals exist to allow higher gold gratings: Edge-on illumination [2] strongly reduces the field-of-view, glancing angle geometry [3] may increase setup length, and phase gratings consisting of alternating prisms [4] reduce angular sensitivity. In this work, we present a further new proposal to solve the aspect ratio problem. Method: The basic idea is to use a refracting lens to combine N>1 fringes into a single fringe (see Fig. 1). An array of such lenses (called 'lens grating') replaces the analyzer grating G2. A new G2 (the period now is N times larger) is put into the focal plane of the lens-array. To this end, several problems have to be solved. Problem 1 – Refraction strongly depends on photon energy. Since G2 is now coarse, the refraction angle is allowed to change by a factor of 3. Problem 2 – Production of strong prisms for a fresnel-style lens. [4] inclines the light source during lithography by rotation around a grating bar (around the y-axis), this delivers strong alternating prisms. We incline by rotating within a grating bar (around the x-axis) and use a y-periodic contract in the grating layout to produce differently strong prisms – this allows to encode a complete fresnel lens in a simple binary layout. Problem 3 – The lenses must analyze the fringe phase. To do so, two arrays of fresnel lenses are interleaved into each other. The even lenses (black) focus on G2 grating bars, the odd lenses (magenta) focus on G2 grating slits. Problem 4 – This does not work with a regular source grating G0. An additional coherence constraint defines a set of planes in which G2 can be placed. Also required is a grouping: In each group of Q slits, only q < Q/2 slits may stay open – we need hierarchical coherence in the form of a darker G0 (see orange lines in Fig. 1). The resulting setup allows analyzer grating periods as large as in the source grating G0. A lens grating may consist of very narrow strips, allowing higher angular sensitivities (refraction is proportional to aspect ratio). Results: We present simulation results of a setup of 180 mm post-patient length for a design energy of 59 keV. The setup uses a modified binary phase grating G1 to operate in second talbot order. This increases sensitivity. The lens grating has a strip width of 0.9 µm ('period' 1.8 µm) and a gold height of 54 µm (aspect ratio 73). It combines 5 fringes to one, resulting in a period of 9.3 µm for G2. The simulation (see Fig. 2) is based on Fresnel-Kirchhoff diffraction. It shows that the lens grating keeps 92% of the visibility created by the first two gratings. Conclusion: The proposal solves the height-problem in the analyzer grating G2. However, G0 will become the critical component of the setup, because of the additional coherence requirements. One option to solve this might be the combination with the glacing angle [3] approach. References: [1] T. Donath, F. Pfeiffer, O. Bunk, W. Groot, M. Bednarzik, C. Grünzweig, E. Hempel, S. Popescu, M. Hoheisel and C. David, "Phase-contrast imaging and tomography at 60 keV using a conventional x-ray tube source", Review of Scientific Instruments 80, 053701 (2009), DOI 10.1063/1.3127712 [2] T. Thüring, M. Abis, Z. Wang, C. David, and M. Stampanoni, "X-ray phase-contrast imaging at 100 keV on a conventional source", Scientific Reports 4 : 5198 (2014), DOI: 10.1038/srep05198 [3] A. Sarapata, J. W. Stayman, M. Finkenthal, J. H. Siewerdsen, F. Pfeiffer, and D. Stutman, "High energy x-ray phase contrast CT using glancing-angle grating interferometers", Med Phys. Feb 2014; 41(2): 021904, Doi: 10.1118/1.4860275 [4] A. Yaroshenko, M. Bech, G. Potdevin, A. Malecki, T. Biernath, J. Wolf, A. Tapfer, M. Schüttler, J. Meiser, D. Kunka, M. Amberger, J. Mohr, and F. Pfeiffer, "Non-binary phase gratings for x-ray imaging with a compact Talbot interferometer," Opt. Express 22, 547-556 (2014), Doi: 10.1364/OE.22.000547</
Keywords: X-ray interferometry; gratings; talbot-lau interferometer; x-ray lenses

Results from the search for dark matter in the Milky Way with 9 years of data of the ANTARES neutrino telescope - Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; Aubert, J. J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Physics Letters B, 2017)
Using data recorded with the ANTARES telescope from 2007 to 2015, a new search for dark matter annihilation in the Milky Way has been performed. Three halo models and five annihilation channels, WIMP + WIMP -> b (b) over bar, W+W-, tau(+)tau(-), mu(+)mu(-) and v (v) over bar, with WIMP masses ranging from 50 2 GeV/C-2 to 100 Tev/C-2, were considered. No excess over the expected background was found, and limits on the thermally averaged annihilation cross-section were set. (C) 2017 The Authors. Published by Elsevier B.V. This is an open access article under the CC BY license.
Keywords: Dark matter; WIMP; Indirect detection; Neutrino telescope; Galactic Centre; ANTARES

Science Case and Detector Concept for the ARIANNA High Energy Neutrino Telescope at Moore’s Bay, Antarctica - Barwick, Steven W.; Anker, Astrid; Baldi, Pierre; Beise, Jakob; Bernhoff, Hans; Besson, Dave Z.; Bingefors, Nils; Cataldo, Maddalena; Chen, Pisin; Fernández, Daniel García; Gaswint, Geoffrey; Glaser, Christian; et al. (Proceedings of Science, 2022)
The ARIANNA neutrino detector, located at sea-level on the Ross Ice Shelf, Antarctica, consists of 200 autonomous and independent detector stations separated by 1 kilometer in a uniform triangular mesh, and serves to inform the planning of the future projects. The primary science mission of ARIANNA is to search for sources of neutrinos with energies greater than 1017 eV, complementing the reach of IceCube and other neutrino telescopes that focus on lower energies. An ARIANNA observation of a neutrino source would provide strong insight into the enigmatic sources of cosmic rays. ARIANNA observes the radio emission from high energy neutrino interactions in the Antarctic ice. Among radio based concepts under current investigation, ARIANNA would uniquely survey the vast majority of the southern sky at any instant in time, and an important region of the northern sky, by virtue of its location on the surface of the Ross Ice Shelf at Moore’s Bay. The broad sky coverage is specific to the Moore’s Bay site, providing capabilities to observe explosive sources from unknown directions. The ARIANNA architecture is designed to measure the angular direction to within 4 degrees for every neutrino candidate, which too plays an important role in the pursuit of multi-messenger observations of astrophysical sources. The sea level location reduces the impact of a potentially serious background associated with the cores of cosmic ray air showers striking the ice surface, generating radio pulses which are similar to those expected from neutrino events. Reflecting layers at the bottom or within the ice sheet (which are known to exist in thick ice sheets) might create a troublesome rate of background events, provided the reflection coefficients are large enough, that arrive at the detector from the same directions as neutrinos.
CRIS-Team Scopus Importer:2023-08-15
Keywords: Cosmic rays; Cosmology; Glaciers; Ice; Neutrons; Particle detectors; Telescopes

Searches for clustering in the time integrated skymap of the ANTARES neutrino telescope - Adrian-Martinez, S.; Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; Bogazzi, C.; et al. (Journal of Cosmology and Astroparticle Physics, 2014)
This paper reports a search for spatial clustering of the arrival directions of high energy muon neutrinos detected by the ANTARES neutrino telescope. An improved two-point correlation method is used to study the autocorrelation of 3058 neutrino candidate events as well as cross-correlations with other classes of astrophysical objects: sources of high energy gamma rays, massive black holes and nearby galaxies. No significant deviations from the isotropic distribution of arrival directions expected from atmospheric backgrounds are observed.
Keywords: neutrino astronomy; neutrino detectors

Searches for gamma-ray lines and 'pure WIMP' spectra from Dark Matter annihilations in dwarf galaxies with HESS - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, Michael; Barnard, Monica; Becherini, Y.; Tjus, J. Becker; et al. (Journal of Cosmology and Astroparticle Physics, 2018)
Dwarf spheroidal galaxies are among the most promising targets for detecting signals of Dark Matter (DM) annihilations. The H.E.S.S. experiment has observed five of these systems for a total of about 130 hours. The data are re-analyzed here, and, in the absence of any detected signals, are interpreted in terms of limits on the DM annihilation cross section. Two scenarios are considered: i) DM annihilation into mono-energetic gamma-rays and ii) DM in the form of pure WIMP multiplets that, annihilating into all electroweak bosons, produce a distinctive gamma-ray spectral shape with a high-energy peak at the DM mass and a lower-energy continuum. For case i), upper limits at 95% confidence level of about less than or similar to 3 x 10(-25) cm(3) s(-1) are obtained in the mass range of 400 GeV to 1TeV. For case ii), the full spectral shape of the models is used and several excluded regions are identified, but the thermal masses of the candidates are not robustly ruled out.
CRIS-Team WoS Importer:2020-01-15

SEARCHES FOR POINT-LIKE AND EXTENDED NEUTRINO SOURCES CLOSE TO THE GALACTIC CENTER USING THE ANTARES NEUTRINO TELESCOPE - Adrian-Martinez, S.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; Aubert, J-J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Astrophysical Journal Letters, 2014)
A search for cosmic neutrino sources using six years of data collected by the ANTARES neutrino telescope has been performed. Clusters of muon neutrinos over the expected atmospheric background have been looked for. No clear signal has been found. The most signal-like accumulation of events is located at equatorial coordinates R.A. = -46 degrees.8 and decl. = -64 degrees.9 and corresponds to a 2.2 sigma background fluctuation. In addition, upper limits on the flux normalization of an E-2 muon neutrino energy spectrum have been set for 50 pre-selected astrophysical objects. Finally, motivated by an accumulation of seven events relatively close to the Galactic Center in the recently reported neutrino sample of the IceCube telescope, a search for point sources in a broad region around this accumulation has been carried out. No indication of a neutrino signal has been found in the ANTARES data and upper limits on the flux normalization of an E-2 energy spectrum of neutrinos from point sources in that region have been set. The 90% confidence level upper limits on the muon neutrino flux normalization vary between 3.5 and 5.1 x 10(-8) GeV cm(-2) s(-1), depending on the exact location of the source.
Keywords: astroparticle physics; Galaxy: center; neutrinos

SEARCH FOR A CORRELATION BETWEEN ANTARES NEUTRINOS AND PIERRE AUGER OBSERVATORY UHECRs ARRIVAL DIRECTIONS - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J.; Baret, B.; Basa, S.; et al. (Astrophysical Journal, 2013)
A multimessenger analysis optimized for a correlation of arrival directions of ultra-high energy cosmic rays (UHECRs) and neutrinos is presented and applied to 2190 neutrino candidate events detected in 2007-2008 by the ANTARES telescope and 69 UHECRs observed by the Pierre Auger Observatory between 2004 January 1 and 2009 December 31. No significant correlation is observed. Assuming an equal neutrino flux (E-2 energy spectrum) from all UHECR directions, a 90% CL upper limit on the neutrino flux of 5.0 x 10(-8) GeV cm(-2) s(-1) per source is derived.
Keywords: astroparticle physics; cosmic rays; neutrinos

Search for correlations between the arrival directions of IceCube neutrino events and ultrahigh-energy cosmic rays detected by the Pierre Auger Observatory and the Telescope Array - Aartsen, M. G.; Abraham, K.; Ackermann, Markus; Adams, J.; Aguilar, J. A.; Ahlers, Markus; Ahrens, M.; Altmann, D.; Anderson, T.; Ansseau, I.; Archinger, M.; Arguelles, C.; et al. (Journal of Cosmology and Astroparticle Physics, 2016)
This paper presents the results of different searches for correlations between very high-energy neutrino candidates detected by IceCube and the highest-energy cosmic rays measured by the Pierre Auger Observatory and the Telescope Array. We first consider samples of cascade neutrino events and of high-energy neutrino-induced muon tracks, which provided evidence for a neutrino flux of astrophysical origin, and study their cross-correlation with the ultrahigh-energy cosmic ray (UHECR) samples as a function of angular separation. We also study their possible directional correlations using a likelihood method stacking the neutrino arrival directions and adopting different assumptions on the size of the UHECR magnetic deflections. Finally, we perform another likelihood analysis stacking the UHECR directions and using a sample of through-going muon tracks optimized for neutrino point-source searches with sub-degree angular resolution. No indications of correlations at discovery level are obtained for any of the searches performed. The smallest of the p-values comes from the search for correlation between UHECRs with IceCube high-energy cascades, a result that should continue to be monitored.
Keywords: neutrino experiments; ultra high energy cosmic rays; cosmic ray experiments; neutrino astronomy

SEARCH FOR COSMIC NEUTRINO POINT SOURCES WITH FOUR YEARS OF DATA FROM THE ANTARES TELESCOPE - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J; Baret, B.; Basa, S.; et al. (Astrophysical Journal, 2012)
In this paper, a time-integrated search for point sources of cosmic neutrinos is presented using the data collected from 2007 to 2010 by the ANTARES neutrino telescope. No statistically significant signal has been found and upper limits on the neutrino flux have been obtained. Assuming an E-nu(-2). spectrum, these flux limits are at 1-10x10(-8) GeV cm(-2) s(-1) for declinations ranging from -90 degrees to 40 degrees. Limits for specific models of RX J1713.7-3946 and Vela X, which include information on the source morphology and spectrum, are also given.
Keywords: astroparticle physics; cosmic rays; neutrinos

Search for dark matter annihilation in the earth using the ANTARES neutrino telescope - Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Physics of the Dark Universe, 2017)
A search for a neutrino signal from WIMP pair annihilations in the centre of the Earth has been performed with the data collected with the ANTARES neutrino telescope from 2007 to 2012. The event selection criteria have been developed and tuned to maximise the sensitivity of the experiment to such a neutrino signal. No significant excess of neutrinos over the expected background has been observed. Upper limits at 90% C.L. on the WIMP annihilation rate in the Earth and the spin independent scattering cross-section of WIMPs to nucleons sigma(SI)(p) were calculated for WIMP pair annihilations into either iota(+) iota(-), W+W-, b (b) over bar or the non-SUSY v mu(v) over bar as a function of the WIMP mass (between 25 GeV/c(2) and 1000 GeV/c(2)) and as a function of the thermally averaged annihilation cross section times velocity (Earth) of the WIMPs in the centre of the Earth. For masses of the WIMP close to the mass of iron nuclei (50 GeV/c(2)), the obtained limits on sigma(SI)(p) are more stringent than those obtained by other indirect searches. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Dark matter; Neutrino telescope; ANTARES; Indirect detection; WIMP

Search for Dark Matter Annihilation Signals from Unidentified Fermi-LAT Objects with HESS - Abdalla, H.; Spencer, Samuel; Aharonian, Felix; Ait Benkhali, F.; Anguner, E. O.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Baghmanyan, V.; Barbosa-Martins, V.; et al. (Astrophysical Journal, 2021)
Cosmological N-body simulations show that Milky Way-sized galaxies harbor a population of unmerged dark matter (DM) subhalos. These subhalos could shine in gamma-rays and eventually be detected in gamma-ray surveys as unidentified sources. We performed a thorough selection among unidentified Fermi-Large Area Telescope Objects (UFOs) to identify them as possible tera-electron-volt-scale DM subhalo candidates. We search for very-high-energy (E greater than or similar to 100 GeV) gamma-ray emissions using H.E.S.S. observations toward four selected UFOs. Since no significant very-high-energy gamma-ray emission is detected in any data set of the four observed UFOs or in the combined UFO data set, strong constraints are derived on the product of the velocity-weighted annihilation cross section sigma v by the J factor for the DM models. The 95% confidence level observed upper limits derived from combined H.E.S.S. observations reach sigma vJ values of 3.7 x 10(-5) and 8.1 x 10(-6) GeV(2 )cm(-2 )s(-1) in the W (+) W (-) and tau (+) tau (-) channels, respectively, for a 1 TeV DM mass. Focusing on thermal weakly interacting massive particles, the H.E.S.S. constraints restrict the J factors to lie in the range 6.1 x 10(19)-2.0 x 10(21) GeV(2 )cm(-5) and the masses to lie between 0.2 and 6 TeV in the W (+) W (-) channel. For the tau (+) tau (-) channel, the J factors lie in the range 7.0 x 10(19)-7.1 x 10(20) GeV(2 )cm(-5) and the masses lie between 0.2 and 0.5 TeV. Assuming model-dependent predictions from cosmological N-body simulations on the J-factor distribution for Milky Way-sized galaxies, the DM models with masses >0.3 TeV for the UFO emissions can be ruled out at high confidence level.
CRIS-Team WoS Importer:2021-09-10

Search for dark matter signals towards a selection of recently detected DES dwarf galaxy satellites of the Milky Way with HESS - Abdallah, H.; Adam, R.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Baghmanyan,; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2020)
Dwarf spheroidal galaxy satellites of the Milky Way are prime targets for indirect detection of dark matter with gamma rays due to their proximity, high dark matter content, and absence of nonthermal emission processes. Recently, the Dark Energy Survey (DES) revealed the existence of new ultrafaint dwarf spheroidal galaxies in the southern-hemisphere sky, therefore ideally located for ground-based observations with the imaging atmospheric Cherenkov telescope array H.E.S.S. We present a search for very-high-energy (E greater than or similar to 100 GeV) gamma-ray emission using H.E.S.S. observations carried out recently towards Reticulum II, Tucana II, Tucana III, Tucana IV, and Grus II satellites. No significant very-high-energy gamma-ray excess is found from the observations on any individual object nor in the combined analysis of all the datasets. Using the most recent modeling of the dark matter distribution in the dwarf galaxy halo, we compute for the first time on DES satellites individual and combined constraints from Cherenkov telescope observations on the annihilation cross section of dark matter particles in the form of Weakly Interacting Massive Particles. The combined 95% C.L. observed upper limits reach similar or equal to 1 x 10(-23) cm(3) s(-1) in the W+W- channel and 4 x 10(-26) cm(3) s(-1) in the gamma gamma channels for a dark matter mass of 1.5 TeV. The H.E.S.S. constraints well complement the results from Fermi-LAT, HAWC, MAGIC, and VERITAS and are currently the most stringent in the gamma gamma channels in the multi-GeV/multi-TeV mass range.
CRIS-Team WoS Importer:2020-09-18

Search for dark matter towards the Galactic Centre with 11 years of ANTARES data - Albert, A.; André, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin, V.; Biagi, S.; et al. (Physics Letters B, 2020)
Neutrino detectors participate in the indirect search for the fundamental constituents of dark matter (DM) in form of weakly interacting massive particles (WIMPs). In WIMP scenarios, candidate DM particles can pair-annihilate into Standard Model products, yielding considerable fluxes of high-energy neutrinos. A detector like ANTARES, located in the Northern Hemisphere, is able to perform a complementary search looking towards the Galactic Centre, where a high density of dark matter is thought to accumulate. Both this directional information and the spectral features of annihilating DM pairs are entered into an unbinned likelihood method to scan the data set in search for DM-like signals in ANTARES data. Results obtained upon unblinding 3170 days of data reconstructed with updated methods are presented, which provides a larger, and more accurate, data set than a previously published result using 2101 days. A non-observation of dark matter is converted into limits on the velocity-averaged cross section for WIMP pair annihilation.
CRIS-Team Scopus Importer:2020-05-12
Keywords: ANTARES; Dark matter indirect detection; Galactic Centre; Neutrino telescope

Search for gamma-Ray Line Signals from Dark Matter Annihilations in the Inner Galactic Halo from 10 Years of Observations with HESS - Abdallah, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; Becherini, Y.; et al. (Physical Review Letters, 2018)
Spectral lines are among the most powerful signatures for dark matter (DM) annihilation searches in very-high-energy gamma rays. The central region of the Milky Way halo is one of the most promising targets given its large amount of DM and proximity to Earth. We report on a search for a monoenergetic spectral line from self-annihilations of DM particles in the energy range from 300 GeV to 70 TeV using a two-dimensional maximum likelihood method taking advantage of both the spectral and spatial features of the signal versus background. The analysis makes use of Galactic center observations accumulated over ten years (2004-2014) with the H.E.S.S. array of ground-based Cherenkov telescopes. No significant gamma-ray excess above the background is found. We derive upper limits on the annihilation cross section (sigma v) for monoenergetic DM lines at the level of 4 x 10(-28) cm(3) s(-1) at 1 TeV, assuming an Einasto DM profile for the Milky Way halo. For a DM mass of 1 TeV, they improve over the previous ones by a factor of 6. The present constraints are the strongest obtained so far for DM particles in the mass range 300 GeV-70 TeV. Ground-based gamma-ray observations have reached sufficient sensitivity to explore relevant velocity-averaged cross sections for DM annihilation into two gamma-ray photons at the level expected from the thermal relic density for TeV DM particles.

Search for High-energy Neutrinos from Binary Neutron Star Merger GW170817 with ANTARES, IceCube, and the Pierre Auger Observatory - Albert, A.; Andre, M.; Anghinolfi, M.; Ardid, M.; Aubert, J. -J.; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin, V.; et al. (Astrophysical Journal Letters, 2017)
The Advanced LIGO and Advanced Virgo observatories recently discovered gravitational waves from a binary neutron star inspiral. A short gamma-ray burst (GRB) that followed the merger of this binary was also recorded by the Fermi Gamma-ray Burst Monitor (Fermi-GBM), and the Anti-Coincidence Shield for the Spectrometer for the International Gamma-Ray Astrophysics Laboratory (INTEGRAL), indicating particle acceleration by the source. The precise location of the event was determined by optical detections of emission following the merger. We searched for high-energy neutrinos from the merger in the GeV-EeV energy range using the ANTARES, IceCube, and Pierre Auger Observatories. No neutrinos directionally coincident with the source were detected within +/- 500 s around the merger time. Additionally, no MeV neutrino burst signal was detected coincident with the merger. We further carried out an extended search in the direction of the source for high-energy neutrinos within the 14 day period following the merger, but found no evidence of emission. We used these results to probe dissipation mechanisms in relativistic outflows driven by the binary neutron star merger. The non-detection is consistent with model predictions of short GRBs observed at a large off-axis angle.
Keywords: gamma-ray burst: general; gravitational waves; neutrinos

Search for high-energy neutrinos from bright GRBs with ANTARES - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Monthly Notices of the Royal Astronomical Society, 2017)
Gamma-ray bursts are thought to be sites of hadronic acceleration, thus neutrinos are expected from the decay of charged particles, produced in p gamma interactions. The methods and results of a search for muon neutrinos in the data of the ANTARES neutrino telescope from four bright GRBs (GRB 080916C, GRB 110918A, GRB 130427A and GRB 130505A) observed between 2008 and 2013 are presented. Two scenarios of the fireball model have been investigated: the internal shock scenario, leading to the production of neutrinos with energies mainly above 100 TeV, and the photospheric scenario, characterized by a low-energy component in neutrino spectra due to the assumption of neutrino production closer to the central engine. Since no neutrino events have been detected in temporal and spatial coincidence with these bursts, upper limits at 90 per cent confidence level on the expected neutrino fluxes are derived. The non-detection allows for directly constraining the bulk Lorentz factor of the jet Gamma and the baryon loading f(p).
Keywords: acceleration of particles; neutrinos; gamma-ray burst: individual: GRB 080916C; gamma-ray burst: individual: GRB 110918A; gamma-ray burst: individual: GRB 130427A; gamma-ray burst: individual: GRB 130505A

Search for high-energy neutrinos from gravitational wave event GW151226 and candidate LVT151012 with ANTARES and IceCube - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2017)
The Advanced LIGO observatories detected gravitational waves from two binary black hole mergers during their first observation run (O1). We present a high-energy neutrino follow-up search for the second gravitational wave event, GW151226, as well as for gravitational wave candidate LVT151012. We find two and four neutrino candidates detected by IceCube, and one and zero detected by ANTARES, within +/- 500 s around the respective gravitational wave signals, consistent with the expected background rate. None of these neutrino candidates are found to be directionally coincident with GW151226 or LVT151012. We use nondetection to constrain isotropic-equivalent high-energy neutrino emission from GW151226, adopting the GW event's 3D localization, to less than 2 x 10(51)-2 x 10(54) erg.

Search for Multimessenger Sources of Gravitational Waves and High-energy Neutrinos with Advanced LIGO during Its First Observing Run, ANTARES, and IceCube - Albert, A.; Andre, M.; Anghinolfi, M.; Ardid, M.; Aubert, J-J; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin,; et al. (Astrophysical Journal, 2019)
Astrophysical sources of gravitational waves, such as binary neutron star and black hole mergers or core-collapse supernovae, can drive relativistic outflows, giving rise to non-thermal high-energy emission. High-energy neutrinos are signatures of such outflows. The detection of gravitational waves and high-energy neutrinos from common sources could help establish the connection between the dynamics of the progenitor and the properties of the outflow. We searched for associated emission of gravitational waves and high-energy neutrinos from astrophysical transients with minimal assumptions using data from Advanced LIGO from its first observing run O1, and data from the ANTARES and IceCube neutrino observatories from the same time period. We focused on candidate events whose astrophysical origins could not be determined from a single messenger. We found no significant coincident candidate, which we used to constrain the rate density of astrophysical sources dependent on their gravitational-wave and neutrino emission processes.
Keywords: gravitational waves; neutrinos

Search for muon-neutrino emission from GeV and TeV gamma-ray flaring blazars using five years of data of the ANTARES telescope - Adrian-Martinez, S.; Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; Bogazzi, C.; et al. (Journal of Cosmology and Astroparticle Physics, 2015)
The ANTARES telescope is well-suited for detecting astrophysical transient neutrino sources as it can observe a full hemisphere of the sky at all times with a high duty cycle. The background due to atmospheric particles can be drastically reduced, and the point-source sensitivity improved, by selecting a narrow time window around possible neutrino production periods. Blazars, being radio-loud active galactic nuclei with their jets pointing almost directly towards the observer, are particularly attractive potential neutrino point sources, since they are among the most likely sources of the very high-energy cosmic rays. Neutrinos and gamma rays may be produced in hadronic interactions with the surrounding medium. Moreover, blazars generally show high time variability in their light curves at different wavelengths and on various time scales. This paper presents a time-dependent analysis applied to a selection of flaring gamma-ray blazars observed by the FERMI/LAT experiment and by TeV Cherenkov telescopes using five years of ANTARES data taken from 2008 to 2012. The results are compatible with fluctuations of the background. Upper limits on the neutrino fluence have been produced and compared to the measured gamma-ray spectral energy distribution.
Keywords: X-ray binaries; neutrino astronomy

Search for muon neutrinos from gamma-ray bursts with the ANTARES neutrino telescope using 2008 to 2011 data - Adrian-Martinez, S.; Albert, A.; Al Samarai, I.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J. -J.; Baret, B.; Barrios-Marti, J.; et al. (Astronomy & Astrophysics, 2013)
Aims. We search for muon neutrinos in coincidence with GRBs with the ANTARES neutrino detector using data from the end of 2007 to 2011.Methods. Expected neutrino fluxes were calculated for each burst individually. The most recent numerical calculations of the spectra using the NeuCosmA code were employed, which include Monte Carlo simulations of the full underlying photohadronic interaction processes. The discovery probability for a selection of 296 GRBs in the given period was optimised using an extended maximum-likelihood strategy.Results. No significant excess over background is found in the data, and 90% confidence level upper limits are placed on the total expected flux according to the model.
Keywords: neutrinos; gamma-ray burst: general; methods: numerical

Search for neutrino counterparts of gravitational-wave events detected by LIGO and Virgo during run O2 with the ANTARES telescope - Albert, A.; André, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin, V.; Biagi, S.; et al. (European Physical Journal C: Particles and Fields, 2020)
An offline search for a neutrino counterpart to gravitational-wave (GW) events detected during the second observation run (O2) of Advanced-LIGO and Advanced-Virgo performed with ANTARES data is presented. In addition to the search for long tracks induced by νμ (ν¯ μ) charged current interactions, a search for showering events induced by interactions of neutrinos of any flavour is conducted. The severe spatial and time coincidence provided by the gravitational-wave alert allows regions above the detector horizon to be probed, extending the ANTARES sensitivity over the entire sky. The results of this all-neutrino-flavour and all-sky time dependent analysis are presented. The search for prompt neutrino emission within ±500 s around the time of six GW events yields no neutrino counterparts. Upper limits on the neutrino spectral fluence and constraints on the isotropic energy radiated via high-energy neutrinos (from a few TeV to a few tens of PeV) are set for each GW event analysed.
CRIS-Team Scopus Importer:2020-06-16

Search for neutrino emission from gamma-ray flaring blazars with the ANTARES telescope - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J.; Baret, B.; Basa, S.; et al. (Astroparticle Physics, 2012)
The ANTARES telescope is well-suited to detect neutrinos produced in astrophysical transient sources as it can observe a full hemisphere of the sky at all times with a high duty cycle. Radio-loud active galactic nuclei with jets pointing almost directly towards the observer, the so-called blazars, are particularly attractive potential neutrino point sources. The all-sky monitor LAT on board the Fermi satellite probes the variability of any given gamma-ray bright blazar in the sky on time scales of hours to months. Assuming hadronic models, a strong correlation between the gamma-ray and the neutrino fluxes is expected. Selecting a narrow time window on the assumed neutrino production period can significantly reduce the background.An unbinned method based on the minimization of a likelihood ratio was applied to a subsample of data collected in 2008 (61 days live time). By searching for neutrinos during the high state periods of the AGN light curve, the sensitivity to these sources was improved by about a factor of two with respect to a standard time-integrated point source search. First results on the search for neutrinos associated with ten bright and variable Fermi sources are presented. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: ANTARES; Neutrino astronomy; Fermi LAT transient sources; Time-dependent search; Blazars

Search for Neutrinos from the Tidal Disruption Events AT2019dsg and AT2019fdr with the ANTARES Telescope - Albert, A.; Alves, S.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bendahman, M.; et al. (Astrophysical Journal, 2021)
On 2019 October 1, the IceCube Collaboration detected a muon track neutrino with a high probability of being of astrophysical origin, IC191001A. After a few hours, the tidal disruption event (TDE) AT2019dsg, observed by the Zwicky Transient Facility (ZTF), was indicated as the most likely counterpart of the IceCube track. More recently, the follow-up campaign of the IceCube alerts by ZTF suggested a second TDE, AT2019fdr, as a promising counterpart of another IceCube muon track candidate, IC200530A, detected on 2020 May 30. Here, these intriguing associations are followed-up by searching for neutrinos in the ANTARES detector from the directions of AT2019dsg and AT2019fdr using a time-integrated approach. As no significant evidence for space clustering is found in the ANTARES data, upper limits on the one-flavor neutrino flux and fluence are set.
CRIS-Team WoS Importer:2021-10-29

Search for relativistic magnetic monopoles with five years of the ANTARES detector data - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Journal of High Energy Physics, 2017)
A search for magnetic monopoles using five years of data recorded with the ANTARES neutrino telescope from January 2008 to December 2012 with a total live time of 1121 days is presented. The analysis is carried out in the range beta > 0.6 of magnetic monopole velocities using a strategy based on run-by-run Monte Carlo simulations. No signal above the background expectation from atmospheric muons and atmospheric neutrinos is observed, and upper limits are set on the magnetic monopole flux ranging from 5.7 x 10(-16) to 1.5 x 10(-18) cm(-2).s(-1).sr(-1).
Keywords: Exotics; Neutrino Detectors and Telescopes (experiments)

Search for relativistic magnetic monopoles with the ANTARES neutrino telescope - Adrian-Martinez, S.; Aguilar, J. A.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Aubert, J-J.; et al. (Astroparticle Physics, 2012)
Magnetic monopoles are predicted in various unified gauge models and could be produced at intermediate mass scales. Their detection in a neutrino telescope is facilitated by the large amount of light emitted compared to that from muons. This paper reports on a search for upgoing relativistic magnetic monopoles with the ANTARES neutrino telescope using a data set of 116 days of live time taken from December 2007 to December 2008. The one observed event is consistent with the expected atmospheric neutrino and muon background, leading to a 90% C.L. upper limit on the monopole flux between 1.3 x 10-(17) and 8.9 x 10(-17) CM-2 s(-1) sr(-1) for monopoles with velocity beta >= 0.625. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Magnetic monopole; Neutrino telescopes; ANTARES

Search for solar atmospheric neutrinos with the ANTARES neutrino telescope - Albert, A.; Alves, S.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Ardid, S.; Aubert, J-J; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; et al. (Journal of Cosmology and Astroparticle Physics, 2022)
Solar Atmospheric Neutrinos (SA nu s) are produced by the interaction of cosmic rays with the solar medium. The detection of SA nu s would provide useful information on the composition of primary cosmic rays as well as the solar density. These neutrinos represent an irreducible source of background for indirect searches for dark matter towards the Sun and the measurement of their flux would allow for a better assessment of the uncertainties related to these searches. In this paper we report on the analysis performed, based on an unbinned likelihood maximisation, to search for SA nu s with the ANTARES neutrino telescope. After analysing the data collected over 11 years, no evidence for a solar atmospheric neutrino signal has been found. An upper limit at 90% confidence level on the flux of solar atmospheric neutrinos has been obtained, equal to 7x10(-11) [TeV-1 cm(-2) s(-1)] b at E-nu = 1 TeV for the reference cosmic ray model assumed.
CRIS-Team WoS Importer:2022-08-19
Keywords: dark matter experiments; neutrino experiments; neutrino detectors; solar and atmospheric neutrinos

Search for Spatial Correlations of Neutrinos with Ultra-high-energy Cosmic Rays - Albert, A.; Domi, Alba; Alves, S.; Andre, M.; Anghinolfi, M.; Ardid, S.; Aubert, J-J; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bendahman, M.; et al. (Astrophysical Journal, 2022)
For several decades, the origin of ultra-high-energy cosmic rays (UHECRs) has been an unsolved question of high-energy astrophysics. One approach for solving this puzzle is to correlate UHECRs with high-energy neutrinos, since neutrinos are a direct probe of hadronic interactions of cosmic rays and are not deflected by magnetic fields. In this paper, we present three different approaches for correlating the arrival directions of neutrinos with the arrival directions of UHECRs. The neutrino data are provided by the IceCube Neutrino Observatory and ANTARES, while the UHECR data with energies above similar to 50 EeV are provided by the Pierre Auger Observatory and the Telescope Array. All experiments provide increased statistics and improved reconstructions with respect to our previous results reported in 2015. The first analysis uses a high-statistics neutrino sample optimized for point-source searches to search for excesses of neutrino clustering in the vicinity of UHECR directions. The second analysis searches for an excess of UHECRs in the direction of the highest-energy neutrinos. The third analysis searches for an excess of pairs of UHECRs and highest-energy neutrinos on different angular scales. None of the analyses have found a significant excess, and previously reported overfluctuations are reduced in significance. Based on these results, we further constrain the neutrino flux spatially correlated with UHECRs.
CRIS-Team WoS Importer:2022-08-26

Search for steady point-like sources in the astrophysical muon neutrino flux with 8 years of IceCube data - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Altmann, D.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; Arguelles, C.; et al. (European Physical Journal C, 2019)
The IceCube Collaboration has observed a high-energy astrophysical neutrino flux and recently found evidence for neutrino emission from the blazar TXS 0506+056. These results open a new window into the high-energy universe. However, the source or sources of most of the observed flux of astrophysical neutrinos remains uncertain. Here, a search for steady point-like neutrino sources is performed using an unbinned likelihood analysis. The method searches for a spatial accumulation of muon-neutrino events using the very high-statistics sample of about 497,000 neutrinos recorded by IceCube between 2009 and 2017. The median angular resolution is approximate to 1 degrees at 1 TeV and improves to approximate to 0.3 degrees for neutrinos with an energy of 1 PeV. Compared to previous analyses, this search is optimized for point-like neutrino emission with the same flux-characteristics as the observed astrophysical muon-neutrino flux and introduces an improved event-reconstruction and parametrization of the background. The result is an improvement in sensitivity to the muon-neutrino flux compared to the previous analysis of approximate to 35% assuming an E-2 spectrum. The sensitivity on the muon-neutrino flux is at a level of E2dN/dE=310-13s-1. No new evidence for neutrino sources is found in a full sky scan and in an a priori candidate source list that is motivated by gamma-ray observations. Furthermore, no significant excesses above background are found from populations of sub-threshold sources. The implications of the non-observation for potential source classes are discussed.
CRIS-Team WoS Importer:2019-03-29

Search for transient optical counterparts to high-energy IceCube neutrinos with Pan-STARRS1 - Kankare, E.; Huber, M.; Smartt, S. J.; Chambers, K.; Smith, K. W.; Mcbrien, O.; Chen, T-W; Flewelling, H.; Lowe, T.; Magnier, E.; Schultz, A.; Waters, C.; et al. (Astronomy & Astrophysics, 2019)
In order to identify the sources of the observed diffuse high-energy neutrino flux, it is crucial to discover their electromagnetic counterparts. To increase the sensitivity of detecting counterparts of transient or variable sources by telescopes with a limited field of view, IceCube began releasing alerts for single high-energy (Eνâ> â60 TeV) neutrino detections with sky localisation regions of order 1° radius in 2016. We used Pan-STARRS1 to follow-up five of these alerts during 2016-2017 to search for any optical transients that may be related to the neutrinos. Typically 10-20 faint (miP1âââ22.5 mag) extragalactic transients are found within the Pan-STARRS1 footprints and are generally consistent with being unrelated field supernovae (SNe) and AGN. We looked for unusual properties of the detected transients, such as temporal coincidence of explosion epoch with the IceCube timestamp, or other peculiar light curve and physical properties. We found only one transient that had properties worthy of a specific follow-up. In the Pan-STARRS1 imaging for IceCube-160427A (probability to be of astrophysical origin of ∼50%), we found a SN PS16cgx, located at 10.0′ from the nominal IceCube direction. Spectroscopic observations of PS16cgx showed that it was an H-poor SN at redshift zâ=â0.2895â ±â 0.0001. The spectra and light curve resemble some high-energy Type Ic SNe, raising the possibility of a jet driven SN with an explosion epoch temporally coincident with the neutrino detection. However, distinguishing Type Ia and Type Ic SNe at this redshift is notoriously difficult. Based on all available data we conclude that the transient is more likely to be a Type Ia with relatively weak Siâ» II absorption and a fairly normal rest-frame r-band light curve. If, as predicted, there is no high-energy neutrino emission from Type Ia SNe, then PS16cgx must be a random coincidence, and unrelated to the IceCube-160427A. We find no other plausible optical transient for any of the five IceCube events observed down to a 5σ limiting magnitude of miP1â≈â22 mag, between 1 day and 25 days after detection.
CRIS-Team Scopus Importer:2019-07-12
Keywords: Astroparticle physics; Neutrinos; Supernovae: general

Searching for TeV Gamma-Ray Emission from SGR 1935+2154 during Its 2020 X-Ray and Radio Bursting Phase - Abdalla, H.; Aharonian, F.; Mitchell, Alison; Spencer, Samuel; Benkhali, F. Ait; Anguner, E. O.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Baghmanyan,; et al. (Astrophysical Journal, 2021)
Magnetar hyperflares are the most plausible explanation for fast radio bursts (FRBs)-enigmatic powerful radio pulses with durations of several milliseconds and high brightness temperatures. The first observational evidence for this scenario was obtained in 2020 April when an FRB was detected from the direction of the Galactic magnetar and soft gamma-ray repeater SGR 1935+2154. The FRB was preceded by two gamma-ray outburst alerts by the BAT instrument aboard the Swift satellite, which triggered follow-up observations by the High Energy Stereoscopic System (H.E.S.S.). H.E.S.S. observed SGR 1935+2154 for 2 hr on 2020 April 28. The observations are coincident with X-ray bursts from the magnetar detected by INTEGRAL and Fermi-GBM, thus providing the first very high energy gamma-ray observations of a magnetar in a flaring state. High-quality data acquired during these follow-up observations allow us to perform a search for short-time transients. No significant signal at energies E > 0.6 TeV is found, and upper limits on the persistent and transient emission are derived. We here present the analysis of these observations and discuss the obtained results and prospects of the H.E.S.S. follow-up program for soft gamma-ray repeaters.
CRIS-Team WoS Importer:2021-10-08

Search of dark matter annihilation in the galactic centre using the ANTARES neutrino telescope - Adrian-Martinez, S.; Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; Bogazzi, C.; et al. (Journal of Cosmology and Astroparticle Physics, 2015)
A search for high-energy neutrinos coming from the direction of the Galactic Centre is performed using the data recorded by the ANTARES neutrino telescope from 2007 to 2012. The event selection criteria are chosen to maximise the sensitivity to possible signals produced by the self-annihilation of weakly interacting massive particles accumulated around the centre of the Milky Way with respect to the atmospheric background. After data unblinding, the number of neutrinos observed in the line of sight of the Galactic Centre is found to be compatible with background expectations. The 90% C.L. upper limits in terms of the neutrino+anti-neutrino flux, Phi(nu mu + (nu) over bar mu), and the velocity averaged annihilation cross-section, , are derived for the WIMP self-annihilation channels into b (b) over bar; W+W-; tau(+)tau(-); mu(+)mu(-); nu(nu) over bar. The ANTARES limits for are shown to be the most stringent for a neutrino telescope over the WIMP masses 25 GeV < M-WIMP < 10TeV.
Keywords: neutrino experiments; dark matter experiments; neutrino astronomy

Sensitivity of the KM3NeT/ARCA neutrino telescope to point-like neutrino sources - Aiello, S.; Akrame, S. E.; Ameli, F.; G. Anassontzis, E.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aublin, J.; Avgitas, T.; Bagatelas, C.; et al. (Astroparticle Physics, 2019)
KM3NeT will be a network of deep-sea neutrino telescopes in the Mediterranean Sea. The KM3NeT/ARCA detector, to be installed at the Capo Passero site (Italy), is optimised for the detection of high-energy neutrinos of cosmic origin. Thanks to its geographical location on the Northern hemisphere, KM3NeT/ARCA can observe upgoing neutrinos from most of the Galactic Plane, including the Galactic Centre. Given its effective area and excellent pointing resolution, KM3NeT/ARCA will measure or significantly constrain the neutrino flux from potential astrophysical neutrino sources. At the same time, it will test flux predictions based on gamma-ray measurements and the assumption that the gamma-ray flux is of hadronic origin. Assuming this scenario, discovery potentials and sensitivities for a selected list of Galactic sources and to generic point sources with an E −2 spectrum are presented. These spectra are assumed to be time independent. The results indicate that an observation with 3σ significance is possible in about six years of operation for the most intense sources, such as Supernovae Remnants RX J1713.7-3946 and Vela Jr. If no signal will be found during this time, the fraction of the gamma-ray flux coming from hadronic processes can be constrained to be below 50% for these two objects.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Astrophysical neutrino sources; Cherenkov underwater neutrino telescope; KM3NeT

Sensitivity to light sterile neutrino mixing parameters with KM3NeT/ORCA - Aiello, S.; Albert, A.; Alshamsi, M.; Garre, S. Alves; Aly, Z.; Ambrosone, Antonio; Ameli, F.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anguita, M.; Anton, Gisela; et al. (Journal of High Energy Physics, 2021)
KM3NeT/ORCA is a next-generation neutrino telescope optimised for atmospheric neutrino oscillations studies. In this paper, the sensitivity of ORCA to the presence of a light sterile neutrino in a 3+1 model is presented. After three years of data taking, ORCA will be able to probe the active-sterile mixing angles theta(14), theta(24), theta(34) and the effective angle theta(mu e), over a broad range of mass squared difference Delta m(41)(2) similar to [10(-5), 10] eV(2), allowing to test the eV-mass sterile neutrino hypothesis as the origin of short baseline anomalies, as well as probing the hypothesis of a very light sterile neutrino, not yet constrained by cosmology. ORCA will be able to explore a relevant fraction of the parameter space not yet reached by present measurements.
CRIS-Team WoS Importer:2021-11-12

Simulation of charge readout with segmented tiles in nEXO - Li, Z.; Cen, W. R.; Robinson, A.; Moore, D. C.; Wen, L. J.; Odian, A.; Kharusi, S. Al; Anton, Gisela; Arnquist, I. J.; Badhrees, I.; Barbeau, P. S.; Beck, D.; et al. (Journal of Instrumentation, 2019)
nEXO is a proposed experiment to search for the neutrino-less double beta decay (0νββ) of 136Xe in a tonne-scale liquid xenon time projection chamber (TPC) . The nEXO TPC will be equipped with charge collection tiles to form the anode. In this work, the charge reconstruction performance of this anode design is studied with a dedicated simulation package. A multi-variate method and a deep neural network are developed to distinguish simulated 0νββ signals from backgrounds arising from trace levels of natural radioactivity in the detector materials. These simulations indicate that the nEXO TPC with charge-collection tiles shows promising capability to discriminate the 0νββ signal from backgrounds. The estimated half-life sensitivity for 0νββ decay is improved by ∼20 (32)% with the multi-variate (deep neural network) methods considered here, relative to the sensitivity estimated in the nEXO pre-conceptual design report.
CRIS-Team Scopus Importer:2019-11-08
Keywords: Double-beta decay detectors; Noble liquid detectors (scintillation; ionization; doublephase)

Simultaneous observations of the blazar PKS 2155-304 from ultra-violet to TeV energies - Abdalla, H.; Adam, R.; Mitchell, Alison; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Ashkar, H.; Backes, M.; Martins, V. Barbosa; et al. (Astronomy & Astrophysics, 2020)
Here we report the results of the first ever contemporaneous multi-wavelength observation campaign on the BL Lac object PKS 2155-304 involving Swift, NuSTAR, Fermi-LAT, and H.E.S.S. The use of these instruments allows us to cover a broad energy range, which is important for disentangling the different radiative mechanisms. The source, observed from June 2013 to October 2013, was found in a low flux state with respect to previous observations but exhibited highly significant flux variability in the X-rays. The high-energy end of the synchrotron spectrum can be traced up to 40 keV without significant contamination by high-energy emission. A one-zone synchrotron self-Compton model was used to reproduce the broadband flux of the source for all the observations presented here but failed for previous observations made in April 2013. A lepto-hadronic solution was then explored to explain these earlier observational results.
CRIS-Team WoS Importer:2020-08-07

Single-exposure X-ray phase imaging microscopy with a grating interferometer - Wolf, Andreas; Akstaller, Bernhard; Cipiccia, Silvia; Flenner, Silja; Hagemann, Johannes; Ludwig, Veronika; Meyer, Pascal; Schropp, Andreas; Schuster, Max; Seifert, Maria; Weule, Mareike; Michel, Thilo; et al. (Journal of Synchrotron Radiation, 2022)
The advent of hard X-ray free-electron lasers enables nanoscopic X-ray imaging with sub-picosecond temporal resolution. X-ray grating interferometry offers a phase-sensitive full-field imaging technique where the phase retrieval can be carried out from a single exposure alone. Thus, the method is attractive for imaging applications at X-ray free-electron lasers where intrinsic pulse-to-pulse fluctuations pose a major challenge. In this work, the single-exposure phase imaging capabilities of grating interferometry are characterized by an implementation at the I13-1 beamline of Diamond Light Source (Oxfordshire, UK). For comparison purposes, propagation-based phase contrast imaging was also performed at the same instrument. The characterization is carried out in terms of the quantitativeness and the contrast-to-noise ratio of the phase reconstructions as well as via the achievable spatial resolution. By using a statistical image reconstruction scheme, previous limitations of grating interferometry regarding the spatial resolution can be mitigated as well as the experimental applicability of the technique.
CRIS-Team Scopus Importer:2022-05-27
Keywords: grating interferometry; phase contrast X-ray imaging; phase retrieval; X-ray microscopy

Sperm whale long-range echolocation sounds revealed by ANTARES, a deep-sea neutrino telescope - Andre, Michel; Caballe, A.; Van Der Schaar, M.; Solsona, A.; Houegnigan, L.; Zaugg, S.; Sanchez, A. M.; Castell, J. V.; Sole, Marta; Vila, F.; Djokic, D.; Adrian-Martinez, S.; et al. (Scientific Reports, 2017)
Despite dedicated research has been carried out to adequately map the distribution of the sperm whale in the Mediterranean Sea, unlike other regions of the world, the species population status is still presently uncertain. The analysis of two years of continuous acoustic data provided by the ANTARES neutrino telescope revealed the year-round presence of sperm whales in the Ligurian Sea, probably associated with the availability of cephalopods in the region. The presence of the Ligurian Sea sperm whales was demonstrated through the real-time analysis of audio data streamed from a cabled-to-shore deep-sea observatory that allowed the hourly tracking of their long-range echolocation behaviour on the Internet. Interestingly, the same acoustic analysis indicated that the occurrence of surface shipping noise would apparently not condition the foraging behaviour of the sperm whale in the area, since shipping noise was almost always present when sperm whales were acoustically detected. The continuous presence of the sperm whale in the region confirms the ecological value of the Ligurian sea and the importance of ANTARES to help monitoring its ecosystems.

Status of the photomultiplier-based FlashCam camera for the Cherenkov Telescope Array - Puehlhofer, Gerd; Jung-Richardt, Ira; Kalekin, Oleg; Lahmann, Robert; et al. (Proceedings of SPIE, 2014)

Status of the PMT development for KM3NeT - Classen, Lew; Kalekin, Oleg (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2013)
Keywords: KM3NeT; Optical module; Neutrino Telescope; Photomultiplier tube

Super-ORCA: Measuring the leptonic CP-phase with atmospheric neutrinos and beam neutrinos - Hofestädt, Jannik; Bruchner, Marc; Eberl, Thomas (Proceedings of Science, 2019)
Studying the atmospheric neutrino oscillation probabilities below 2 GeV with a multi-megaton Cherenkov detector allows for a measurement of the leptonic CP-phase dCP. The most relevant CP-sensitive energy range is below the neutrino detection threshold of KM3NeT/ORCA, which is an underwater Cherenkov detector optimised to determine the neutrino mass ordering by measuring the oscillation pattern of 3-30 GeV atmospheric neutrinos. With Super-ORCA, a 10 times more-densely instrumented version of ORCA, the detection threshold can be lowered and the event reconstruction capabilities improved. In this paper, the key detector performance indicators for a possible Super-ORCA detector and the sensitivity to dCP with atmospheric neutrinos are presented. Including systematics, a 1s-resolution on dCP of about 38? (23?) is achieved for dCP = 0 (dCP = p/2) after 10 years. In addition, the potential of using a neutrino beam from the Protvino accelerator facility to the Super-ORCA detector is discussed. With this, a 1s-resolution on dCP of about 10? (16?) is achieved for dCP = 0 (dCP = p/2) after 10 years.
CRIS-Team Scopus Importer:2021-04-20

Talbot-Lau x-ray phase-contrast setup for fast scanning of large samples - Seifert, Maria; Ludwig, Veronika; Käppler, Sebastian; Horn, Florian; Meyer, Pascal; Pelzer, Georg; Rieger, Jens; Sand, Daniel; Michel, Thilo; Mohr, Juergen; Riess, Christian; Anton, Gisela (Scientific Reports, 2019)
Compared to conventional attenuation x-ray radiographic imaging, the x-ray Talbot-Lau technique provides further information about the scattering and the refractive properties of the object in the beam path. Hence, this additional information should improve the diagnostic process concerning medical applications and non-destructive testing. Nevertheless, until now, due to grating fabrication process, Talbot-Lau imaging suffers from small grating sizes (70 mm diameter). This leads to long acquisition times for imaging large objects. Stitching the gratings is one solution. Another one consists of scanning Talbot-Lau setups. In this publication, we present a compact and very fast scanning setup which enables imaging of large samples. With this setup a maximal scanning velocity of 71.7 mm/s is possible. A resolution of 4.1 lines/mm can be achieved. No complex alignment procedures are necessary while the field of view comprises 17.5 x 150 cm2. An improved reconstruction algorithm concerning the scanning approach, which increases robustness with respect to mechanical instabilities, has been developed and is presented. The resolution of the setup in dependence of the scanning velocity is evaluated. The setup imaging qualities are demonstrated using a human knee ex-vivo as an example for a high absorbing human sample.
CRIS-Team WoS Importer:2019-03-29

TeV Emission of Galactic Plane Sources with HAWC and HESS - Abdalla, H.; Mitchell, Alison; Aharonian, Felix; Spencer, Samuel; Benkhali, F. Ait; Anguner, E. O.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Baghmanyan,; et al. (Astrophysical Journal, 2021)
The High Altitude Water Cherenkov (HAWC) observatory and the High Energy Stereoscopic System (H.E.S.S.) are two leading instruments in the ground-based very-high-energy gamma-ray domain. HAWC employs the water Cherenkov detection (WCD) technique, while H.E.S.S. is an array of Imaging Atmospheric Cherenkov Telescopes (IACTs). The two facilities therefore differ in multiple aspects, including their observation strategy, the size of their field of view, and their angular resolution, leading to different analysis approaches. Until now, it has been unclear if the results of observations by both types of instruments are consistent: several of the recently discovered HAWC sources have been followed up by IACTs, resulting in a confirmed detection only in a minority of cases. With this paper, we go further and try to resolve the tensions between previous results by performing a new analysis of the H.E.S.S. Galactic plane survey data, applying an analysis technique comparable between H.E.S.S. and HAWC. Events above 1 TeV are selected for both data sets, the point-spread function of H.E.S.S. is broadened to approach that of HAWC, and a similar background estimation method is used. This is the first detailed comparison of the Galactic plane observed by both instruments. H.E.S.S. can confirm the gamma-ray emission of four HAWC sources among seven previously undetected by IACTs, while the three others have measured fluxes below the sensitivity of the H.E.S.S. data set. Remaining differences in the overall gamma-ray flux can be explained by the systematic uncertainties. Therefore, we confirm a consistent view of the gamma-ray sky between WCD and IACT techniques.
CRIS-Team WoS Importer:2021-08-20

TeV Gamma-Ray Observations of the Binary Neutron Star Merger GW170817 with HESS - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, Michael; Balzer, A.; Barnard, Monica; Becherini, Y.; et al. (Astrophysical Journal Letters, 2017)
We search for high-energy gamma-ray emission from the binary neutron star merger GW170817 with the H.E.S.S. Imaging Air Cherenkov Telescopes. The observations presented here have been obtained starting only 5.3 hr after GW170817. The H.E.S.S. target selection identified regions of high probability to find a counterpart of the gravitational-wave event. The first of these regions contained the counterpart SSS17a that has been identified in the optical range several hours after our observations. We can therefore present the first data obtained by a ground-based pointing instrument on this object. A subsequent monitoring campaign with the H.E.S.S. telescopes extended over several days, covering timescales from 0.22 to 5.2 days and energy ranges between 270 GeV to 8.55 TeV. No significant gamma-ray emission has been found. The derived upper limits on the very-high-energy gamma-ray flux for the first time constrain non-thermal, high-energy emission following the merger of a confirmed binary neutron star system.
CRIS-Team WoS Importer:2020-01-15

The ANTARES telescope neutrino alert system - Ageron, M.; Aguilar, J. A.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Aubert, J. -J.; et al. (Astroparticle Physics, 2012)
The ANTARES telescope has the capability to detect neutrinos produced in astrophysical transient sources. Potential sources include gamma-ray bursts, core collapse supernovae, and flaring active galactic nuclei. To enhance the sensitivity of ANTARES to such sources, a new detection method based on coincident observations of neutrinos and optical signals has been developed. A fast online muon track reconstruction is used to trigger a network of small automatic optical telescopes. Such alerts are generated for special events, such as two or more neutrinos, coincident in time and direction, or single neutrinos of very high energy. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: ANTARES; Neutrino astronomy; Transient sources; Optical follow-up

The ANTARES underwater neutrino telescope - Kalekin, Oleg (Journal of Physics: Conference Series, 2009)

The Control Unit of the KM3NeT Data Acquisition System - Aiello, S.; Ameli, F.; Domi, Alba; Kalekin, Oleg; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anton, G.; Ardid, M.; Aublin, J.; Bagatelas, C.; Barbarino, G.; et al. (Computer Physics Communications, 2020)
The KM3NeT Collaboration runs a multi-site neutrino observatory in the Mediterranean Sea. Water Cherenkov particle detectors, deep in the sea and far off the coasts of France and Italy, are already taking data while incremental construction progresses. Data Acquisition Control software is operating off-shore detectors as well as testing and qualification stations for their components. The software, named Control Unit, is highly modular. It can undergo upgrades and reconfiguration with the acquisition running. Interplay with the central database of the Collaboration is obtained in a way that allows for data taking even if Internet links fail. In order to simplify the management of computing resources in the long term, and to cope with possible hardware failures of one or more computers, the KM3NeT Control Unit software features a custom dynamic resource provisioning and failover technology, which is especially important for ensuring continuity in case of rare transient events in multi-messenger astronomy. The software architecture relies on ubiquitous tools and broadly adopted technologies and has been successfully tested on several operating systems.
CRIS-Team Scopus Importer:2020-06-23
Keywords: 07.05.Hd; 29.85.Ca; Astroparticle detector; Data acquisition control; KM3NeT; Neutrino detector

The cosmic ray shadow of the Moon observed with the ANTARES neutrino telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Martit, J.; Basa, S.; Belhorma, B.; et al. (European Physical Journal C, 2018)
One of the main objectives of the ANTARES telescope is the search for point- like neutrino sources. Both the pointing accuracy and the angular resolution of the detector are important in this context and a reliableway to evaluate this performance is needed. In order to measure the pointing accuracy of the detector, one possibility is to study the shadow of the Moon, i. e. the deficit of the atmospheric muon flux from the direction of the Moon induced by the absorption of cosmic rays. Analysing the data taken between 2007 and 2016, theMoon shadow is observed with 3.5s statistical significance. The detector angular resolution for downwardgoing muons is 0.73. +/- 0.14.. The resulting pointing performance is consistent with the expectations. An independent check of the telescope pointing accuracy is realised with the data collected by a shower array detector onboard of a ship temporarily moving around the ANTARES location.

The EXO-200 detector, part II: Auxiliary systems - Ackerman, N.; Albert, J.; Auger, M.; Auty, D. J.; Badhrees, I.; Barbeau, P. S.; Bartoszek, L.; Baussan, E.; Belov, V.; Benitez-Medina, C.; Bhatta, T.; Breidenbach, M.; et al. (Journal of Instrumentation, 2022)
The EXO-200 experiment searched for neutrinoless double-beta decay of 136Xe with a single-phase liquid xenon detector. It used an active mass of 110 kg of 80.6%-enriched liquid xenon in an ultra-low background time projection chamber with ionization and scintillation detection and readout. This paper describes the design and performance of the various support systems necessary for detector operation, including cryogenics, xenon handling, and controls. Novel features of the system were driven by the need to protect the thin-walled detector chamber containing the liquid xenon, to achieve high chemical purity of the Xe, and to maintain thermal uniformity across the detector.
CRIS-Team Scopus Importer:2022-03-11
Keywords: Cryogenic detectors; Double-beta decay detectors; Liquid detectors; Time projection Chambers (TPC)

THE FIRST COMBINED SEARCH for NEUTRINO POINT-SOURCES in the SOUTHERN HEMISPHERE with the ANTARES and ICECUBE NEUTRINO TELESCOPES - Adrian-Martinez, S.; Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; Bormuth, R.; et al. (Astrophysical Journal, 2016)
We present the results of searches for point-like sources of neutrinos based on the first combined analysis of data from both the ANTARES and IceCube neutrino telescopes. The combination of both detectors, which differ in size and location, forms a window in the southern sky where the sensitivity to point sources improves by up to a factor of 2 compared with individual analyses. Using data recorded by ANTARES from 2007 to 2012, and by IceCube from 2008 to 2011, we search for sources of neutrino emission both across the southern sky and from a preselected list of candidate objects. No significant excess over background has been found in these searches, and flux upper limits for the candidate sources are presented for E and E power-law spectra with different energy cut-offs.
Keywords: astroparticle physics; neutrinos

The GCT camera for the Cherenkov Telescope Array - Lapington, J. S.; Abchiche, A.; Allan, D.; Amans, J. -P.; Armstrong, T. P.; Balzer, A.; Berge, David; Boisson, C.; Bousquet, J. -J.; Bose, R.; Brown, A. M.; Bryan, M.; et al. (ELSEVIER SCIENCE BV, 2017)
The Gamma Cherenkov Telescope (GCT) is one of the designs proposed for the Small Sized Telescope (SST) section of the Cherenkov Telescope Array (CTA). The GCT uses dual-mirror optics, resulting in a compact telescope with good image quality and a large field of view with a smaller, more economical, camera than is achievable with conventional single mirror solutions. The photon counting GCT camera is designed to record the flashes of atmospheric Cherenkov light from gamma and cosmic ray initiated cascades, which last only a few tens of nanoseconds.The GCT optics require that the camera detectors follow a convex surface with a radius of curvature of 1 m and a diameter of similar to 35 cm, which is approximated by tiling the focal plane with 32 modules. The first camera prototype is equipped with multi-anode photomultipliers, each comprising an 8x8 array of 6x6 mm(2) pixels to provide the required angular scale, adding up to 2048 pixels in total. Detector signals are shaped, amplified and digitised by electronics based on custom ASICs that provide digitisation at 1 GSample/s. The camera is self-triggering, retaining images where the focal plane light distribution matches predefined spatial and temporal criteria. The electronics are housed in the liquid-cooled, sealed camera enclosure. LED flashers at the corners of the focal plane provide a calibration source via reflection from the secondary mirror.The first GCT camera prototype underwent preliminary laboratory tests last year. In November 2015, the camera was installed on a prototype GCT telescope (SST-GATE) in Paris and was used to successfully record the first Cherenkov light of any CTA prototype, and the first Cherenkov light seen with such a dual-mirror optical system. A second full-camera prototype based on Silicon Photomultipliers is under construction. Up to 35 GCTs are envisaged for CTA.
Keywords: GCT; Cherenkov Telescope Array; Schwarzschild-Couder; Imaging air Cherenkov telescope; Photon-counting; Camera

The GCT camera for the Cherenkov Telescope Array - Lapington, J. S.; Abchiche, A.; Allan, D.; Amans, J. -P.; Armstrong, T. P.; Balzer, A.; Berge, David; Boisson, C.; Bousquet, J. -J.; Bose, R.; Brown, A. M.; Bryan, M.; et al. (ELSEVIER SCIENCE BV, 2017)
The Gamma Cherenkov Telescope (GCT) is one of the designs proposed for the Small Sized Telescope (SST) section of the Cherenkov Telescope Array (CTA). The GCT uses dual-mirror optics, resulting in a compact telescope with good image quality and a large field of view with a smaller, more economical, camera than is achievable with conventional single mirror solutions. The photon counting GCT camera is designed to record the flashes of atmospheric Cherenkov light from gamma and cosmic ray initiated cascades, which last only a few tens of nanoseconds.The GCT optics require that the camera detectors follow a convex surface with a radius of curvature of 1 m and a diameter of similar to 35 cm, which is approximated by tiling the focal plane with 32 modules. The first camera prototype is equipped with multi-anode photomultipliers, each comprising an 8x8 array of 6x6 mm(2) pixels to provide the required angular scale, adding up to 2048 pixels in total. Detector signals are shaped, amplified and digitised by electronics based on custom ASICs that provide digitisation at 1 GSample/s. The camera is self-triggering, retaining images where the focal plane light distribution matches predefined spatial and temporal criteria. The electronics are housed in the liquid-cooled, sealed camera enclosure. LED flashers at the corners of the focal plane provide a calibration source via reflection from the secondary mirror.The first GCT camera prototype underwent preliminary laboratory tests last year. In November 2015, the camera was installed on a prototype GCT telescope (SST-GATE) in Paris and was used to successfully record the first Cherenkov light of any CTA prototype, and the first Cherenkov light seen with such a dual-mirror optical system. A second full-camera prototype based on Silicon Photomultipliers is under construction. Up to 35 GCTs are envisaged for CTA.
Keywords: GCT; Cherenkov Telescope Array; Schwarzschild-Couder; Imaging air Cherenkov telescope; Photon-counting; Camera

The Influence of Satellite Trails on H.E.S.S. Gamma-Ray Astronomical Observations - Spencer, Samuel; Lang, Thomas; Mitchell, Alison (38th International Cosmic Ray Conference (ICRC2023), 2023)
The number of satellites launched into low earth orbit has almost tripled (to over 4000) in the last three years due to the increasing commercialisation of space. Satellite constellations with a total of over 400,000 satellites are proposed to be launched in the near future. Many of these satellites are highly reflective, resulting in a high optical brightness that affects ground-based astronomical observations across the electromagnetic spectrum. Despite this, the potential effect of these satellites on Imaging Atmospheric Cherenkov Telescopes (IACTs) has so far been assumed to be negligible due to their nanosecond integration times. This has, however, never been verified. We aim to identify satellite trails in data taken by the High Energy Stereoscopic System (H.E.S.S.) IACT array in Namibia, using Night Sky Background (NSB) data from the CT5 camera installed in 2019. We determine which observation times and pointing directions are affected the most, and evaluate the impact on Hillas parameters used for classification and reconstruction of high-energy Extensive Air Shower events. Finally, we predict how future planned satellite launches will affect gamma-ray observations with IACTs.<br

The KM3NeT potential for the next core-collapse supernova observation with neutrinos: KM3NeT Collaboration - Aiello, S.; Domi, Alba; Albert, A.; Garre, S. Alves; Aly, Z.; Ambrosone, A.; Ameli, F.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anguita, M.; Anton, Gisela; et al. (European Physical Journal C: Particles and Fields, 2021)
The KM3NeT research infrastructure is under construction in the Mediterranean Sea. It consists of two water Cherenkov neutrino detectors, ARCA and ORCA, aimed at neutrino astrophysics and oscillation research, respectively. Instrumenting a large volume of sea water with ∼ 6200 optical modules comprising a total of ∼ 200 , 000 photomultiplier tubes, KM3NeT will achieve sensitivity to ∼10MeV neutrinos from Galactic and near-Galactic core-collapse supernovae through the observation of coincident hits in photomultipliers above the background. In this paper, the sensitivity of KM3NeT to a supernova explosion is estimated from detailed analyses of background data from the first KM3NeT detection units and simulations of the neutrino signal. The KM3NeT observational horizon (for a 5σ discovery) covers essentially the Milky-Way and for the most optimistic model, extends to the Small Magellanic Cloud (∼60kpc). Detailed studies of the time profile of the neutrino signal allow assessment of the KM3NeT capability to determine the arrival time of the neutrino burst with a few milliseconds precision for sources up to 5–8 kpc away, and detecting the peculiar signature of the standing accretion shock instability if the core-collapse supernova explosion happens closer than 3–5 kpc, depending on the progenitor mass. KM3NeT’s capability to measure the neutrino flux spectral parameters is also presented.
CRIS-Team Scopus Importer:2021-06-11

The positioning system of the ANTARES Neutrino Telescope - Adrian-Martinez, S.; Ageron, M.; Aguilar, J. A.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; et al. (Journal of Instrumentation, 2012)
The ANTARES neutrino telescope, located 40km off the coast of Toulon in the Mediterranean Sea at a mooring depth of about 2475m, consists of twelve detection lines equipped typically with 25 storeys. Every storey carries three optical modules that detect Cherenkov light induced by charged secondary particles (typically muons) coming from neutrino interactions. As these lines are flexible structures fixed to the sea bed and held taut by a buoy, sea currents cause the lines to move and the storeys to rotate. The knowledge of the position of the optical modules with a precision better than 10cm is essential for a good reconstruction of particle tracks. In this paper the ANTARES positioning system is described. It consists of an acoustic positioning system, for distance triangulation, and a compass-tiltmeter system, for the measurement of the orientation and inclination of the storeys. Necessary corrections are discussed and the results of the detector alignment procedure are described.
Keywords: Timing detectors; Detector modelling and simulations II (electric fields; charge transport; multiplication and induction; pulse formation; electron emission; etc); Detector alignment and calibration methods (lasers; sources; particle-beams); Detector control systems (detector and experiment monitoring and slow-control systems; architecture; hardware; algorithms; databases)

The prototype detection unit of the KM3NeT detector: KM3NeT Collaboration - Adrian-Martinez, S.; Ageron, M.; Aharonian, F.; Aiello, S.; Albert, A.; Ameli, F.; Anassontzis, E. G.; Androulakis, G. C.; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, M.; et al. (European Physical Journal C: Particles and Fields, 2016)
A prototype detection unit of the KM3NeT deep-sea neutrino telescope has been installed at 3500m depth 80 km offshore the Italian coast. KM3NeT in its final configuration will contain several hundreds of detection units. Each detection unit is a mechanical structure anchored to the sea floor, held vertical by a submerged buoy and supporting optical modules for the detection of Cherenkov light emitted by charged secondary particles emerging from neutrino interactions. This prototype string implements three optical modules with 31 photomultiplier tubes each. These optical modules were developed by the KM3NeT Collaboration to enhance the detection capability of neutrino interactions. The prototype detection unit was operated since its deployment in May 2014 until its decommissioning in July 2015. Reconstruction of the particle trajectories from the data requires a nanosecond accuracy in the time calibration. A procedure for relative time calibration of the photomultiplier tubes contained in each optical module is described. This procedure is based on the measured coincidences produced in the sea by the ^4040K background light and can easily be expanded to a detector with several thousands of optical modules. The time offsets between the different optical modules are obtained using LED nanobeacons mounted inside them. A set of data corresponding to 600 h of livetime was analysed. The results show good agreement with Monte Carlo simulations of the expected optical background and the signal from atmospheric muons. An almost background-free sample of muons was selected by filtering the time correlated signals on all the three optical modules. The zenith angle of the selected muons was reconstructed with a precision of about 3^° ∘.

Thermo-acoustic sound generation in the interaction of pulsed proton and laser beams with a water target - Lahmann, Robert; Anton, Gisela; Graf, Kay; Hossl, J.; Kappes, Alexander; Katz, Uli; Mecke, Klaus; Schwemmer, S. (Astroparticle Physics, 2015)
The generation of hydrodynamic radiation in interactions of pulsed proton and laser beams with matter is explored. The beams were directed into a water target and the resulting acoustic signals were recorded with pressure sensitive sensors. Measurements were performed with varying pulse energies, sensor positions, beam diameters and temperatures. The obtained data are matched by simulation results based on the thermo-acoustic model with uncertainties at a level of 10%. The results imply that the primary mechanism for sound generation by the energy deposition of particles propagating in water is the local heating of the medium. The heating results in a fast expansion or contraction and a pressure pulse of bipolar shape is emitted into the surrounding medium. An interesting, widely discussed application of this effect could be the detection of ultra-high energetic cosmic neutrinos in future large-scale acoustic neutrino detectors. For this application a validation of the sound generation mechanism to high accuracy, as achieved with the experiments discussed in this article, is of high importance.
Keywords: Acoustic neutrino detection; Beam interaction; Cosmic neutrinos; Thermo-acoustic model; Ultra-high energy cosmic rays

The search for high-energy neutrinos coincident with fast radio bursts with the ANTARES neutrino telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; et al. (Monthly Notices of the Royal Astronomical Society, 2019)
In the past decade, a new class of bright transient radio sources with millisecond duration has been discovered. The origin of these so-called fast radio bursts (FRBs) is still a mystery, despite the growing observational efforts made by various multiwavelength and multimessenger facilities. To date, many models have been proposed to explain FRBs, but neither the progenitors nor the radiative and the particle acceleration processes at work have been clearly identified. In this paper, we assess whether hadronic processes may occur in the vicinity of the FRB source. If they do, FRBs may contribute to the high-energy cosmic-ray and neutrino fluxes. A search for these hadronic signatures was carried out using the ANTARES neutrino telescope. The analysis consists in looking for high-energy neutrinos, in the TeV-PeV regime, that are spatially and temporally coincident with the detected FRBs. Most of the FRBs discovered in the period 2013-2017 were in the field of view of the ANTARES detector, which is sensitive mostly to events originating from the Southern hemisphere. From this period, 12 FRBs were selected and no coincident neutrino candidate was observed. Upper limits on the per-burst neutrino fluence were derived using a power-law spectrum, dN/DE nu proportional to E-nu(-gamma), for the incoming neutrino flux, assuming spectral indexes gamma = 1.0, 2.0, 2.5. Finally, the neutrino energy was constrained by computing the total energy radiated in neutrinos, assuming different distances for the FRBs. Constraints on the neutrino fluence and on the energy released were derived from the associated null results.
Keywords: acceleration of particles; neutrinos; astroparticle physics; radio continuum: transients; methods: data analysis

The Search for Neutrinos from TXS 0506+056 with the ANTARES Telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; et al. (Astrophysical Journal Letters, 2018)
The results of three different searches for neutrino candidates, associated with the IceCube-170922A event or from the direction of TXS 0506+056, by the ANTARES neutrino telescope, are presented. The first search refers to the online follow-up of the IceCube alert; the second is based on the standard time-integrated method employed by the Collaboration to search for point-like neutrino sources; the third uses information from the IceCube time-dependent analysis that reported bursting activity centered on 2014 December 13, as input for an ANTARES time-dependent analysis. The online follow-up and the time-dependent analysis yield no events related to the source. The time-integrated study performed over a period from 2007 to 2017 fits 1.03 signal events, which corresponds to a p-value of 3.4% (not considering trial factors). Only for two other astrophysical objects in our candidate list has a smaller p-value been found. When considering that 107 sources have been investigated, the post-trial p-value for TXS 0506+056 corresponds to 87%.
Keywords: astroparticle physics; elementary particles; galaxies: active

The SUrvey for Pulsars and Extragalactic Radio Bursts - II. New FRB discoveries and their follow-up - Bhandari, S.; Keane, E. F.; Barr, E. D.; Jameson, A.; Petroff, E.; Johnston, Simon; Bailes, Matthew; Bhat, N. D. R.; Burgay, M.; Burke-Spolaor, S.; Caleb, M.; Eatough, R. P.; et al. (Monthly Notices of the Royal Astronomical Society, 2018)
We report the discovery of four Fast Radio Bursts (FRBs) in the ongoing SUrvey for Pulsars and Extragalactic Radio Bursts at the Parkes Radio Telescope: FRBs 150610, 151206, 151230 and 160102. Our real-time discoveries have enabled us to conduct extensive, rapid multimessenger follow-up at 12 major facilities sensitive to radio, optical, X-ray, gamma-ray photons and neutrinos on time-scales ranging from an hour to a few months post-burst. No counterparts to the FRBs were found and we provide upper limits on afterglow luminosities. None of the FRBs were seen to repeat. Formal fits to all FRBs show hints of scattering while their intrinsic widths are unresolved in time. FRB 151206 is at low Galactic latitude, FRB 151230 shows a sharp spectral cut-off, and FRB 160102 has the highest dispersion measure (DM = 2596.1 +/- 0.3 pc cm(-3)) detected to date. Three of the FRBs have high dispersion measures (DM > 1500 pc cm(-3)), favouring a scenario where the DMis dominated by contributions from the intergalactic medium. The slope of the Parkes FRB source counts distribution with fluences > 2 Jy ms is alpha = - 2.2(-1.2)(+0.6) and still consistent with a Euclidean distribution (alpha = -3/2). We also find that the all-sky rate is 1.7(-0.9)(+1.5) x 10(3)FRBs/(4 pi sr)/day above similar to 2 Jy ms and there is currently no strong evidence for a latitude- dependent FRB sky rate.
Keywords: radiation mechanisms: general; methods: data analysis; methods: observational; surveys; intergalactic medium; radio continuum: general

Time calibration with atmospheric muon tracks in the ANTARES neutrino telescope - Adrian-Martinez, S.; Albert, A.; Andre, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Baret, B.; Barrios-Marti, Javier; Basa, S.; Bertin, V.; Biagi, Simone; Bogazzi, C.; et al. (Astroparticle Physics, 2016)
The ANTARES experiment consists of an array of photomultipliers distributed along 12 lines and located deep underwater in the Mediterranean Sea. It searches for astrophysical neutrinos collecting the Cherenkov light induced by the charged particles, mainly muons, produced in neutrino interactions around the detector. Since at energies of ∼10 TeV the muon and the incident neutrino are almost collinear, it is possible to use the ANTARES detector as a neutrino telescope and identify a source of neutrinos in the sky starting from a precise reconstruction of the muon trajectory. To get this result, the arrival times of the Cherenkov photons must be accurately measured. A to perform time calibrations with the precision required to have optimal performances of the instrument is described. The reconstructed tracks of the atmospheric muons in the ANTARES detector are used to determine the relative time offsets between photomultipliers. Currently, this method is used to obtain the time calibration constants for photomultipliers on different lines at a precision level of 0.5 ns. It has also been validated for calibrating photomultipliers on the same line, using a system of LEDs and laser light devices.
Keywords: ANTARES; Atmospheric muon tracks; Neutrino Telescopes; Time calibration

Time-dependent search for neutrino emission from X-ray binaries with the ANTARES telescope - Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; Bormuth, R.; et al. (Journal of Cosmology and Astroparticle Physics, 2017)
ANTARES is currently the largest neutrino telescope operating in the Northern Hemisphere, aiming at the detection of high-energy neutrinos from astrophysical sources. Neutrino telescopes constantly monitor at least one complete hemisphere of the sky, and are thus well-suited to detect neutrinos produced in transient astrophysical sources. A time-dependent search has been applied to a list of 33 X-ray binaries undergoing high flaring activities in satellite data (RXTE/ASM, MAXI and Swift/BAT) and during hardness transition states in the 2008-2012 period. The background originating from interactions of charged cosmic rays in the Earth's atmosphere is drastically reduced by requiring a directional and temporal coincidence with astrophysical phenomena. The results of this search are presented together with comparisons between the neutrino flux upper limits and the neutrino flux predictions from astrophysical models. The neutrino flux upper limits resulting from this search limit the jet parameter space for some astrophysical models.
Keywords: neutrino astronomy; X-ray binaries; X-ray telescopes

Trigger performance verification of the FlashCam prototype camera - Sailer, S.; Werner, F.; Hermann, G.; Barcelo, M.; Bauer, C.; Bernhard, S.; Biegger, M.; Canelli, F.; Capasso, M.; Diebold, S.; Eisenkolb, F.; Eschbach, Stefan; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2019)
FlashCam is a camera proposed for the medium-sized telescopes of the Cherenkov Telescope Array (CTA). We compare camera trigger rates obtained from measurements with the camera prototype in the laboratory and Monte Carlo simulations, when scanning the parameter space of the fully-digital trigger logic and the intensity of a continuous light source mimicking the night sky background (NSB) during on-site operation. The comparisons of the measured data results to the Monte Carlo simulations are used to verify the FlashCam trigger logic and the expected trigger performance.
CRIS-Team Scopus Importer:2019-06-25
Keywords: CTA; DAQ; Data management; FlashCam; Front end; Trigger

Using NuRadioMC to study the performance of UHE radio neutrino detectors - Bouma, Sjoerd; Clark, B.; Giri, P.; Glaser, C.; Hallmann, S.; Heyer, N.; Kravchenko, I.; Nelles, Anna; Oeyen, B.; Plaisier, I.; Pyras, Lilly Marie; Schlüter, F.; et al. (Proceedings of Science, 2023)
NuRadioMC is an open-source, Python-based simulation and reconstruction framework for radio detectors of ultra-high energy neutrinos and cosmic rays. Its modular design makes NuRadioMC suitable for use with a range of past, current and future detectors. In addition, the recent deployment of a complete documentation as well as a pip release make NuRadioMC relatively easy to learn and use. Here, we outline the features currently available and under development in NuRadioMC, with a focus on its usage to simulate and study in-ice radio neutrino detectors.
CRIS-Team Scopus Importer:2023-12-15

Validation of standardized data formats and tools for ground-level particle-based gamma-ray observatories - Albert, A.; Alfaro, R.; Arteaga-Velazquez, J. C.; Ayala Solares, H. A.; Babu, R.; Belmont-Moreno, E.; Brisbois, C.; Caballero-Mora, K. S.; Capistran, T.; Carraminana, A.; Casanova, S.; Chaparro-Amaro, O.; et al. (Astronomy & Astrophysics, 2022)
Context. Ground-based gamma-ray astronomy is still a rather young field of research, with strong historical connections to particle physics. This is why most observations are conducted by experiments with proprietary data and analysis software, as is usual in the particle physics field. However, in recent years, this paradigm has been slowly shifting toward the development and use of open-source data formats and tools, driven by upcoming observatories such as the Cherenkov Telescope Array (CTA). In this context, a community-driven, shared data format (the gamma-astro-data-format, or GADF) and analysis tools such as Gammapy and ctools have been developed. So far, these efforts have been led by the Imaging Atmospheric Cherenkov Telescope community, leaving out other types of ground-based gamma-ray instruments. Aims. We aim to show that the data from ground particle arrays, such as the High-Altitude Water Cherenkov (HAWC) observatory, are also compatible with the GADF and can thus be fully analyzed using the related tools, in this case, Gammapy. Methods. We reproduced several published HAWC results using Gammapy and data products compliant with GADF standard. We also illustrate the capabilities of the shared format and tools by producing a joint fit of the Crab spectrum including data from six different gamma-ray experiments. Results. We find excellent agreement with the reference results, a powerful confirmation of both the published results and the tools involved. Conclusions. The data from particle detector arrays such as the HAWC observatory can be adapted to the GADF and thus analyzed with Gammapy. A common data format and shared analysis tools allow multi-instrument joint analysis and effective data sharing. To emphasize this, a sample of Crab nebula event lists is made public with this paper. Because of the complementary nature of pointing and wide-field instruments, this synergy will be distinctly beneficial for the joint scientific exploitation of future observatories such as the Southern Wide-field Gamma-ray Observatory and CTA.
CRIS-Team WoS Importer:2022-11-25

3D Tensor Reconstruction in X-Ray Dark-Field Tomography: The First Phantom Result - Hu, Shiyang; Riess, Christian; Hornegger, Joachim; Fischer, Peter; Bayer, Florian; Weber, Thomas; Anton, Gisela; Maier, Andreas (Bildverarbeitung für die Medizin 2015, 2015)

A fast alignment method for grating-based X-ray phase-contrast imaging systems - Schuster, Max; Ludwig, Veronika; Akstaller, Bernhard; Seifert, Maria; Wolf, Andreas; Michel, Thilo; Neumayer, P.; Funk, Stefan; Anton, Gisela (Journal of Instrumentation, 2019)
The alignment of a grating-based X-ray phase-contrast interferometer is an iterative process that requires numerous steps of changing the distances and angles between the gratings. For each alignment step an image is acquired to evaluate the detected intensity signature in order to optimize the observed moir'e pattern. Thus, a large number of images has to be taken for the alignment procedure. This is not feasible within reasonable time at X-ray sources like X-ray backlighters where the time between two X-ray shots is on the scale of hours. Here, we report on the development of a stable and transportable setup ready-to-use for grating-based X-ray phase-contrast imaging. A comprehensive set of reference images taken at a continuous beam serves as a look-up table which enables the grating alignment within very few alignment steps. Since this method features a fast, reliable and predictable alignment, it is also beneficial for grating-based X-ray phase-contrast imaging systems at common X-ray sources.
CRIS-Team Scopus Importer:2019-10-08
Keywords: Inspection with x-rays; Plasma diagnostics - interferometry; spectroscopy and imaging; X-ray radiography and digital radiography (DR)

Assessing aerosol induced errors in Monte Carlo based air-shower reconstruction for atmospheric Cherenkov detectors - Holch, T. L.; Leuschner, F.; Schäfer, Johannes; Steinmassl, S. (Journal of Physics: Conference Series, 2022)
Aerosol levels influence the wavelength dependent transmission properties of the atmosphere. Variations in aerosol levels therefore affect the amount of Cherenkov light from air-showers that can reach an atmospheric Cherenkov detector. As the amount of detected Cherenkov light is directly related to a primary shower particle's energy, deviations between actual and assumed atmospheric transmission properties yield errors in reconstructed particle energies as well as energy axes of instrument response functions. In this work, a scheme is presented to assess this influence and potentially reduce related errors in the air-shower reconstruction. The proposed scheme relies on estimations or measurements of the aerosol optical depth and atmospheric density profile which are then used in radiative transfer simulations to generate atmospheric transmission profiles. As the scheme furthermore uses detector specific quantum efficiencies and generalised shower evolution models, it does not rely on detailed Monte Carlo simulations for the different atmospheric conditions but only on the transmission profile which the initial shower reconstruction algorithm is based on. The approach is derived and presented on the example of the H.E.S.S. experiment which employs imaging atmospheric Cherenkov telescopes in the Khomas Highland of Namibia to detect gamma rays in the GeV to TeV energy range.
CRIS-Team Scopus Importer:2024-12-16

Characterisation of the Hamamatsu R12199-01 HA MOD photomultiplier tube for low temperature applications - Elorrieta, M. A. Unland; Classen, L.; Reubelt, Jonas; Schmiemann, S.; Schneider, Jonas; Kappes, A. (Journal of Instrumentation, 2019)
We present a detailed characterisation of the new Hamamatsu R12199-01 HA MOD 3-inch photomultiplier tube (PMT) which is under consideration for the use in segmented optical modules of deep-ice neutrino detectors at the South Pole. Because of the significantly lower operation-temperature range compared to standard applications, a focus of our studies lies on the investigation of the temperature dependence of background characteristics (dark count rate, probability of correlated pulses), timing properties, gain and peak-to-valley ratio of this PMT type. In addition, the performance of the "HA coating" intended for background reduction was tested, as well as the influence of conductive objects near the photocathode like reflectors on the PMT noise rate. A low background rate is of particular importance as the deep ice at the South Pole features negligible optical background. We find that the new PMT type is well suited for the intended applications.
CRIS-Team WoS Importer:2019-04-16

Characterization of the Hamamatsu VUV4 MPPCs for nEXO - Gallina, G.; Giampa, P.; Retière, F.; Kroeger, J.; Zhang, G.; Ward, M.; Margetak, P.; Li, G.; Tsang, T.; Doria, L.; Al Kharusi, S.; Alfaris, M.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2019)
In this paper we report on the characterization of the Hamamatsu VUV4 (S/N: S13370-6152) Vacuum Ultra-Violet (VUV) sensitive Multi-Pixel Photon Counters (MPPC)s as part of the development of a solution for the detection of liquid xenon scintillation light for the nEXO experiment. Various MPPC features, such as: dark noise, gain, correlated avalanches, direct crosstalk and Photon Detection Efficiency (PDE) were measured in a dedicated setup at TRIUMF. MPPCs were characterized in the range 163K≤T≤233K. At an over voltage of 3.1±0.2 V and at T=163K we report a number of Correlated Avalanches (CAs) per pulse in the 1μs interval following the trigger pulse of 0.161±0.005. At the same settings the Dark-Noise (DN) rate is 0.137±0.002Hz/mm2. Both the number of CAs and the DN rate are within nEXO specifications. The PDE of the Hamamatsu VUV4 was measured for two different devices at T=233K for a mean wavelength of 189±7nm. At 3.6±0.2 V and 3.5±0.2 V of over voltage we report a PDE of 13.4±2.6% and 11±2%, corresponding to a saturation PDE of 14.8±2.8% and 12.2±2.3%, respectively. Both values are well below the 24% saturation PDE advertised by Hamamatsu. More generally, the second device tested at 3.5±0.2 V of over voltage is below the nEXO PDE requirement. The first one instead yields a PDE that is marginally close to meeting the nEXO specifications. This suggests that with modest improvements the Hamamatsu VUV4 MPPCs could be considered as an alternative to the FBK-LF Silicon Photo-Multipliers for the final design of the nEXO detector.
CRIS-Team Scopus Importer:2019-07-02
Keywords: Hamamatsu; MPPCs; nEXO; PDE; SiPMs; VUV4

Constraints on Lorentz Invariance Violation from HAWC Observations of Gamma Rays above 100 TeV - Albert, A.; Alfaro, R.; Alvarez, C.; Angeles Camacho, J. R.; Arteaga-Velazquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Solares, H. A. Ayala; Baghmanyan, V.; Belmont-Moreno, E.; Benzvi, S. Y.; Brisbois, C.; et al. (Physical Review Letters, 2020)
Because of the high energies and long distances to the sources, astrophysical observations provide a unique opportunity to test possible signatures of Lorentz invariance violation (LIV). Superluminal LIV enables the decay of photons at high energy. The high altitude water Cherenkov (HAWC) observatory is among the most sensitive gamma-ray instruments currently operating above 10 TeV. HAWC finds evidence of 100 TeV photon emission from at least four astrophysical sources. These observations exclude, for the strongest of the limits set, the LIV energy scale to 2.2 x 10(31) eV, over 1800 times the Planck energy and an improvement of 1 to 2 orders of magnitude over previous limits.
CRIS-Team WoS Importer:2020-04-14

Constraints on the emission region of 3C 279 during strong flares in 2014 and 2015 through VHE γ -ray observations with H.E.S.S. - Abdalla, H.; Adam, R.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Ashkar, H.; Backes, M.; Martins, V. Barbosa; Barnard, M.; et al. (Astronomy & Astrophysics, 2019)
The flat spectrum radio quasar 3C 279 is known to exhibit pronounced variability in the high-energy (100MeV < E < 100 GeV) gamma-ray band, which is continuously monitored with Fermi-LAT. During two periods of high activity in April 2014 and June 2015 target-of-opportunity observations were undertaken with the High Energy Stereoscopic System (H.E.S.S.) in the very-high-energy (VHE, E > 100 GeV) gamma-ray domain. While the observation in 2014 provides an upper limit, the observation in 2015 results in a signal with 8 : 7 sigma significance above an energy threshold of 66 GeV. No VHE variability was detected during the 2015 observations. The VHE photon spectrum is soft and described by a power-law index of 4.2 +/- 0.3. The H.E.S.S. data along with a detailed and contemporaneous multiwavelength data set provide constraints on the physical parameters of the emission region. The minimum distance of the emission region from the central black hole was estimated using two plausible geometries of the broad-line region and three potential intrinsic spectra. The emission region is confidently placed at r greater than or similar to 1 : 7 X 1017 cm from the black hole, that is beyond the assumed distance of the broad-line region. Time-dependent leptonic and lepto-hadronic one-zone models were used to describe the evolution of the 2015 flare. Neither model can fully reproduce the observations, despite testing various parameter sets. Furthermore, the H.E.S.S. data were used to derive constraints on Lorentz invariance violation given the large redshift of 3C 279.
CRIS-Team WoS Importer:2019-07-30
Keywords: Galaxies: active; Quasars: individual: 3C 279; Radiation mechanisms: non-thermal; Relativistic processes

Depth of shower maximum and mass composition of cosmic rays from 50 PeV to 2 EeV measured with the LOFAR radio telescope - Corstanje, A.; Buitink, S.; Falcke, H.; Hare, B. M.; Horandel, J. R.; Huege, T.; Krampah, G. K.; Mitra, P.; Mulrey, K.; Nelles, Anna; Pandya, H.; Rachen, J. P.; et al. (Physical Review D, 2021)
We present an updated cosmic-ray mass composition analysis in the energy range 10(16.8) to 10(18.3) eV from 334 air showers measured with the LOFAR radio telescope and selected for minimal bias. In this energy range, the origin of cosmic rays is expected to shift from galactic to extragalactic sources. The analysis is based on an improved method to infer the depth of the maximum X-max of extensive air showers from radio measurements and air shower simulations. We show results of the average and standard deviation of X-max versus primary energy and analyze the X-max dataset at the distribution level to estimate the cosmic ray mass composition. Our approach uses an unbinned maximum likelihood analysis, making use of existing parametrizations of the X-max distributions per element. The analysis has been repeated for three main models of hadronic interactions. Results are consistent with a significant light-mass fraction, at best fit 23% to 39% protons plus helium, depending on the choice of hadronic interaction model. The fraction of the intermediate-mass nuclei dominates. This confirms earlier results from LOFAR, with systematic uncertainties on X-max now lowered to 7 to 9 g/cm(2). We find agreement in mass composition compared to results from Pierre Auger Observatory, within statistical and systematic uncertainties. However, in line with earlier LOFAR results, we find a slightly lower average X-max. The values are in tension with those found at Pierre Auger Observatory but agree with results from other cosmic ray observatories based in the northern hemisphere.
CRIS-Team WoS Importer:2021-06-18

Development of a Software Framework for the ANTARES Acoustic Data and Simulations within the Framework - Würstlein, Alexander (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2010)

EUSO-TA - First results from a ground-based EUSO telescope - Abdellaoui, G.; Abe, S.; Adams, J. H.; Ahriche, A.; Allard, D.; Allen, L.; Alonso, G.; Anchordoqui, L.; Anzalone, A.; Arai, Y.; Asano, K.; Attallah, R.; et al. (Astroparticle Physics, 2018)
EUSO-TA is a ground-based telescope, installed at the Telescope Array (TA) site in Black Rock Mesa, Utah, USA. This is the first detector to successfully use a Fresnel lens based optical system and multi-anode photomultipliers (64 channels per tube, 2304 channels encompassing a 10.6 degrees x 10.6 degrees field of view) for detection of Ultra High Energy Cosmic Rays (UHECR). The telescope is located in front of one of the fluorescence detectors of the TA experiment. Since its installation in 2013, the detector has observed several ultra-high energy cosmic ray events and, in addition, meteors. The limiting magnitude of 5.5 on summed frames (similar to 3 ms) has been established. Measurements of the UV night sky emission in different conditions and moon phases and positions have been completed. The performed observations serve as a proof of concept for the future application of this detector technology. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: UHECR; EAS; JEM-EUSO; cosmic rays; Fresnel lens

Evaluation of X-ray phase-contrast imaging with the Medipix - Bartl, Peter; Michel, Thilo; Nachtrab, F.; Uhlmann, N.; Anton, Gisela (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2011)
In the recent decade phase-contrast imaging in the X-ray regime has been developed as a competitive alternative to conventional absorption radiography and computed tomography Wilkins et al. (1996) [1]. As phase-contrast is an energy dependent phenomenon, the use of a spectroscopic detector like the Medipix is a key tool to characterize and optimize imaging methods such as in-line or interferometric phase-contrast imaging. In the following the energy dependency of interference patterns caused by phase shifts in a coherent wavefront will be shown. Moreover, the spatial coherence of X-rays, considered as wavefronts, is crucial for the formation of detectable interference effects. The newest generations of X-ray sources produce small but finite focal spot sizes, so that partial spatial coherence of the wave-field has to be taken into account. The contribution of partial coherence to the image recorded in the detector plane has been investigated and the outcome will be presented. For a fuller understanding of a complete phase-contrast imaging setup the incoherent scattering effects were additionally simulated with Monte-Carlo methods. Furthermore, to develop a realistic simulation-tool for X-ray phase-contrast imaging, a good comprehension of the detection system is needed. This was also achieved by Monte-Carlo simulations. The comparison with measurements of the simulations of a complete setup shows a very good agreement.
EAM Import::2019-03-14

First ground-based measurement of sub-20 GeV to 100 GeV gamma-Rays from the Vela pulsar with HESS II - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, Michael; Barnard, M.; Becherini, Y.; Tjus, J. Becker; et al. (Astronomy & Astrophysics, 2018)
Aims. We report on the measurement and investigation of pulsed high-energy y-ray emission from the Vela pulsar, PSR B0833-45, based on observations with the largest telescope of H.E.S.S., CT5, in monoscopic mode, and on data obtained with the Fermi-LAT.
CRIS-Team WoS Importer:2020-01-15
Keywords: Gamma rays: stars; Pulsars: individual: PSR B0833-45; Radiation mechanisms: non-Thermal

First observations of speed of light tracks by a fluorescence detector looking down on the atmosphere - Abdellaoui, G.; Abe, S.; Adams, J. H.; Ahriche, A.; Allard, D.; Allen, L.; Alonso, G.; Anchordoqui, L.; Anzalone, A.; Arai, Y.; Asano, K.; Attallah, R.; et al. (Journal of Instrumentation, 2018)
EUSO-Balloon is a pathfinder mission for the Extreme Universe Space Observatory onboard the Japanese Experiment Module (JEM-EUSO). It was launched on the moonless night of the 25(th) of August 2014 from Timmins, Canada. The flight ended successfully after maintaining the target altitude of 38 km for five hours. One part of the mission was a 2.5 hour underflight using a helicopter equipped with three UV light sources (LED, xenon flasher and laser) to perform an inflight calibration and examine the detectors capability to measure tracks moving at the speed of light. We describe the helicopter laser system and details of the underflight as well as how the laser tracks were recorded and found in the data. These are the first recorded laser tracks measured from a fluorescence detector looking down on the atmosphere. Finally, we present a first reconstruction of the direction of the laser tracks relative to the detector.
Keywords: Detectors for UV; visible and IR photons; Lasers; Balloon instrumentation; Space instrumentation

Front-end electronics of the Compact High Energy Camera - Leach, S. A.; Lapington, J. S.; Ross, D.; Thornhill, J.; Duffy, C.; Funk, Stefan; Zink, Adrian; Jankowsky, David; White, R.; Zorn, J.; Tibaldo, L.; Varner, G.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2019)
The Compact High Energy Camera is a focal plane camera designed for two mirror Schwarzschild–Couder design imaging air Cherenkov telescopes such as the SST-2M variants on the Cherenkov Telescope Array. It utilises a 2048-pixel array of silicon photomultipliers arranged in thirty-two 8 x 8 pixel 2 tiles. Each detector tile is instrumented with a front-end electronics module designed to provide single photon counting with sub-nanosecond timing, full-waveform digitisation and event triggering capabilities based around TARGET ASICs. Performance results including triggering, digitiser noise, signal crosstalk, linearity and dynamic range from initial laboratory tests have been collated and are presented.
CRIS-Team Scopus Importer:2019-05-07
Keywords: CHEC; CTA; Front-end electronics; Full-waveform readout; Readout; Silicon photomultipliers; SST-2M; TARGET

HAWC J2227+610 and Its Association with G106.3+2.7, a New Potential Galactic PeVatron - Albert, A.; Alfaro, R.; Alvarez, C.; Angeles Camacho, J. R.; Arteaga-Velazquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Ayala Solares, H. A.; Baghmanyan, V.; Belmont-Moreno, E.; Benzvi, S. Y.; Brisbois, C.; et al. (Astrophysical Journal Letters, 2020)
We present the detection of very-high-energy gamma-ray emission above 100 TeV from HAWC J2227+610 with the High-Altitude Water Cherenov Gamma-Ray Observatory (HAWC) observatory. Combining our observations with previously published results by the Very Energetic Radiation Imaging Telescope Array System (VERTIAS), we interpret the gamma-ray emission from HAWC J2227+610 as emission from protons with a lower limit in their cutoff energy of 800 TeV. The most likely source of the protons is the associated supernova remnant G106.3+2.7, making it a good candidate for a Galactic PeVatron. However, a purely leptonic origin of the observed emission cannot be excluded at this time.
CRIS-Team Scopus Importer:2020-07-10

HILIGT, upper limit servers I — Overview - Saxton, R. D.; König, Ole; Descalzo, M.; Belanger, G.; Kretschmar, P.; Gabriel, C.; Evans, P. A.; Ibarra, A.; Colomo, E.; Sarmiento, M.; Salgado, J.; Agrafojo, A.; et al. (Astronomy and Computing, 2022)
The advent of all-sky facilities, such as the Neil Gehrels Swift observatory, the All Sky Automated Search for Supernovae (ASAS-SN), eROSITA and Gaia has led to a new appreciation of the importance of transient sources in solving outstanding astrophysical questions. Identification and catalogue cross-matching of transients has been eased over the last two decades by the Virtual Observatory but we still lack a client capable of providing a seamless, self-consistent, analysis of all observations made of a particular object by current and historical facilities. HILIGT is a web-based interface which polls individual servers written for XMM-Newton, INTEGRAL and other missions, to find the fluxes, or upper limits, from all observations made of a given target. These measurements are displayed as a table or a time series plot, which may be downloaded in a variety of formats. HILIGT currently works with data from X-ray and Gamma-ray observatories.
CRIS-Team Scopus Importer:2021-12-24
Keywords: Aperture photometry; Catalogs; Instrumentation: detectors; Surveys; Upper limit; X-rays: general

Influence of X-Ray Radiation on Historical Paper - Zippert, Patrick; Seuret, Mathias; Maier, Andreas; Hausotte, Tino (11th Conference on Industrial Computed Tomography, 2022)
Historical books are often so fragile that they cannot easily be opened in order to read the contents without damaging them. Current research shows, that industrial X-ray computed tomography (CT) can be used to examine closed historical manuscripts. However, the effect of X-rays on ancient paper has rarely been studied, making it difficult to assess the impact of CT measurements on fragile historical manuscripts in terms of additional destruction. To address this problem, various types of paper were exposed to high levels of X-ray radiation in order to examine them for change in optical properties. The investigations showed increasing yellowing due to the increased radiation energy. However, the severity of the yellowing is strongly dependent on the composition of the paper.<br
Keywords: Historical documents; CT measurement side effects; radiation damage

Multiple Galactic Sources with Emission Above 56 TeV Detected by HAWC - Albert, A.; Alfaro, R.; Avila Rojas, D.; Baghmanyan, V.; Belmont-Moreno, E.; Brisbois, C.; Capistran, T.; Carraminana, A.; Casanova, S.; Cotti, U.; Cotzomi, J.; Coutino De Leon, S.; et al. (Physical Review Letters, 2020)
We present the first catalog of gamma-ray sources emitting above 56 and 100 TeV with data from the High Altitude Water Cherenkov Observatory, a wide field-of-view observatory capable of detecting gamma rays up to a few hundred TeV. Nine sources are observed above 56 TeV, all of which are likely galactic in origin. Three sources continue emitting past 100 TeV, making this the highest-energy gamma-ray source catalog to date. We report the integral flux of each of these objects. We also report spectra for three high-estenergy sources and discuss the possibility that they are PeVatrons.
CRIS-Team WoS Importer:2020-01-31

Needle Propagation and Twinkling Characteristics - Hare, B. M.; Scholten, O.; Dwyer, J.; Strepka, C.; Buitink, S.; Corstanje, A.; Falcke, H.; Hörandel, Jörg R.; Huege, T.; Krampah, G. K.; Mitra, P.; Mulrey, K.; et al. (Journal of Geophysical Research: Atmospheres, 2021)
Recently, a new lightning phenomena, termed needles, has been observed in both VHF and in optical along positive lightning leaders. They appear as small (<100 m) leader branches that undergo dielectric breakdown at regular intervals (called twinkles). Providing a coherent and consistent explanation for this phenomenon is challenging as each twinkle is a form of negative breakdown that propagates away from the positive leader. In this study, we provide detailed observations of needles in VHF, observed during two lightning flashes. We show distributions of different needle properties, including twinkle propagation speeds, time between twinkles, and needle lengths, among others. We show a return stroke and multiple recoil leaders that quench needle activity. We also show that nearby needle activity does not seem to correlate together, and that needle twinkling can slow down by 10%–30% per twinkle. We conclude by presenting possibilities for how the positive leader could induce negative propagation away from the positive channel, and we argue that twinkles can propagate like a stepped leader or like a recoil leader depending on the temperature of the needle, which implies that needle twinkles can probably propagate without emitting VHF.
CRIS-Team Scopus Importer:2021-04-02
Keywords: imaging; lightning; LOFAR; mapping; needles; VHF

Operating performance of the gamma-ray Cherenkov telescope: An end-to-end Schwarzschild-Couder telescope prototype for the Cherenkov Telescope Array - Dournaux, J. L.; De Franco, A.; Laporte, P.; White, R.; Greenshaw, T.; Sol, H.; Abchiche, A.; Allan, D.; Amans, J. P.; Armstrong, T. P.; Balzer, A.; Berge, D.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2017)
The Cherenkov Telescope Array (CTA) consortium aims to build the next-generation ground-based very-high-energy gamma-ray observatory. The array will feature different sizes of telescopes allowing it to cover a wide gamma-ray energy band from about 20. GeV to above 100. TeV. The highest energies, above 5. TeV, will be covered by a large number of Small-Sized Telescopes (SSTs) with a field-of-view of around 9°. The Gamma-ray Cherenkov Telescope (GCT), based on Schwarzschild-Couder dual-mirror optics, is one of the three proposed SST designs. The GCT is described in this contribution and the first images of Cherenkov showers obtained using the telescope and its camera are presented. These were obtained in November 2015 in Meudon, France.
Keywords: Cherenkov detector; Cherenkov telescopes; CTA; GCT; IACT; Schwarzschild-Couder telescope

Performance analysis of X-Ray phase-contrast interferometers with respect to grating layouts - Haas, Wilhelm; Bartl, Peter; Bayer, Florian; Durst, Jürgen; Grund, T.; Kenntner, J.; Michel, Thilo; Ritter, André; Weber, Thomas; Anton, Gisela; Hornegger, Joachim (2010 IEEE Nuclear Science Symposium, Medical Imaging Conference, NSS/MIC 2010 and 17th International Workshop on Room-Temperature Semiconductor X-ray and Gamma-ray Detectors, RTSD 2010, 2010)
The grating-based phase-contrast imaging approach is highly dependent on the quality of the used gratings. While the fabrication of gratings for the soft X-ray range is more or less well controllable, the fabrication for the hard X-ray range (>30 keV) is more challenging as the gratings must have high aspect ratios and thus fine structures. One of the best fabrication technologies for such gratings is LIGA (Lithography, Electroplating and Molding). However, due to such small structures and high aspect ratio it is unavoidable that the gratings become non-perfect and have deformations. Since the fabrication is complex, expensive and time consuming, a simple way is needed to assess the influence of such deformations on the signal and also a simple way to design and test new grating layouts. This work presents a simulation framework for X-ray phase-contrast imaging which allows to model, simulate and assess the quality of arbitrary grating layouts in an easier, cheaper and faster way. Furthermore, it allows the assessment of the quality of new grating layouts as well as of existing gratings. © 2010 IEEE.

REVEALING W51C AS A COSMIC RAY SOURCE USING FERMI-LAT DATA - Jogler, T.; Funk, Stefan (Astrophysical Journal, 2016)
Supernova remnants (SNRs) are commonly believed to be the primary sources of Galactic cosmic rays. Despite intensive study of the non-thermal emission of many SNRs the identification of the accelerated particle type relies heavily on assumptions of ambient-medium parameters that are only loosely constrained. Compelling evidence of hadronic acceleration can be provided by detecting a strong roll-off in the secondary γ-ray spectrum below the production threshold energy of about 135 MeV, the so called "pion bump." Here we use five years of Fermi-Large Area Telescope data to study the spectrum above 60 MeV of the middle-aged SNR W51C. A clear break in the power-law γ-ray spectrum at is detected with significance and we show that this break is most likely associated with the energy production threshold of mesons. A high-energy break in the γ-ray spectrum at about 2.7 GeV is found with significance. The spectral index at energies beyond this second break is and closely matches the spectral index derived by the MAGIC Collaboration above 75 GeV. Therefore our analysis provides strong evidence to explain the γ-ray spectrum of W51C by a single particle population of protons with a momentum spectrum best described by a broken power law with break momentum W51C is the third middle-aged SNR that displays compelling evidence for cosmic-ray acceleration and thus strengthens the case of SNRs as the main source of Galactic cosmic rays.
Keywords: astroparticle physics; gamma-rays: general; ISM: supernova remnants

The 2014 TeV γ-Ray Flare of Mrk 501 Seen with H.E.S.S.: Temporal and Spectral Constraints on Lorentz Invariance Violation - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, M.; Barnard, M.; Becherini, Y.; Tjus, J. Becker; et al. (Astrophysical Journal, 2019)
The blazar Mrk 501 (z = 0.034) was observed at very-high-energy (VHE, E ≳ 100 GeV) gamma-ray wavelengths during a bright flare on the night of 2014 June 23-24 (MJD 56832) with the H.E.S.S. phase-II array of Cherenkov telescopes. Data taken that night by H.E.S.S. at large zenith angle reveal an exceptional number of gamma-ray photons at multi-TeV energies, with rapid flux variability and an energy coverage extending significantly up to 20 TeV. This data set is used to constrain Lorentz invariance violation (LIV) using two independent channels: a temporal approach considers the possibility of an energy dependence in the arrival time of gamma-rays, whereas a spectral approach considers the possibility of modifications to the interaction of VHE gamma-rays with extragalactic background light (EBL) photons. The non-detection of energy-dependent time delays and the non-observation of deviations between the measured spectrum and that of a supposed power-law intrinsic spectrum with standard EBL attenuation are used independently to derive strong constraints on the energy scale of LIV (E QG ) in the subluminal scenario for linear and quadratic perturbations in the dispersion relation of photons. For the case of linear perturbations, the 95% confidence level limits obtained are E QG,1 > 3.6 ×10 17 GeV using the temporal approach and E QG,1 > 2.6 ×10 19 GeV using the spectral approach. For the case of quadratic perturbations, the limits obtained are E QG,2 > 8.5 ×10 10 GeV using the temporal approach and E QG,2 > 7.8 ×10 11 GeV using the spectral approach.
CRIS-Team Scopus Importer:2019-05-14
Keywords: astroparticle physics; BL Lacertae objects: individual (Mrk 501); gamma rays: galaxies

The gamma-ray spectrum of the core of Centaurus A as observed with HESS and Fermi-LAT - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Armand, C.; Arrieta, M.; Backes, Michael; Balzer, A.; Barnard, M.; Becherini, Y.; et al. (Astronomy & Astrophysics, 2018)
Centaurus A (Cen A) is the nearest radio galaxy discovered as a very-high-energy (VHE; 100 GeV-100 TeV) gamma-ray source by the High Energy Stereoscopic System (H.E.S.S.). It is a faint VHE gamma-ray emitter, though its VHE flux exceeds both the extrapolation from early Fermi-LAT observations as well as expectations from a (misaligned) single-zone synchrotron-self Compton (SSC) description. The latter satisfactorily reproduces the emission from Cen A at lower energies up to a few GeV. New observations with H.E.S.S., comparable in exposure time to those previously reported, were performed and eight years of Fermi-LAT data were accumulated to clarify the spectral characteristics of the gamma-ray emission from the core of Cen A. The results allow us for the first time to achieve the goal of constructing a representative, contemporaneous gamma-ray core spectrum of Cen A over almost five orders of magnitude in energy. Advanced analysis methods, including the template fitting method, allow detection in the VHE range of the core with a statistical significance of 12 sigma on the basis of 213 hours of total exposure time. The spectrum in the energy range of 250 GeV-6 TeV is compatible with a power-law function with a photon index Gamma = 2.52 +/- 0.13(stat) +/- 0.20(sys). An updated Fermi-LAT analysis provides evidence for spectral hardening by Delta Gamma similar or equal to 0.4 +/- 0.1 at gamma-ray energies above 2.8(-0.6)(+1.0) GeV at a level of 4.0 sigma. The fact that the spectrum hardens at GeV energies and extends into the VHE regime disfavour a single-zone SSC interpretation for the overall spectral energy distribution (SED) of the core and is suggestive of a new gamma-ray emitting component connecting the high-energy emission above the break energy to the one observed at VHE energies. The absence of significant variability at both GeV and TeV energies does not yet allow disentanglement of the physical nature of this component, though a jet-related origin is possible and a simple two-zone SED model fit is provided to this end.
CRIS-Team WoS Importer:2020-01-15
Keywords: Radiation mechanisms: non-thermal; Gamma rays: galaxies

The relationship between the shape of SPARC rotation curves to the galactic mass model: a chi-square test of independence - Haethaisong, Waeowan; Duangchan, Chaimongkol; Wechakama, Maneenate (Journal of Physics: Conference Series, 2023)
Rotation curves of galaxies are strongly related to dark matter and baryonic matter. The gravitational attraction of baryonic matter, e.g., stars and gas, is the dominant force in the inner regions of galaxies, and its distribution determines the shape of the inner rotation curve. In contrast, the outer regions of galaxies are dominated by the gravitational force of dark matter, which is thought to be distributed in a spherical halo around a galaxy. Since the ratio of rotational speed in the inner regions and maximum rotational speed (ηrot) is related to the shape of the galaxy rotation curve, it might be a significant association between this ratio and each combination of matters, or the mass models. Specifically, for dark matter, we assume the Navarro-Frenk-White (NFW) profile. This study explores the use of SPARC data (Spitzer Photometry and Accurate Rotation Curves) and categorizes shapes of galaxy rotation curves according to ηrot. For mass models, we classify galaxies by considering the reduced chi-square of the best-fit parameter of each model. To determine whether there is a significant association between ηrot and the mass models, we utilize the chi-square test of independence. The study suggests with a 95% confidence level that there is no relation between the mass models and ηrot.
CRIS-Team Scopus Importer:2024-12-16

Very high energy gamma-ray emission from two blazars of unknown redshift and upper limits on their distance - Abdalla, H.; Adam, R.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Baghmanyan, V.; et al. (Monthly Notices of the Royal Astronomical Society, 2020)
We report on the detection of very high energy (VHE; E > 100 GeV) gamma-ray emission from the BL Lac objects KUV 00311-1938 and PKS 1440-389 with the High Energy Stereoscopic System (H.E.S.S.). H.E.S.S. observations were accompanied or preceded by multiwavelength observations with Fermi/LAT, XRT and UVOT onboard the Swift satellite, and ATOM. Based on an extrapolation of the Fermi/LAT spectrum towards the VHE gamma-ray regime, we deduce a 95 per cent confidence level upper limit on the unknown redshift of KUV 00311-1938 of z < 0.98 and of PKS 1440-389 of z < 0.53. When combined with previous spectroscopy results, the redshift of KUV 00311-1938 is constrained to 0.51 <= z < 0.98 and of PKS 1440-389 to 0.14 (sic) z < 0.53.
CRIS-Team WoS Importer:2020-06-26